Optical adhesive tape
Patent Information
- Application Number
- CN202280012018.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-11-05
- Filing Date
- 2022-01-26
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-01-26
AI Technical Summary
[0007]在拼接显示器中,为了使多个图像显示装置之间不明显,需要使间隙变窄(例如100μm以下),但是存在如下问题:在使用环境下图像显示装置收缩或膨胀,从而间隙稍微变大或者图像显示装置产生微小的重叠而使间隙明显,而且透明性降低、外观变差
[0036] By using the optical adhesive tape of the present invention in the manufacture of a video wall display obtained by arranging multiple image display devices, it is possible to suppress the shrinkage or expansion of the image display devices under the use environment. Therefore, the gaps between the image display devices are less likely to become noticeable, and a good appearance can be maintained. In addition, transparency can be maintained without change. Furthermore, even if the image display devices expand or shrink to some extent, the adhesive layer is less likely to bulge or peel off, thus enabling the efficient manufacture of high-performance video wall displays.
Smart Images

Figure CN116806246B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to optical adhesive tapes. More specifically, this invention relates to optical adhesive tapes suitable for manufacturing tiled displays that arrange multiple image display devices in a tile-like pattern. Background Technology
[0002] With the increasing demand for higher resolutions such as 4K and 8K, the need for larger screen image display devices is growing. Furthermore, the application of large-screen image display devices in outdoor advertising displays and signage such as bulletin boards in public facilities is being promoted. However, the manufacture of large-screen image display devices has led to problems such as lower yield rates and higher manufacturing costs. To manufacture large-screen image display devices at a lower cost, research is underway on tile-shaped splicing displays (e.g., Patent Document 1).
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Application Publication No. 2017-161634 Summary of the Invention
[0006] The problem that the invention aims to solve
[0007] In video wall displays, to minimize the visual impact between multiple image display devices, the gaps need to be narrowed (e.g., below 100 μm). However, this presents several problems: the image display devices may shrink or expand during use, slightly increasing the gaps or causing minor overlap, making the gaps more noticeable, and reducing transparency and appearance. Furthermore, the adhesive layer used to bond the optical components between the image display devices may not keep pace with their shrinkage and expansion, leading to bulging or peeling at the ends and further deteriorating the appearance.
[0008] The present invention is proposed based on the above circumstances. The purpose of the present invention is to provide an optical adhesive tape that is used in a tile-shaped splicing display in which multiple image display devices are arranged, so that even in the use environment, the gaps between the multiple image display devices are not obvious, and transparency and good appearance are maintained.
[0009] means for solving problems
[0010] That is, a first aspect of the present invention provides an optical adhesive tape having a laminated structure obtained by laminating a substrate and an adhesive layer, wherein the substrate has a first side and a second side, and the adhesive layer is laminated on the first side of the substrate.
[0011] The optical adhesive tape of the first aspect of the present invention, after being heated for 500 hours at 60°C and 90% relative humidity, exhibits an average dimensional change rate in both the width and length directions within ±0.15%. From the viewpoint of suppressing shrinkage or expansion of the image display devices under use, suppressing noticeable gaps between image display devices, and maintaining a good appearance in a splicing display obtained by arranging multiple image display devices with the optical adhesive tape of the first aspect of the present invention stacked together, and from the viewpoint of minimizing shrinkage or expansion and maintaining transparency, a configuration with an average dimensional change rate within ±0.15% is suitable. From the viewpoint of suppressing noticeable gaps between image display devices, minimizing shrinkage or expansion, and maintaining transparency, the aforementioned average dimensional change rate is preferably within ±0.1%, and may also be within ±0.05%.
[0012] In the optical adhesive tape of the first aspect of the present invention, the recovery rate of the adhesive layer determined in the following shear test is 95% or less.
[0013] <Shear Test>
[0014] The strain A (%) was measured when a shear force of 500 Pa in the torsional direction was applied to a disc-shaped adhesive layer with a thickness of 2 mm and a diameter of 7.9 mm for 600 seconds at 60 °C, and the strain B (%) was measured when the layer was held at a shear force of 0 Pa for 1800 seconds. The recovery rate (%) was calculated using the following formula.
[0015] Recovery rate (%) = (Sufficiency A - Sufficiency B) / Sufficiency A × 100
[0016] In this specification, when referring to “strain A”, “strain B”, or “recovery rate”, unless otherwise stated, they refer to “strain A”, “strain B”, or “recovery rate” as determined in the above-described shear test.
[0017] From the perspectives of ensuring the adhesive layer adequately follows the shrinkage or expansion of the image display device to which the optical adhesive tape of the first aspect of the present invention is laminated, suppressing bulging or peeling, and maintaining unchanged transparency, a recovery rate of 95% or less for the adhesive layer is preferred. Furthermore, from the perspective of ensuring the adhesive layer adequately follows the height difference caused by wiring or other irregularities on the adhered surface such as the image display panel, filling the gap without leaving air bubbles, a recovery rate of 95% or less for the adhesive layer is also preferred. From the perspectives of suppressing bulging or peeling of the optical adhesive tape of the first aspect of the present invention, maintaining unchanged transparency, and following height differences, a recovery rate of 94% or less for the adhesive layer is preferred, and may also be 93.5% or less.
[0018] The optical adhesive tape of the first aspect of the present invention preferably satisfies the following formula:
[0019] |C×D|≤3
[0020] In the above formula,
[0021] C represents the average dimensional change rate [%) of the width and length directions of the optical adhesive tape of the first aspect of the present invention after heating it at 60°C and 90% relative humidity for 500 hours.
[0022] D is the maximum curl [mm] of the laminate obtained by bonding the adhesive layer of the aforementioned optical adhesive tape onto a 50μm thick PET film, cutting it into 10cm squares, and heating the laminate at 60°C and 90% relative humidity for 500 hours.
[0023] • Maximum curl amount: With the convex side of the laminate facing down on a horizontal surface, the highest warp amount among the four corner warp amounts is defined as the maximum curl amount D [mm]. The maximum curl amount measured with the PET film side of the laminate facing down on a horizontal surface is defined as +, and the maximum curl amount measured with the substrate side of the laminate facing down on a horizontal surface is defined as -.
[0024] From the viewpoint that changes in the gaps between image display devices are not easily visually discernible in a splicing display obtained by arranging multiple image display devices with optical adhesive tape of the first aspect of the present invention, and that the image display devices can be precisely bonded to the film substrate, a configuration in which the absolute value of the product of the average dimensional change rate C [%) and the maximum curling amount D [mm], |C×D|, is 3 or less is suitable. From the viewpoint that changes in the gaps between image display devices are not easily visually discernible and that the image display devices can be precisely bonded to the film substrate, the aforementioned |C×D| is preferably 2.5 or less, more preferably 2.4 or less, and may also be 2.3 or less or 2.2 or less.
[0025] In the optical adhesive tape of the first aspect of the present invention, there is no particular limitation on the strain A of the adhesive layer obtained in the shear test, but it is preferably 3% or more. From the viewpoint that the adhesive layer adequately follows the shrinkage or expansion of the image display device to which the optical adhesive tape of the first aspect of the present invention is laminated, and can suppress bulging or peeling, a strain A of 3% or more for the adhesive layer is preferred. Furthermore, from the viewpoint that when there is a height difference in the shape of unevenness caused by wiring or the like on the adhered object such as the image display panel, a strain A of 3% or more for the adhesive layer adequately follows this height difference and can fill it without leaving air bubbles, is also preferred. From the viewpoint of suppressing bulging or peeling of the optical adhesive tape of the present invention and being able to follow the height difference, the strain A of the adhesive layer of the present invention is preferably 4% or more, and may also be 5% or more.
[0026] In the optical adhesive tape of the first aspect of the present invention, there is no particular limitation on the strain B of the adhesive layer obtained in the shear test, but it is preferably 0.1% or more. From the viewpoint that the adhesive layer adequately follows the shrinkage or expansion of the image display device on which the optical adhesive tape of the first aspect of the present invention is laminated, and that bulging or peeling can be suppressed, a strain B of 0.1% or more for the adhesive layer is preferred. Furthermore, from the viewpoint that when there is a height difference in the shape of unevenness caused by wiring or the like on the adhered object such as the image display panel, a strain B of 0.1% or more for the adhesive layer adequately follows this height difference and can fill it without leaving air bubbles, is also preferred. From the viewpoint of suppressing bulging or peeling of the optical adhesive tape of the present invention and being able to follow the height difference, the strain B of the adhesive layer of the present invention is preferably 0.2% or more, and may also be 0.3% or more.
[0027] In the optical adhesive tape of the first aspect of the present invention, the glass transition temperature (Tg) of the substrate is preferably 60°C or higher. From the viewpoint of ensuring the mechanical stability of the image display devices in the usage environment in a video wall display obtained by arranging multiple image display devices on which the optical adhesive tape of the first aspect of the present invention is stacked, a glass transition temperature of 60°C or higher for the substrate is preferred. From the viewpoint of ensuring the mechanical stability of the image display devices, the glass transition temperature of the substrate can be 63°C or higher or 65°C or higher.
[0028] In the optical adhesive tape of the first aspect of the present invention, the glass transition temperature (Tg) of the adhesive layer is preferably -10°C or lower. From the viewpoints of maintaining stress relaxation of the adhesive layer even in low-temperature environments, ensuring that the adhesive layer adequately follows the shrinkage or expansion of the image display device to which the optical adhesive tape of the first aspect of the present invention is laminated under operating conditions, suppressing bulging or peeling, and ensuring sufficient adhesion to the adhered object, a Tg of -10°C or lower for the adhesive layer is preferred. From the viewpoints of suppressing bulging or peeling in the image display device and good adhesion to the adhered object, the glass transition temperature of the adhesive layer is preferably -15°C or lower, and may also be -20°C or lower.
[0029] The humidity expansion rate of the optical adhesive tape of the first aspect of the present invention when humidified from 60°C and 30% relative humidity to 60°C and 60% relative humidity is preferably 0.1% or less. From the viewpoint of suppressing the expansion of the image display devices caused by moisture absorption and suppressing the widening of gaps between the image display devices in a splicing display obtained by arranging multiple image display devices on which the optical adhesive tape of the first aspect of the present invention is stacked, and from the viewpoint of minimizing shrinkage or expansion and maintaining transparency, the aforementioned humidity expansion rate of 0.1% or less is suitable. From the viewpoint of suppressing the expansion of the image display devices caused by moisture absorption, minimizing shrinkage or expansion, and maintaining transparency, the aforementioned humidity expansion rate is preferably 0.08% or less, and may also be 0.06% or less.
[0030] In the optical adhesive tape of the first aspect of the present invention, the coefficient of hygroscopic expansion of the substrate is preferably 5 × 10⁻⁶. -5 Below / %RH. From the viewpoint of improving the dimensional stability of the above-mentioned substrate under humidity changes; and from the viewpoint of suppressing the shrinkage or expansion of the image display devices under the usage environment and suppressing the gaps between the image display devices from becoming obvious in a splicing display obtained by arranging multiple image display devices with optical adhesive tape of the first aspect of the present invention, thereby maintaining a good appearance; and from the viewpoint of minimizing shrinkage or expansion and maintaining unchanged transparency, the humidity expansion coefficient of the above-mentioned substrate is 5 × 10⁻⁶. -5 The following composition with / %RH is suitable. From the viewpoints of dimensional stability, minimal shrinkage or expansion, and maintaining unchanged transparency, the humidity expansion coefficient of the above-mentioned substrate is preferably 3 × 10⁻⁶. -5 The following / %RH can also be 2×10 -5 Below / %RH.
[0031] In the optical adhesive tape of the first aspect of the present invention, it is preferable that the second surface of the substrate is subjected to anti-reflection treatment and / or anti-glare treatment. From the viewpoint of preventing reflections caused by metal wiring, ITO wiring, etc., disposed on the substrate of the image display device, the configuration in which the second surface of the substrate is subjected to anti-reflection treatment and / or anti-glare treatment is preferred. Furthermore, from the viewpoint that in a video wall display obtained by arranging multiple image display devices on which the optical adhesive tape of the first aspect of the present invention is stacked, it is difficult to visually discern the gaps between the image display devices, the configuration in which the second surface of the substrate is subjected to anti-reflection treatment and / or anti-glare treatment is also preferred.
[0032] In the optical adhesive tape of the first aspect of the present invention, the adhesive layer is preferably an acrylic adhesive layer comprising an acrylic polymer. This configuration is suitable from the viewpoint of adjusting the aforementioned properties of the adhesive layer (particularly strain A, strain B, and recovery rate).
[0033] Furthermore, a second aspect of the present invention provides an image display device obtained by stacking an optical adhesive tape of the first aspect of the present invention and an image display panel. Additionally, a third aspect of the present invention provides a video wall display obtained by arranging a plurality of image display devices of the second aspect of the present invention.
[0034] The image display device of the second aspect of the present invention, by incorporating the optical adhesive tape of the first aspect of the present invention in its laminated structure, can suppress shrinkage or expansion under operating conditions. Furthermore, even if the image display device of the second aspect of the present invention undergoes some degree of shrinkage or expansion, the adhesive layer adequately follows the shrinkage or expansion of the image display device, making bulging or peeling less likely. Therefore, in the splicing display of the third aspect of the present invention manufactured by arranging multiple image display devices of the second aspect of the present invention, the gaps between the image display devices are less likely to become noticeable under operating conditions, maintaining a good appearance. Additionally, transparency remains unchanged.
[0035] Invention Effects
[0036] By using the optical adhesive tape of the present invention in the manufacture of a video wall display obtained by arranging multiple image display devices, it is possible to suppress the shrinkage or expansion of the image display devices under the use environment. Therefore, the gaps between the image display devices are less likely to become noticeable, and a good appearance can be maintained. In addition, transparency can be maintained without change. Furthermore, even if the image display devices expand or shrink to some extent, the adhesive layer is less likely to bulge or peel off, thus enabling the efficient manufacture of high-performance video wall displays. Attached Figure Description
[0037] Figure 1This is a schematic diagram illustrating one embodiment of the optical adhesive tape of the present invention. Figure 1 (a) is a sectional view. Figure 1 (b) is a top view.
[0038] Figure 2 This is a schematic diagram (cross-sectional view) illustrating another embodiment of the optical adhesive tape of the present invention.
[0039] Figure 3 To indicate that there are layers Figure 2 A schematic diagram (cross-sectional view) of one embodiment of the image display device of the present invention using optical adhesive tape.
[0040] Figure 4 This is a schematic diagram (perspective view) illustrating one embodiment of the splicing display of the present invention.
[0041] Figure 5 This is a schematic diagram (three-dimensional view) used to illustrate the shear test. Detailed Implementation
[0042] A first aspect of the present invention provides an optical adhesive tape having a laminated structure obtained by laminating a substrate and an adhesive layer, wherein the substrate has a first side and a second side, and the adhesive layer is laminated on the first side of the substrate.
[0043] In this specification, the optical adhesive tape of the first aspect of the present invention is sometimes referred to as "the optical adhesive tape of the present invention". Furthermore, in this specification, the substrate and adhesive layer constituting the optical adhesive tape of the present invention are sometimes referred to as "the substrate of the present invention" and "the adhesive layer of the present invention", respectively. Additionally, "adhesive tape" includes the meaning of "adhesive sheet". That is, the optical adhesive tape of the present invention can also be an adhesive sheet having a sheet-like shape.
[0044] A second aspect of the present invention provides an image display device obtained by laminating an optical adhesive tape of the first aspect of the present invention and an image display panel. In this specification, the image display device of the second aspect of the present invention is sometimes referred to as "the image display device of the present invention".
[0045] Furthermore, a third aspect of the present invention provides a video wall display, which is obtained by arranging a plurality of image display devices of the present invention. In this specification, the video wall display of the third aspect of the present invention is sometimes referred to as "the video wall display of the present invention".
[0046] Hereinafter, embodiments of the optical adhesive tape of the present invention will be described with reference to the accompanying drawings. However, the present invention is not limited thereto, and is merely an example.
[0047] Figure 1This is a schematic diagram illustrating one embodiment of the optical adhesive tape of the present invention. Figure 1 (a) is a sectional view. Figure 1 (b) is a top view.
[0048] exist Figure 1 In (a), the optical adhesive tape 10A has a laminated structure obtained by laminating a substrate 1 and an adhesive layer 2. The substrate 1 has a first surface 1a and a second surface 1b, and the adhesive layer 2 is laminated on the first surface 1a of the substrate 1.
[0049] exist Figure 1 In (b), the width direction (TD) and longitudinal direction (MD) of the optical adhesive tape 10A are specified corresponding to the width direction (TD) and longitudinal direction (MD) of the substrate 1.
[0050] exist Figure 2 In this embodiment, the optical adhesive tape 10B has a laminated structure obtained by laminating a substrate 1 and an adhesive layer 2. The substrate 1 has a first surface 1a and a second surface 1b, and the adhesive layer 2 is laminated on the first surface 1a of the substrate 1. The second surface 1b of the substrate 1 is subjected to an anti-reflection treatment and / or an anti-glare treatment 3.
[0051] Figure 3 This is a schematic diagram (cross-sectional view) illustrating one embodiment of the image display device of the present invention. Figure 3 In the image display device 20, an image display panel 4 is laminated on the adhesive layer 2 of the optical adhesive tape 10B.
[0052] Figure 4 This is a schematic diagram (perspective view) illustrating one embodiment of the video wall display of the present invention. Figure 4 In the above, the splicing display 30 is formed by arranging nine image display devices 20 (layered structure omitted) in a 3×3 array on a support substrate 31 in a tile-like pattern, and the image display devices 20 are in contact with each other with a gap 32 between them.
[0053] The following is an explanation of each component.
[0054] <Optical Adhesive Tape>
[0055] In this invention, the term "optical" in the adhesive tape for optics refers to applications for optical purposes, and more specifically, to applications in the manufacture of products using optical components (optical products). Examples of optical products include image display devices and input devices such as touch panels, and this adhesive tape is suitable for manufacturing liquid crystal image display devices, self-emissive image display devices (e.g., organic EL (electroluminescent) image display devices, LED image display devices), etc. In particular, this adhesive tape for optics is suitable for manufacturing tiled displays that arrange multiple image display devices in a tile-like pattern.
[0056] The optical adhesive tape of the present invention is not particularly limited in form as long as the adhesive layer of the present invention is laminated on the first surface of the substrate of the present invention. For example, it can be a single-sided adhesive tape with only one side as the adhesive surface, or it can be a double-sided adhesive tape with both sides as the adhesive surface. In addition, when the optical adhesive tape of the present invention is a double-sided adhesive tape, it can have a form in which the adhesive layer of the present invention provides two adhesive surfaces, or it can have a form in which the adhesive layer of the present invention provides one adhesive surface and the other adhesive surface is provided by an adhesive layer other than the adhesive layer of the present invention. When the optical adhesive tape of the present invention constitutes the outermost surface of an optical product, a single-sided adhesive tape is preferred, and when the objects to be bonded (optical components) are bonded together, a double-sided adhesive tape is preferred.
[0057] In addition to the substrate and adhesive layer of the present invention, the optical adhesive tape of the present invention may have other layers on its surface or between any layers without impairing the effect of the present invention, such as a substrate other than the substrate of the present invention, an adhesive layer other than the adhesive layer of the present invention, an intermediate layer, a base coating, an antistatic layer, a spacer, a surface protective film, etc.
[0058] The average dimensional change rate in the width and longitudinal directions of the optical adhesive tape of the present invention, after being heated at 60°C and 90% relative humidity for 500 hours, is within ±0.15%. The dimensional change rate in the width and longitudinal directions is the percentage (%) of the dimensional change after heating at 60°C and 90% relative humidity for 500 hours with the initial dimensions in both directions set to 100%, calculated by the following formula.
[0059] Dimensional change rate (%) = [(Dimensions after heating for 500 hours at 60℃ and 90% relative humidity) - (Initial dimensions)] / (Initial dimensions) × 100
[0060] For the dimensional change rate (%), "+" indicates expansion and "-" indicates contraction. The average dimensional change rate in the width and longitudinal directions is the average of the dimensional change rates in the width and longitudinal directions, calculated by the following formula.
[0061] Average dimensional change rate (%) = [(dimensional change rate in width direction (%)) + (dimensional change rate in length direction (%))] / 2
[0062] It should be noted that there are no particular limitations on the size of the optical adhesive tape of the present invention, and it can usually be determined by measuring the length of the ends in the width direction and the longitudinal direction of the optical adhesive tape.
[0063] From the viewpoint of suppressing the shrinkage or expansion of the image display device of the present invention under the usage environment, suppressing the gap between image display devices from becoming obvious, and maintaining a good appearance in the splicing display of the present invention; and from the viewpoint of minimizing shrinkage or expansion and maintaining transparency, the above-mentioned configuration with an average size change rate within ±0.15% is suitable. From the viewpoint of suppressing the gap between image display devices from becoming obvious, minimizing shrinkage or expansion, and maintaining transparency, the above-mentioned average size change rate is preferably within ±0.1%, and may also be within ±0.05%.
[0064] The aforementioned average dimensional change rate of the optical adhesive tape of the present invention can be specifically measured by the method described in the embodiments below. The aforementioned average dimensional change rate of the optical adhesive tape of the present invention can be adjusted by adjusting the type or thickness of the resin constituting the substrate of the present invention, the coefficient of hygroscopic expansion or glass transition temperature of the substrate, the type of resin constituting the adhesive layer of the present invention, monomer composition, degree of crosslinking, elastic modulus, glass transition temperature, etc.
[0065] The optical adhesive tape of the present invention preferably satisfies the following formula:
[0066] |C×D|≤3
[0067] In the above formula,
[0068] C represents the average dimensional change rate [%) of the width and length directions of the optical adhesive tape of the present invention after heating it at 60°C and 90% relative humidity for 500 hours.
[0069] D is the maximum curl [mm] of the laminate obtained by bonding the adhesive layer of the aforementioned optical adhesive tape onto a 50μm thick PET film, cutting it into 10cm squares, and heating the laminate at 60°C and 90% relative humidity for 500 hours.
[0070] • Maximum curl amount: With the convex side of the laminate facing down on a horizontal surface, the highest warp amount among the four corner warp amounts is defined as the maximum curl amount D [mm]. The maximum curl amount measured with the PET film side of the laminate facing down on a horizontal surface is defined as +, and the maximum curl amount measured with the substrate side of the laminate facing down on a horizontal surface is defined as -.
[0071] From the viewpoint that changes in the gaps between image display devices are not easily visually discernible in a splicing display obtained by arranging multiple image display devices on which the optical adhesive tape of the present invention is stacked, and that the image display devices can be precisely bonded to the film substrate, a configuration in which the absolute value of the product of the average dimensional change rate C [%) and the maximum curling amount D [mm], |C×D|, is 3 or less is suitable. From the viewpoint that changes in the gaps between image display devices are not easily visually discernible, and that the image display devices can be precisely bonded to the film substrate, the aforementioned |C×D| is preferably 2.5 or less, more preferably 2.4 or less, and can be 2.3 or less or 2.2 or less.
[0072] There are no special restrictions on the lower limit value of |C×D| above, and the lower the value, the better. It can be above 0.001.
[0073] There is no particular limitation on the absolute value of the maximum curling amount |D| [mm]. From the viewpoint that the image display devices can be precisely bonded to the film substrate in a splicing display obtained by arranging multiple image display devices with the optical adhesive tape of the present invention stacked together, it is preferably 60 mm or less, more preferably 55 mm or less, and even more preferably 50 mm or less.
[0074] There are no special restrictions on the lower limit of |D|, and the lower the value, the better. It can be above 0.1 mm.
[0075] Specifically, the aforementioned |C×D| and |D| of the optical adhesive tape of the present invention can be measured by the method described in the embodiments below. The aforementioned |C×D| and |D| of the optical adhesive tape of the present invention can be adjusted by adjusting the type or thickness of the resin constituting the substrate of the present invention, the coefficient of hygroscopic expansion or glass transition temperature of the substrate, the type of resin constituting the adhesive layer of the present invention, monomer composition, degree of crosslinking, elastic modulus, glass transition temperature, etc.
[0076] The humidity expansion rate of the optical adhesive tape of the present invention when humidified from 60°C and 30% relative humidity to 60°C and 60% relative humidity is preferably 0.1% or less. From the viewpoint of suppressing the expansion of the image display device of the present invention due to moisture absorption and suppressing the widening of gaps between image display devices in the splicing display of the present invention, and from the viewpoint of minimizing shrinkage or expansion and maintaining unchanged transparency, the above-mentioned humidity expansion rate of 0.1% or less is suitable. From the viewpoint of suppressing the expansion of the image display device of the present invention due to moisture absorption, minimizing shrinkage or expansion, and maintaining unchanged transparency, the above-mentioned humidity expansion rate is preferably 0.08% or less, and may also be 0.06% or less.
[0077] The aforementioned humidity expansion rate of the optical adhesive tape of the present invention can be specifically measured by the method described in the embodiments below. The aforementioned humidity expansion rate of the optical adhesive tape of the present invention can be adjusted by adjusting the type or thickness of the resin constituting the substrate of the present invention, the humidity expansion coefficient or glass transition temperature of the substrate, the type of resin constituting the adhesive layer of the present invention, monomer composition, degree of crosslinking, elastic modulus, glass transition temperature, etc.
[0078] The ratio of the longitudinal dimensional change rate to the width dimensional change rate (longitudinal dimensional change rate / width dimensional change rate) of the optical adhesive tape of the present invention, when heated at 60°C and 90% relative humidity for 500 hours, is not particularly limited, but is preferably 0.5 or more and 2.0 or less. Within this range, in the splicing display of the present invention, the difference between the width and longitudinal dimensional change rates of the image display device under the usage environment is small, which is suitable from the viewpoint of suppressing noticeable gaps between image display devices and maintaining a good appearance; and from the viewpoint of minimizing shrinkage or expansion and maintaining unchanged transparency. From the viewpoint of suppressing noticeable gaps between image display devices, minimizing shrinkage or expansion, and maintaining unchanged transparency, the above ratio is preferably 0.6 or more and 1.8 or less, and may also be 0.7 or more and 1.5 or less.
[0079] The aforementioned ratio (longitudinal dimensional change rate / width dimensional change rate) of the optical adhesive tape of the present invention can be adjusted by adjusting the type or thickness of the resin constituting the substrate of the present invention, the coefficient of hygroscopic expansion or glass transition temperature of the substrate, the manufacturing conditions of the substrate (e.g., extrusion molding temperature, speed, etc.), the type of resin constituting the adhesive layer of the present invention, monomer composition, degree of crosslinking, elastic modulus, glass transition temperature, etc.
[0080] There is no particular limitation on the haze of the optical adhesive tape of the present invention, but 5% or more is preferred. From the viewpoint of preventing reflections caused by metal wiring, ITO wiring, etc., on the substrate of the image display panel disposed in the image display device of the present invention, and from the viewpoint of making it difficult to visually discern the gaps between image display devices in the splicing display of the present invention, a haze of 5% or more for the optical adhesive tape of the present invention is preferred, more preferably 6% or more, and may also be 7% or more. There is no particular limitation on the upper limit of the haze of the optical adhesive tape of the present invention, but from the viewpoint of the visual discernibility of the splicing display of the present invention, 50% or less is preferred, and may also be 40% or less or 30% or less.
[0081] The haze of the optical adhesive tape of the present invention can be measured according to JIS K 7136, and more specifically, it can be measured using the method described in the embodiments described later. The haze of the optical adhesive tape of the present invention can be adjusted by the type or thickness of the resin constituting the substrate of the present invention, the type or thickness of the resin constituting the adhesive layer of the present invention, and by performing anti-reflection treatment and / or anti-glare treatment on the surface of the substrate.
[0082] There is no particular limitation on the reflectivity of the optical adhesive tape of the present invention, but it is preferably 5% or less. From the viewpoint of preventing reflections caused by metal wiring, ITO wiring, etc., on the substrate of the image display panel disposed in the image display device of the present invention, and from the viewpoint that the gaps between image display devices are not easily visually discernible in the splicing display of the present invention, a reflectivity of 5% or less for the optical adhesive tape of the present invention is preferred, more preferably 3% or less, and may also be 1.5% or less. There is no particular limitation on the lower limit of the reflectivity of the optical adhesive tape of the present invention, and it may be 0.1% or more or 0.3% or more.
[0083] The reflectivity of the optical adhesive tape of the present invention can be measured according to JIS K 7361-1, and more specifically, it can be measured using the method described in the embodiments described later. The reflectivity of the optical adhesive tape of the present invention can be adjusted by the type or thickness of the resin constituting the substrate of the present invention, the type or thickness of the resin constituting the adhesive layer of the present invention, and by performing anti-reflection treatment and / or anti-glare treatment on the surface of the substrate.
[0084] There is no particular limitation on the total light transmittance of the optical adhesive tape of the present invention, but 85% or more is preferred. From the viewpoint of obtaining excellent transparency and excellent appearance of the image display device of the present invention, a total light transmittance of 85% or more for the optical adhesive tape of the present invention is preferred, more preferably 88% or more, and may also be 90% or more. There is no particular limitation on the upper limit of the total light transmittance of the optical adhesive tape of the present invention, and it may be 95% or less.
[0085] The total light transmittance of the optical adhesive tape of the present invention can be measured according to JIS K 7361-1. The total light transmittance of the optical adhesive tape of the present invention can be adjusted by the type or thickness of the resin constituting the substrate of the present invention, the type or thickness of the resin constituting the adhesive layer of the present invention, and by performing anti-reflection treatment and / or anti-glare treatment on the surface of the substrate.
[0086] There are no particular limitations on the thickness of the optical adhesive tape of the present invention. For example, when considering the workability, thinness, etc., such as dimensional stability, strength, operability, etc., it is preferred to be in the range of 10 μm to 500 μm, more preferably in the range of 20 μm to 300 μm, and most preferably in the range of 30 μm to 200 μm.
[0087] <Substrate>
[0088] Materials that constitute the base material of this invention include glass, plastic film, etc. Examples of plastic films mentioned above include: polyester resins such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN); cyclic olefin polymers (COP) (e.g., trade names "ARTON" (manufactured by JSR Corporation) and "ZEONOR" (manufactured by Zeon Corporation of Japan)); acrylic resins such as polymethyl methacrylate (PMMA); and plastic materials such as polycarbonate (PC), triacetyl cellulose (TAC), polysulfone, polyarylate, polyether ether ketone (PEEK), polyimide (PI), transparent polyimide (CPI), polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, and ethylene-propylene copolymer. Polyester resins such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), cyclic olefin polymers (COP), polycarbonate (PC), polyether ether ketone (PEEK), and transparent polyimide (CPI) are preferred due to their excellent dimensional stability and resistance to shrinkage. It should be noted that these plastic materials can be used alone or in combination of two or more. The substrate of this invention refers to the portion that is adhered to the substrate (such as an image display panel) along with the adhesive layer when the optical adhesive tape of this invention is applied to the substrate. The release liner that is peeled off during the use of the optical adhesive tape of this invention (during application) is not included in the "substrate".
[0089] The substrate of the present invention is a substrate having a film-like (substrate-like) shape with a first surface and a second surface. The width direction (TD) and longitudinal direction (MD) of the substrate of the present invention are directions determined in the substrate manufacturing process. For example, after the extrusion molding of the raw material resin material, the direction of flow of the film-like extruded body is longitudinal (MD), and the width direction (TD) is a direction orthogonal to the longitudinal direction.
[0090] The substrate of this invention is not particularly limited as long as it is an optical component constituting the aforementioned optical product; various optical films such as cover plates, polarizers, and retardation plates can be included, but it is preferred to use it as a cover plate component. When the substrate of this invention is a cover plate component, the second surface, for example, becomes the outermost surface of the aforementioned optical product.
[0091] There is no particular limitation on the glass transition temperature (Tg) of the substrate of the present invention, but it is preferably 60°C or higher. From the viewpoint of ensuring the mechanical stability of the image display device of the present invention in the usage environment of the splicing display of the present invention, a glass transition temperature of 60°C or higher for the substrate of the present invention is preferred. From the viewpoint of ensuring the mechanical stability of the image display device of the present invention, the glass transition temperature of the substrate can be 63°C or higher or 65°C or higher. In addition, there is no particular limitation on the upper limit of the glass transition temperature of the substrate, but from the viewpoint of simplifying the molding process of the substrate, the glass transition temperature of the substrate is preferably 350°C or lower, but can also be 250°C or lower, 200°C or lower, 140°C or lower, 130°C or lower, or 125°C or lower.
[0092] The glass transition temperature (Tg) of the substrate of the present invention can be measured according to JIS K 7121. The glass transition temperature (Tg) of the substrate of the present invention can be adjusted by the type of resin constituting the substrate of the present invention, etc.
[0093] There is no particular limitation on the coefficient of hygroscopic expansion of the substrate of the present invention, but it is preferably 5 × 10⁻⁶. -5 Below / %RH. From the viewpoints of improving the dimensional stability of the substrate of the present invention under humidity changes; suppressing the shrinkage or expansion of the image display device of the present invention in the splicing display of the present invention under the usage environment, and suppressing the gap between image display devices from becoming obvious, thereby maintaining a good appearance; and considering the viewpoints of minimal shrinkage or expansion and maintaining unchanged transparency, the humidity expansion coefficient of the substrate of the present invention is 5 × 10⁻⁶. -5 The following composition with / %RH is suitable. From the viewpoints of dimensional stability of the substrate of the present invention, minimal shrinkage or expansion, and the ability to maintain unchanged transparency, the coefficient of humidity expansion of the substrate of the present invention is preferably 3 × 10⁻⁶. -5 The following / %RH can also be 2×10 -5 Below / %RH.
[0094] There is no particular limitation on the lower limit of the humidity expansion coefficient of the substrate of the present invention, but a lower value is preferred, and it can be 0.001×10. -5 Above / %RH.
[0095] The coefficient of hygroscopic expansion of the substrate of the present invention can be specifically measured by the method described in the embodiments described later. The coefficient of hygroscopic expansion of the substrate of the present invention can be adjusted by the type of resin constituting the substrate of the present invention, the conditions during substrate manufacturing (temperature, extrusion speed, etc.), etc.
[0096] There is no particular limitation on the haze of the substrate of the present invention, but 5% or more is preferred. From the viewpoint of preventing reflections caused by metal wiring, ITO wiring, etc., on the substrate of the image display panel disposed in the image display device of the present invention, and from the viewpoint of making it difficult to visually discern the gaps between image display devices in the splicing display of the present invention, a haze of 5% or more for the substrate of the present invention is preferred, more preferably 6% or more, and may also be 7% or more. There is no particular limitation on the upper limit of the haze of the substrate of the present invention, but from the viewpoint of the visual discernibility of the splicing display of the present invention, 50% or less is preferred, and may also be 40% or less or 30% or less.
[0097] The haze of the substrate of the present invention can be measured according to JIS K 7136. The haze of the substrate of the present invention can be adjusted by the type or thickness of the resin constituting the substrate, by applying anti-reflective treatment and / or anti-glare treatment to the surface of the substrate, etc.
[0098] There is no particular limitation on the reflectivity of the substrate of the present invention, but it is preferably 5% or less. From the viewpoint of preventing reflections caused by metal wiring, ITO wiring, etc., on the substrate of the image display panel disposed in the image display device of the present invention, and from the viewpoint that the gaps between image display devices are not easily visually discernible in the splicing display of the present invention, a reflectivity of 5% or less for the substrate of the present invention is preferred, more preferably 3% or less, and may also be 1.5% or less. There is no particular limitation on the lower limit of the reflectivity of the substrate of the present invention, and it may be 0.1% or more or 0.3% or more.
[0099] The reflectivity of the substrate of the present invention can be measured according to JIS K 7361-1. The reflectivity of the substrate of the present invention can be adjusted by the type or thickness of the resin constituting the substrate, by applying anti-reflection treatment and / or anti-glare treatment to the surface of the substrate, etc.
[0100] There are no particular limitations on the thickness of the substrate of the present invention. For example, when considering workability such as dimensional stability, strength, and operability, as well as thinness, it is preferably in the range of 10 μm to 500 μm, more preferably in the range of 20 μm to 300 μm, and most preferably in the range of 30 μm to 200 μm. There are no particular limitations on the refractive index of the substrate of the present invention. For example, it is in the range of 1.30 to 1.80, preferably in the range of 1.40 to 1.70.
[0101] The second surface of the substrate of the present invention preferably undergoes anti-reflection treatment and / or anti-glare treatment. From the viewpoint of preventing reflections caused by metal wiring, ITO wiring, etc., disposed on the substrate of the image display device of the present invention, the configuration of performing anti-reflection treatment and / or anti-glare treatment on the second surface of the substrate of the present invention is preferred. Furthermore, from the viewpoint that the gaps between image display devices are not easily visually discernible in the splicing display of the present invention, the configuration of performing anti-reflection treatment and / or anti-glare treatment on the second surface of the substrate of the present invention is also preferred.
[0102] As an anti-reflection treatment as described above, known anti-reflection treatments can be used without particular limitations, such as anti-reflection (AR) treatments.
[0103] As for the aforementioned anti-reflective (AR) treatment, known AR treatments can be applied without particular limitations. Specifically, it can be implemented by forming an optical thin film with strictly controlled thickness and refractive index on the second surface of the substrate of the present invention, or by stacking two or more of the aforementioned optical thin films to obtain an anti-reflective layer (AR layer). The aforementioned AR layer exhibits anti-reflective function by utilizing the interference effect of light to cancel out the phase reversals of the incident and reflected light. Preferably, the AR layer is designed to exhibit anti-reflective function in the visible light wavelength range, for example, 380 nm to 780 nm, particularly in the wavelength range of 450 nm to 650 nm where visual sensitivity is high, and to minimize the reflectivity at its center wavelength of 550 nm.
[0104] As the aforementioned AR layer, a multilayer antireflective layer can generally be described as having a structure of 2 to 5 stacked optical thin layers (thickness and refractive index of thin films with strict control). By forming multiple layers with different refractive indices at a specified thickness, the optical design freedom of the AR layer is increased, which can further improve the antireflection effect and make the spectral reflectance characteristics more uniform (flat) in the visible light region. In the aforementioned optical thin films, due to the requirement of high thickness accuracy, the formation of each layer is generally carried out by dry vacuum evaporation, sputtering, CVD, etc.
[0105] Alternatively, the aforementioned AR layer can also be formed using an antireflective coating solution. This antireflective coating solution may contain, for example, resin, fluorine-containing additives, hollow particles, solid particles, and diluents, and can be manufactured, for example, by mixing these components.
[0106] Examples of the resins mentioned above include thermosetting resins and ionizing radiation-cured resins that are cured by ultraviolet light or light. Commercially available thermosetting resins and ultraviolet-cured resins can also be used as the resins mentioned above.
[0107] As for the aforementioned thermosetting and UV-curing resins, examples include curable compounds having at least one of acrylate and methacrylate groups that can be cured by heat, light (ultraviolet light, etc.), or electron beams. Examples include oligomers or prepolymers of acrylates or methacrylates of polyfunctional compounds such as silicone resins, polyester resins, polyether resins, epoxy resins, polyurethane resins, alkyd resins, spiroacetal resins, polybutadiene resins, polythiol polyene resins, and polyols. These can be used alone or in combination with two or more.
[0108] In the aforementioned resin, a reactive diluent having at least one of acrylate and methacrylate groups can also be used. The reactive diluent described in Japanese Patent Application Publication No. 2008-88309 can be used, including monofunctional acrylates, monofunctional methacrylates, polyfunctional acrylates, and polyfunctional methacrylates. As the aforementioned reactive diluent, trifunctional or higher acrylates and trifunctional or higher methacrylates are preferred. This is because it allows for excellent hardness of the second surface of the substrate of the present invention. Examples of the aforementioned reactive diluents include, for example, butanediol glycerol ether diacrylate, isocyanuric acid acrylate, and isocyanuric acid methacrylate. They can be used individually or in combination of two or more. The weight-average molecular weight of the aforementioned resin before curing can be, for example, 100 or more, 300 or more, 500 or more, 1,000 or more, or 2,000 or more, and can be 100,000 or less, 70,000 or less, 50,000 or less, 30,000 or less, or 10,000 or less. If the weight-average molecular weight before curing is high, the hardness decreases, but there is a tendency for cracks to form less easily when bent. On the other hand, if the weight-average molecular weight before curing is low, there is a tendency for increased intermolecular crosslinking density and increased hardness.
[0109] The resin described above preferably contains a polyfunctional acrylate (e.g., pentaerythritol triacrylate).
[0110] To cure the aforementioned curable resin, a curing agent may be added, for example. There are no particular limitations on the curing agent; for example, a known polymerization initiator (e.g., a thermal polymerization initiator, a photopolymerization initiator, etc.) may be appropriately used. There are no particular limitations on the amount of the curing agent added; relative to 100 parts by weight of the resin in the antireflective coating liquid, it may be, for example, 0.5 parts by weight or more, 1.0 parts by weight or more, 1.5 parts by weight or more, 2.0 parts by weight or more, or 2.5 parts by weight or more, or 15 parts by weight or less, 13 parts by weight or less, 10 parts by weight or less, 7 parts by weight or less, or 5 parts by weight or less.
[0111] There are no particular restrictions on the fluorine-containing additives mentioned above; for example, they can be organic or inorganic compounds containing fluorine in their molecules. There are no particular restrictions on the organic compounds mentioned above; examples include fluorine-containing antifouling coating agents, fluorine-containing acrylic compounds, and fluorine- and silicon-containing acrylic compounds. Specifically, examples of the organic compounds mentioned above include, for example, the trade name "KY-1203" manufactured by Shin-Etsu Chemical Industry Co., Ltd., and the trade name "MEGAFACE" manufactured by DIC Co., Ltd. There are no particular restrictions on the inorganic compounds mentioned above. There are no particular restrictions on the amount of the fluorine-containing additives mentioned above. For example, relative to the total weight of the solid components in the coating liquid for forming the antireflective layer, the weight of fluorine in the solid components can be, for example, 0.05% by weight or more, 0.1% by weight or more, 0.15% by weight or more, 0.20% by weight or more, or 0.25% by weight or more, and can be less than 20% by weight, less than 15% by weight, less than 10% by weight, less than 5% by weight, or less than 3% by weight. In addition, for example, relative to 100 parts by weight of the resin in the coating liquid for forming the antireflective layer, the weight of the fluorine-containing additive may be 0.05% by weight or more, 0.1% by weight or more, 0.15% by weight or more, 0.20% by weight or more, or 0.25% by weight or more, or less than 20% by weight, less than 15% by weight, less than 10% by weight, less than 5% by weight, or less than 3% by weight.
[0112] There are no particular limitations on the hollow particles mentioned above; for example, they can be silica particles, acrylic polymer particles, acrylic-styrene copolymer particles, etc. Examples of silica particles include those manufactured by Nippon Ketsubai Chemical Industry Co., Ltd. under the trade names "THRULYA 5320" and "THRULYA 4320". There are no particular limitations on the weight-average particle size of the hollow particles; for example, they can be 30 nm or more, 40 nm or more, 50 nm or more, 60 nm or more, or 70 nm or more, and can be 150 nm or less, 140 nm or less, 130 nm or less, 120 nm or less, or 110 nm or less. There are no particular limitations on the shape of the hollow particles; for example, they can be bead-like or approximately spherical, or irregularly shaped particles such as powder. Approximately spherical particles are preferred, more preferably approximately spherical particles with an aspect ratio of 1.5 or less, and most preferably spherical particles. By adding the hollow particles mentioned above, for example, a low refractive index and good anti-reflection properties of the aforementioned anti-reflection layer can be achieved. There is no particular limitation on the amount of hollow particles added. Relative to 100 parts by weight of the resin in the coating liquid for forming the antireflective layer, the amount can be, for example, 30 parts by weight or more, 50 parts by weight or more, 70 parts by weight or more, 90 parts by weight or more, or 100 parts by weight or more, or less than 300 parts by weight, less than 270 parts by weight, less than 250 parts by weight, less than 200 parts by weight, or less than 180 parts by weight. From the viewpoint of reducing the refractive index of the antireflective layer, it is preferable that the amount of hollow particles added is not too small; from the viewpoint of ensuring the mechanical properties of the antireflective layer, it is preferable that the amount of hollow particles added is not too large.
[0113] There are no particular limitations on the solid particles mentioned above; for example, they can be silica particles, zirconium oxide particles, titanium-containing particles (e.g., titanium oxide particles), etc. Examples of silica particles include those manufactured by Nissan Chemical Industries, Ltd. under the trade names "MEK-2140Z-AC," "MIBK-ST," and "IPA-ST." There are no particular limitations on the weight-average particle size of the solid particles mentioned above; for example, they can be 5 nm or more, 10 nm or more, 15 nm or more, 20 nm or more, or 25 nm or more, and can be less than 300 nm, less than 250 nm, less than 200 nm, less than 150 nm, or less than 100 nm. There are no particular limitations on the shape of the solid particles mentioned above; for example, they can be bead-like or approximately spherical, or irregularly shaped particles such as powder. Approximately spherical particles are preferred, more preferably approximately spherical particles with an aspect ratio of 1.5 or less, and most preferably spherical particles. By adding the aforementioned solid particles, such as the aforementioned fluorine-containing additives, they easily concentrate on the surface of the coating liquid for forming the antireflective layer, resulting in excellent scratch resistance of the antireflective layer and achieving low refractive index and good antireflective properties. There are no particular limitations on the amount of the solid particles added; relative to 100 parts by weight of the resin in the coating liquid for forming the antireflective layer, it can be, for example, 5 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, 20 parts by weight or more, or 25 parts by weight or more, or less than 150 parts by weight, less than 120 parts by weight, less than 100 parts by weight, or less than 80 parts by weight.
[0114] The diluting solvent mentioned above can be, for example, a mixed solvent containing MIBK (methyl isobutyl ketone) and PMA (propylene glycol monomethyl ether acetate). There are no particular limitations on the mixing ratio in this case; when the weight of MIBK is set to 100% by weight, the weight of PMA can be, for example, 20% or more by weight, 50% or more by weight, 100% or more by weight, 150% or more by weight, or 200% or more by weight, or less than 400% by weight, 350% or less by weight, 300% or less by weight, or 250% or less by weight.
[0115] The aforementioned diluent can be, for example, a mixed solvent containing TBA (tert-butanol) in addition to MIBK and PMA. There are no particular limitations on the mixing ratio in this case. When the weight of MIBK is set to 100% by weight, the weight of PMA can be, for example, 10% or more by weight, 30% or more by weight, 50% or more by weight, 80% or more by weight, or 100% or more by weight, or less than 200% by weight, 180% or less by weight, 150% or less by weight, 130% or less by weight, or 110% or less by weight. Similarly, when the weight of MIBK is set to 100% by weight, the weight of TBA can be, for example, 10% or more by weight, 30% or more by weight, 50% or more by weight, 80% or more by weight, or 100% or more by weight, or less than 200% by weight, 180% or less by weight, 150% or less by weight, 130% or less by weight, or 110% or less by weight.
[0116] There are no particular limitations on the amount of the diluent added. For example, the weight of the solid component relative to the total weight of the antireflective coating liquid can be 0.1% by weight or more, 0.3% by weight or more, 0.5% by weight or more, 1.0% by weight or more, or 1.5% by weight or more. Alternatively, the weight of the solid component relative to the total weight of the antireflective coating liquid can be 20% by weight or less, 15% by weight or less, 10% by weight or less, 5% by weight or less, or 3% by weight or less. From the viewpoint of ensuring coatability (wetting, leveling), it is preferable that the content of the solid component is not too high. From the viewpoint of preventing drying spots, whitening, and other appearance defects caused by drying, it is preferable that the content of the solid component is not too low.
[0117] Next, the antireflective layer forming coating liquid is coated onto the second surface of the substrate of the present invention (the coating process described above). There are no particular limitations on the coating method; for example, known coating methods such as spray coating, die coating, spin coating, gravure coating, roller coating, and doctor blade coating can be appropriately used. There are also no particular limitations on the amount of the antireflective layer forming coating liquid applied; the thickness of the formed antireflective layer can be, for example, 0.1 μm or more, 0.3 μm or more, 0.5 μm or more, 1.0 μm or more, or 2.0 μm or more, and the thickness of the formed antireflective layer can be 50 μm or less, 40 μm or less, 30 μm or less, 20 μm or less, or 10 μm or less.
[0118] Next, the coated antireflective layer is dried using a coating solution to form a coating film (the coating film formation step described above). There are no particular limitations on the drying temperature; for example, it can be in the range of 30°C to 200°C. The drying temperature can be, for example, 40°C or higher, 50°C or higher, 60°C or higher, 70°C or higher, 80°C or higher, 90°C or higher, or 100°C or higher, and can be below 190°C, 180°C or lower, 170°C or lower, 160°C or lower, 150°C or lower, 140°C or lower, 135°C or lower, 130°C or lower, 120°C or lower, or 110°C or lower. There are no particular limitations on the drying time; for example, it can be 30 seconds or higher, 40 seconds or higher, 50 seconds or higher, or 60 seconds or higher, and can be below 150 seconds, 130 seconds or lower, 110 seconds or lower, or 90 seconds or lower.
[0119] In addition, the above-mentioned coating film can also be cured (curing process). The curing can be carried out, for example, by heating or light irradiation. There are no particular limitations on the light source; for example, it can be ultraviolet light. There are also no particular limitations on the light source used for irradiation; for example, it can be a high-pressure mercury lamp. The irradiation dose of the energy source in the ultraviolet curing process, measured in terms of cumulative exposure at an ultraviolet wavelength of 365 nm, is preferably 50 mJ / cm². 2 ~500mJ / cm 2 If the radiation dose is 50 mJ / cm 2 If the above conditions are met, curing can proceed smoothly and the resulting antireflective layer will have a higher hardness. Additionally, if the irradiation dose is 500 mJ / cm², curing will be more efficient. 2 The following can prevent the tinting of the formed antireflective layer.
[0120] As the aforementioned anti-glare (AG) treatment, known AG treatments can be applied without particular limitation, for example, by forming an anti-glare layer on the second surface of the substrate of the present invention. As the aforementioned anti-glare layer, known anti-glare layers can be used without limitation, and are generally formed in the form of a layer in which inorganic or organic particles as anti-glare agents are dispersed in a resin.
[0121] There are no particular limitations on the anti-glare layer described above. For example, an anti-glare layer forming material comprising resin, particles, and a thixotropic agent can be used, and protrusions are formed on the surface of the anti-glare layer by the aggregation of the particles and the thixotropic agent. According to this configuration, the anti-glare layer possesses excellent display properties that combine anti-glare and prevention of white blurring. Furthermore, although the anti-glare layer is formed by the aggregation of particles, the generation of protrusions on the surface of the anti-glare layer, which would otherwise be considered an appearance defect, can be prevented, thereby improving the product yield.
[0122] Examples of the aforementioned resins include thermosetting resins and ionizing radiation-cured resins that are cured by ultraviolet light or light. Commercially available thermosetting resins and ultraviolet-cured resins may also be used.
[0123] As for the aforementioned thermosetting and UV-curing resins, examples include curable compounds having at least one of acrylate and methacrylate groups that can be cured by heat, light (ultraviolet light, etc.), or electron beams. Examples include oligomers or prepolymers of acrylates, methacrylates, and other polyfunctional compounds such as silicone resins, polyester resins, polyether resins, epoxy resins, polyurethane resins, alkyd resins, spiroacetal resins, polybutadiene resins, polythiol polyene resins, and polyols. These can be used alone or in combination with two or more.
[0124] Reactive diluents having at least one of acrylate and methacrylate groups can also be used in the above-mentioned resins. For example, reactive diluents disclosed in Japanese Patent Application Publication No. 2008-88309 can be used, including monofunctional acrylates, monofunctional methacrylates, polyfunctional acrylates, and polyfunctional methacrylates. As the above-mentioned reactive diluents, trifunctional or higher acrylates and trifunctional or higher methacrylates are preferred. This is because they result in excellent hardness of the anti-glare layer. Examples of the above-mentioned reactive diluents include, for example, butylene glycol glycerol ether diacrylate, acrylates of isocyanuric acid, and methacrylates of isocyanuric acid. They can be used individually or in combination of two or more.
[0125] The resin described above preferably comprises a urethane acrylate resin, and more preferably a copolymer of a cured urethane acrylate resin and a polyfunctional acrylate (e.g., pentaerythritol triacrylate).
[0126] The main function of the particles used to form the anti-glare layer is to give the surface of the formed anti-glare layer an uneven shape, thereby imparting anti-glare properties, and to control the haze value of the anti-glare layer. The haze value of the anti-glare layer can be designed by controlling the refractive index difference between the particles and the resin. The particles include, for example, inorganic and organic particles. There are no particular limitations on the inorganic particles; examples include: silicon oxide particles, titanium oxide particles, aluminum oxide particles, zinc oxide particles, tin oxide particles, zirconium oxide particles, calcium carbonate particles, barium sulfate particles, talc particles, kaolin particles, and calcium sulfate particles. Similarly, there are no particular limitations on the organic particles; examples include: polymethyl methacrylate resin powder (PMMA microparticles), silicone resin powder, polystyrene resin powder, polycarbonate resin powder, acrylic-styrene resin powder, phenylguanidine resin powder, melamine resin powder, polyolefin resin powder, polyester resin powder, polyamide resin powder, polyimide resin powder, and polyvinyl fluoride resin powder. These inorganic and organic particles can be used individually or in combination with two or more.
[0127] The weight-average particle size (D) of the aforementioned particles is preferably in the range of 2.5 μm to 10 μm. By setting the weight-average particle size within this range, for example, the anti-glare performance is improved, and white blurring can be prevented. The weight-average particle size is more preferably in the range of 3 μm to 7 μm. It should be noted that the weight-average particle size can be determined, for example, by the Coulter counting method. For example, using a particle size distribution measuring device utilizing pore resistance (trade name: Coulter Multisizer, manufactured by Beckman Coulter), the resistance of the electrolyte equivalent to the particle volume when the particles pass through the pores is measured, thereby determining the number and volume of the particles and calculating the weight-average particle size.
[0128] There are no particular restrictions on the shape of the particles. For example, they can be bead-shaped or approximately spherical, or they can be irregularly shaped particles such as powder. Particles that are approximately spherical are preferred, particles that are approximately spherical with an aspect ratio of 1.5 or less are more preferred, and spherical particles are the most preferred.
[0129] The proportion of the particles in the anti-glare layer is preferably in the range of 0.2 parts by weight to 12 parts by weight, more preferably in the range of 0.5 parts by weight to 12 parts by weight, and even more preferably in the range of 1 part by weight to 7 parts by weight, relative to 100 parts by weight of the resin described above. By setting it within the above range, for example, the anti-glare performance is better, and white blurring can be prevented.
[0130] The aforementioned anti-glare layer may contain a thixotropic agent. By including the thixotropic agent, the aggregation state of the particles can be easily controlled. Examples of thixotropic agents used to form the aforementioned anti-glare layer include: organoclay, oxidized polyolefin, modified urea, etc.
[0131] The aforementioned organic clay is preferably an organically treated clay to improve its affinity with the aforementioned resin. Examples of organic clays include layered organic clays. The aforementioned organic clay can be homemade or commercially available. Examples of the aforementioned commercially available products include: Lucentite SAN, Lucentite STN, Lucentite SEN, Lucentite SPN, Somasif ME-100, Somasif MAE, Somasif MTE, Somasif MEE, and Somasif MPE (trade names, all manufactured by Co-op Chemical Co., Ltd.); Esben, Esben C, Esben E, Esben W, Esben P, Esben WX, Esben N-400, Esben NX, Esben NX80, Esben NO12S, Esben NEZ, Esben NO12, Esben NE, Esben NZ, Esben NZ70, Organite, Organite D, and Organite T (trade names, all manufactured by Hojun Co., Ltd.); Kunipia F, Kunipia G, and Kunipia G4 (trade names, all manufactured by Kunimine Industries, Ltd.); Thixogel VZ, Clayton HT, Clayton 40 (trade names, all manufactured by Rockwood Additives), etc.
[0132] The aforementioned oxidized polyolefins can be manufactured in-house or commercially available products can be used. Examples of such commercially available products include: Disparon 4200-20 (trade name, manufactured by Kusunoki Chemical Co., Ltd.) and Floron SA300 (trade name, manufactured by Kyoei Chemical Co., Ltd.).
[0133] The modified urea described above is a reaction product of isocyanate monomers or their adducts with an organic amine. This modified urea can be prepared in-house or commercially available products can be used. Examples of such commercially available products include BYK410 (manufactured by BYK Chemical Company).
[0134] The above-mentioned thixotropic agents can be used alone or in combination with two or more.
[0135] The height of the aforementioned convex portion, measured from the average roughness line of the anti-glare layer, is preferably less than 0.4 times the thickness of the anti-glare layer. More preferably, it is in the range of greater than or equal to 0.01 times and less than 0.4 times, and even more preferably, it is in the range of greater than or equal to 0.01 times and less than 0.3 times. If it is within this range, it is possible to appropriately prevent the formation of protrusions that become appearance defects on the aforementioned convex portion. The aforementioned anti-glare layer, with its convex portion of such height, is less prone to appearance defects. Here, the aforementioned height measured from the average roughness line can be measured, for example, by the method described in Japanese Patent Application Publication No. 2017-138620.
[0136] The proportion of the thixotropic agent in the anti-glare layer is preferably in the range of 0.1 parts by weight to 5 parts by weight, and more preferably in the range of 0.2 parts by weight to 4 parts by weight, relative to 100 parts by weight of the above-mentioned resin.
[0137] There is no particular limitation on the thickness (d) of the anti-glare layer, but it is preferably in the range of 3 μm to 12 μm. By setting the thickness (d) of the anti-glare layer within the above range, for example, curling of the optical adhesive tape of the present invention can be prevented, and problems such as poor transportability and reduced productivity can be avoided. In addition, when the thickness (d) is within the above range, the weight-average particle size (D) of the particles is preferably in the range of 2.5 μm to 10 μm as described above. By combining the thickness (d) of the anti-glare layer and the weight-average particle size (D) of the particles as described above, the anti-glare performance can be further improved. The thickness (d) of the anti-glare layer is more preferably in the range of 3 μm to 8 μm.
[0138] The relationship between the thickness (d) of the aforementioned anti-glare layer and the weight-average particle size (D) of the aforementioned particles is preferably within the range of 0.3 ≤ D / d ≤ 0.9. By satisfying this relationship, an anti-glare layer with superior anti-glare performance can be formed, which can prevent white blurring and has no appearance defects.
[0139] In the optical adhesive tape of the present invention, as described above, the anti-glare layer forms a convex portion on its surface by agglomeration of the particles and the thixotropic agent. In the agglomerated portion forming the convex portion, the particles exist in a state of multiple particle aggregation in the planar direction of the anti-glare layer. Thus, the convex portion becomes a gently sloping shape. The anti-glare layer, by having convex portions of such shape, can maintain its anti-glare properties, prevent white blurring, and is less prone to appearance defects.
[0140] The surface shape of the aforementioned anti-glare layer can be arbitrarily designed by controlling the aggregation state of the particles contained in the anti-glare layer forming material. The aggregation state of these particles can be controlled, for example, by the material of the particles (e.g., the chemical modification state of the particle surface, affinity for solvents or resins, etc.), the type of resin (binder), or the combination of solvents. Here, by utilizing a thixotropic agent contained in the aforementioned anti-glare layer forming material, the aggregation state of the particles can be controlled. As a result, the aggregation state of the particles can be as described above, and the aforementioned convex portion can be made into a gentler shape.
[0141] In the optical adhesive tape of the present invention, when the substrate of the present invention is formed of resin or the like, it is preferable to have a permeation layer at the interface between the substrate of the present invention and the anti-glare layer. This permeation layer is formed by the resin component contained in the anti-glare layer forming material permeating into the substrate of the present invention. When a permeation layer is formed, the adhesion between the substrate of the present invention and the anti-glare layer is improved, which is preferable. The thickness of the permeation layer is preferably in the range of 0.2 μm to 3 μm, more preferably in the range of 0.5 μm to 2 μm. For example, when the substrate of the present invention is a polyester resin and the resin contained in the anti-glare layer is an acrylic resin, the permeation layer can be formed. The thickness of the permeation layer can be confirmed and measured, for example, by observing the cross-section of the optical adhesive tape of the present invention using a transmission electron microscope (TEM).
[0142] Even when applied to the optical adhesive tape of the present invention having such a permeation layer, a smooth surface texture that combines anti-glare and prevention of white blurring can be easily formed. For the aforementioned permeation layer, the thicker the substrate to which the anti-glare layer adheres, the better the adhesion.
[0143] In the aforementioned anti-glare layer, it is preferable to have a layer every 1m 2 The anti-glare layer contains one or fewer appearance defects with a maximum diameter of 200 μm or more. More preferably, it has no such appearance defects.
[0144] In the uneven shape of the surface of the aforementioned anti-glare layer, the average tilt angle θa (°) is preferably in the range of 0.1 to 5.0, more preferably in the range of 0.3 to 4.5, even more preferably in the range of 1.0 to 4.0, and particularly preferably in the range of 1.6 to 4.0. Here, the aforementioned average tilt angle θa is a value defined by the following formula (1). The aforementioned average tilt angle θa is, for example, a value measured by the method described in Japanese Patent Application Publication No. 2017-138620.
[0145] The average tilt angle θa = tan⁻¹Δa(1)
[0146] In formula (1) above, as shown in formula (2) below, Δa is the sum of the differences (height h) between the apex of adjacent peaks and the lowest point of valleys in the reference length L of the roughness curve specified in JIS B 0601 (published in 1994), divided by the reference length L. The roughness curve above is obtained by removing surface ripple components longer than the specified wavelength from the cross-sectional curve using a phase difference compensated high-pass filter. In addition, the cross-sectional curve above refers to the profile that appears at the cut when the object surface is cut with a plane perpendicular to the object surface.
[0147] Δa=(h1+h2+h3……+hn) / L (2)
[0148] When θa is within the above range, the anti-glare performance is better and it can prevent white blurring.
[0149] When forming the above-mentioned anti-glare layer, the anti-glare layer forming material (coating liquid) preferably exhibits thixotropy, and the Ti value specified below is preferably in the range of 1.3 to 3.5, more preferably in the range of 1.3 to 2.8.
[0150] Ti value = β1 / β2
[0151] Here, β1 is the viscosity measured using RheoStress 6000 manufactured by HAAKE at a shear rate of 20 (1 / s), and β2 is the viscosity measured using RheoStress 6000 manufactured by HAAKE at a shear rate of 200 (1 / s).
[0152] When the Ti value is less than 1.3, appearance defects are easily generated, and the anti-glare and white blurring properties deteriorate. In addition, when the Ti value is greater than 3.5, the above particles are difficult to aggregate and tend to be dispersed.
[0153] There are no particular limitations on the manufacturing method of the above-mentioned anti-glare layer. It can be manufactured by any method, for example, by preparing an anti-glare layer forming material (coating liquid) comprising the above-mentioned resin, the above-mentioned particles, the above-mentioned thixotropic agent and solvent, coating the above-mentioned anti-glare layer forming material (coating liquid) onto the second surface of the substrate of the present invention to form a coating film, and curing the above-mentioned coating film to form an anti-glare layer. It is also possible to use a method of transferring using a mold, or a method of imparting an uneven shape by means of sandblasting, embossing rollers or other suitable methods.
[0154] There are no particular restrictions on the solvents mentioned above; various solvents can be used, either alone or in combination of two or more. Optimal solvent types and ratios exist based on the composition of the resin, the types of particles, and the types and contents of the thixotropic agents. As solvents, there are no particular limitations; examples include: alcohols such as methanol, ethanol, isopropanol, butanol, and 2-methoxyethanol; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclopentanone; esters such as methyl acetate, ethyl acetate, and butyl acetate; ethers such as diisopropyl ether and propylene glycol monomethyl ether; diols such as ethylene glycol and propylene glycol; cellosolves such as ethyl cellosolve and butyl cellosolve; aliphatic hydrocarbons such as hexane, heptane, and octane; and aromatic hydrocarbons such as benzene, toluene, and xylene.
[0155] For example, when using a polyester resin as the substrate of the present invention and forming the permeation layer, a good solvent for the polyester resin can be appropriately used. Examples of such solvents include ethyl acetate, methyl ethyl ketone, and cyclopentanone.
[0156] By appropriately selecting the solvents mentioned above, the thixotropic properties imparted to the anti-glare layer forming material (coating liquid) by the thixotropic agent can be well exhibited. For example, in the case of using organic clay, toluene and xylene can be used alone or in combination; in the case of using oxidized polyolefin, methyl ethyl ketone, ethyl acetate, and propylene glycol monomethyl ether can be used alone or in combination; and in the case of using modified urea, butyl acetate and methyl isobutyl ketone can be used alone or in combination.
[0157] Various leveling agents can be added to the aforementioned anti-glare layer forming material. As the leveling agent, to prevent uneven coating (homogenization of the coating surface), fluorinated or silicone-based leveling agents can be used, for example. The leveling agent can be appropriately selected depending on whether anti-fouling properties are required on the surface of the anti-glare layer, or whether an anti-reflective layer (low refractive index layer) or a layer containing an interlayer filler is formed on the anti-glare layer. For example, by containing the aforementioned thixotropic agent, the coating liquid can exhibit thixotropic properties, thus reducing the likelihood of uneven coating. Therefore, it has the advantage of expanding the options for the aforementioned leveling agents.
[0158] The amount of the leveling agent is, for example, 5 parts by weight or less, preferably in the range of 0.01 parts by weight to 5 parts by weight, relative to 100 parts by weight of the above resin.
[0159] In the aforementioned anti-glare layer forming material, pigments, fillers, dispersants, plasticizers, UV absorbers, surfactants, antifouling agents, antioxidants, etc., can be added as needed, within a range that does not impair performance. These additives can be used individually or in combination of two or more.
[0160] In the aforementioned anti-glare layer forming material, for example, a previously known photopolymerization initiator as described in Japanese Patent Application Publication No. 2008-88309 can be used.
[0161] As a method for coating the above-mentioned anti-glare layer forming material onto the second surface of the substrate of the present invention, coating methods such as spray coating, die coating, spin coating, spray coating, gravure coating, roller coating, and doctor blade coating can be used.
[0162] A coating film is formed on the substrate of the present invention by coating the aforementioned anti-glare layer forming material, and the coating film is then cured. Preferably, the coating film is dried before curing. The drying can be, for example, natural drying, air drying, heat drying, or a combination of these methods.
[0163] There are no particular limitations on the curing method for the coating film of the above-mentioned anti-glare layer forming material, but ultraviolet curing is preferred. The irradiation dose from the energy source, measured as the cumulative exposure dose at an ultraviolet wavelength of 365 nm, is preferably 50 mJ / cm². 2 ~500mJ / cm 2 If the radiation dose is 50 mJ / cm 2 The above process allows for more complete curing, resulting in a more sufficiently hard anti-glare layer. Additionally, if the irradiation dose is 500 mJ / cm²... 2 The following can prevent the coloring of the formed anti-glare layer.
[0164] The anti-glare layer described above can be formed on the second surface of the substrate of the present invention in the manner described above. It should be noted that the anti-glare layer can also be formed using manufacturing methods other than those described above. While the hardness of the anti-glare layer is also affected by the layer thickness, it is preferable to have a hardness of 2H or higher when measured using a pencil hardness tester.
[0165] The aforementioned anti-glare layer can be a multi-layered structure with two or more layers stacked together.
[0166] The aforementioned AR layer (low refractive index layer) can be disposed on the anti-glare layer. For example, when optical adhesive tape is installed in an image display device, one of the main reasons for reduced visual recognizability of the image is light reflection at the interface between the air and the anti-glare layer. The AR layer reduces surface reflection. It should be noted that the aforementioned anti-glare layer and anti-reflection layer can each be a multilayer structure with two or more layers stacked on top of each other.
[0167] In addition, in order to prevent the adhesion of pollutants and improve the ease of removal of the adhered pollutants, it is preferable to laminate an anti-pollution layer formed of fluorine-containing silane compounds or fluorine-containing organic compounds onto the aforementioned antireflective layer and / or anti-glare layer.
[0168] Preferably, at least one of the substrate of the present invention and the above-described anti-glare layer is surface-treated. If the surface of the substrate of the present invention is surface-treated, the adhesion to the above-described anti-glare layer is further improved. Furthermore, if the surface of the above-described anti-glare layer is surface-treated, the adhesion to the above-described AR layer is further improved.
[0169] To prevent curling of the substrate of the present invention, the other side of the anti-glare layer can be solvent-treated. Alternatively, to prevent curling, a transparent resin layer can be formed on the other side of the anti-glare layer.
[0170] <Adhesive layer>
[0171] The adhesive layer of the present invention can be an adhesive layer without a substrate (substrate layer) or an adhesive layer of the type having a substrate. It should be noted that in this specification, an adhesive layer without a substrate (substrate layer) is sometimes referred to as a "substrate-free adhesive layer," and an adhesive layer of the type having a substrate is sometimes referred to as a "substrate-supported adhesive layer." Examples of substrate-free adhesive layers include, for example, a single-layer adhesive layer containing only the adhesive layer of the present invention, and an adhesive layer containing the adhesive layer of the present invention and other adhesive layers (adhesive layers other than the adhesive layer of the present invention). Examples of substrate-supported adhesive layers include, for example, an adhesive layer having the adhesive layer of the present invention on both sides of the substrate, and an adhesive layer having the adhesive layer of the present invention on one side of the substrate and other adhesive layers on the other side. The "substrate (substrate layer)" constituting the "substrate-supported adhesive layer" can be the same plastic film as the substrate of the present invention.
[0172] Regarding the recovery rate of the adhesive layer of the present invention, the recovery rate determined in the following shear test is 95% or less.
[0173] <Shear Test>
[0174] The strain A (%) was measured when a shear force of 500 Pa in the torsional direction was applied to a disc-shaped adhesive layer with a thickness of 2 mm and a diameter of 7.9 mm for 600 seconds at 60 °C, and the strain B (%) was measured when the layer was held at a shear force of 0 Pa for 1800 seconds. The recovery rate (%) was calculated using the following formula.
[0175] Recovery rate (%) = (Sufficiency A - Sufficiency B) / Sufficiency A × 100
[0176] The above "shear test" is explained with reference to the attached diagram. Figure 5 This is a schematic diagram for illustrating a shear test; 40 represents the adhesive layer, and 41 and 42 represent parallel plates.
[0177] The adhesive layer 40 is a disc-shaped adhesive layer with a thickness of 2 mm and a diameter of 7.9 mm, and is composed of the adhesive layer of the present invention. Parallel plates 41 and 42 each have an upper surface and a bottom surface with a diameter of 7.9 mm, and are made, for example, of stainless steel. Figure 5 (a) Align and contact the upper surface of parallel plate 41 and the bottom surface of parallel plate 42 with the bottom and upper surfaces of adhesive layer 40, respectively. Figure 5 (b) Next, the ambient temperature was set to 60°C, and a torsional shear force F of 500 Pa was applied to the adhesive layer 40 for 600 seconds. Figure 5 (c)). Next, the shear force of parallel plates 41 and 42 is released, and the plate is placed at a shear force of 0 Pa for 1800 seconds. Figure 5 (d)). “Dependent variable A” is relative to the initial ( Figure 5 (b)) the outer periphery (100%) of the adhesive layer 40, at the moment when shear force F is applied for 600 seconds ( Figure 5 (c)) The percentage (%) of the change in the direction of torsion. “Due variable B” is relative to the initial ( Figure 5 (b) The outer periphery (100%) of the adhesive layer 40, after being subjected to a shear force F for 600 seconds and placed under a shear force of 0 Pa for 1800 seconds. Figure 5 (d) The percentage (%) of the change in the direction of torsion. The recovery rate (%) is calculated by the following formula.
[0178] Recovery rate (%) = (Sufficiency A - Sufficiency B) / Sufficiency A × 100
[0179] From the viewpoints of the adhesive layer being able to adequately follow the shrinkage or expansion of the image display device under the usage environment, suppressing bulging or peeling, and maintaining unchanged transparency, a recovery rate of 95% or less for the adhesive layer of the present invention is preferred. Furthermore, from the viewpoints of the adhesive layer adequately following the height difference caused by wiring or the like on the adhered object such as the image display panel, and filling without leaving air bubbles, a recovery rate of 95% or less for the adhesive layer of the present invention is also preferred. From the viewpoints of suppressing bulging or peeling of the optical adhesive tape of the present invention, maintaining unchanged transparency, and following height differences, a recovery rate of 94% or less for the adhesive layer of the present invention is preferably 94%, and may also be 93.5% or less. There is no particular limitation on the lower limit of the recovery rate of the adhesive layer of the present invention; from the viewpoints of minimizing defects such as adhesive layer protrusion from the ends when storing the optical adhesive tape of the present invention, a recovery rate of 70% or more is preferred, and may also be 80% or more or 85% or more.
[0180] There is no particular limitation on the strain A of the adhesive layer of the present invention, but it is preferably 3% or more. From the viewpoint that the adhesive layer can adequately follow the shrinkage or expansion of the image display device under the usage environment and can suppress bulging or peeling, a strain A of 3% or more in the adhesive layer of the present invention is preferred. Furthermore, from the viewpoint that when there is a difference in the shape of unevenness caused by wiring or the like on the adhered object such as the image display panel, a strain A of 3% or more in the adhesive layer can adequately follow this difference and fill it without leaving air bubbles, etc., is also preferred. From the viewpoint that it can suppress bulging or peeling of the optical adhesive tape of the present invention and follow the difference in shape, the strain A of the adhesive layer of the present invention is preferably 4% or more, and may also be 5% or more. There is no particular limitation on the upper limit of the strain A of the present invention, but from the viewpoint that it is less likely to cause defects such as the adhesive layer protruding from the end when storing the optical adhesive tape of the present invention, and that transparency remains unchanged, it is preferably 25% or less, and may also be 20% or less or 15% or less.
[0181] There is no particular limitation on the strain B of the adhesive layer of the present invention, but it is preferably 0.1% or more. From the viewpoint that the adhesive layer adequately follows the shrinkage or expansion of the image display device under the usage environment and can suppress bulging or peeling, a strain B of 0.1% or more in the adhesive layer of the present invention is preferred. Furthermore, from the viewpoint that when there is a height difference in the shape of unevenness caused by wiring or the like on the adhered object such as the image display panel, and the adhesive layer adequately follows this height difference and can fill it without leaving air bubbles, a strain B of 0.1% or more in the adhesive layer of the present invention is also preferred. From the viewpoint that it suppresses bulging or peeling of the optical adhesive tape of the present invention and can follow the height difference, the strain B of the adhesive layer of the present invention is preferably 0.2% or more, and may also be 0.3% or more. There is no particular limitation on the upper limit of the strain B of the present invention. From the viewpoint that it is less likely to cause defects such as the adhesive layer protruding from the end when storing the optical adhesive tape of the present invention, and that transparency remains unchanged, the upper limit of the strain B of the present invention is preferably 10% or less, and may also be 8% or less or 5% or less.
[0182] The strain A, strain B, and recovery rate of the adhesive layer of the present invention were determined by shear tests in the examples described later. The strain A, strain B, and recovery rate of the present invention can be adjusted by the composition of the adhesive composition used to form the adhesive layer of the present invention (e.g., the type or molecular weight of the base polymer, the amount used, the monomer composition, the type and amount of functional groups, the type and amount of crosslinking agent), curing conditions (heating conditions, radiation irradiation conditions), etc.
[0183] The glass transition temperature (Tg) of the adhesive layer of the present invention is preferably -10°C or lower. From the viewpoints of maintaining the stress relaxation properties of the adhesive layer even at low temperatures, ensuring the adhesive layer adequately adapts to the shrinkage or expansion of the image display device under usage conditions, suppressing bulging or peeling, and adequately ensuring adhesion to the adhered object, a Tg of -10°C or lower for the adhesive layer of the present invention is preferred. From the viewpoints of suppressing bulging or peeling in the image display device of the present invention and good adhesion to the adhered object, the glass transition temperature of the adhesive layer of the present invention is preferably -15°C or lower, and may also be -20°C or lower. There is no particular limitation on the lower limit of the Tg of the adhesive layer of the present invention; however, from the viewpoints of minimizing defects such as adhesive layer protrusion from the ends when storing the optical adhesive tape of the present invention, a Tg of -50°C or higher is preferred, and may also be -40°C or higher.
[0184] The glass transition temperature (Tg) of the adhesive layer of the present invention was determined by dynamic viscoelasticity measurement in the examples described later. The glass transition temperature (Tg) of the adhesive layer of the present invention can be adjusted by the composition of the adhesive composition used to form the adhesive layer of the present invention (e.g., the type or molecular weight of the base polymer, the amount used, the monomer composition, the type and amount of functional groups, the type and amount of crosslinking agent), curing conditions (heating conditions, radiation irradiation conditions), etc.
[0185] There is no particular limitation on the storage modulus of the adhesive layer of the present invention at 70°C and 1Hz, but it is preferably 80 kPa or less. From the viewpoint that the adhesive layer of the present invention can adequately follow the shrinkage or expansion of the image display device under the usage environment and can suppress bulging or peeling, a configuration in which the storage modulus of the adhesive layer of the present invention at 70°C and 1Hz is 80 kPa or less is preferred. Furthermore, from the viewpoint that when there is a height difference in the shape of unevenness caused by wiring or the like on the adhered object such as the image display panel, and the adhesive layer adequately follows this height difference and can fill it without leaving air bubbles, a configuration in which the storage modulus of the adhesive layer of the present invention at 70°C and 1Hz is 80 kPa or less is also preferred. From the viewpoint of suppressing bulging or peeling of the optical adhesive tape of the present invention and being able to follow height differences, a storage modulus of the adhesive layer of the present invention at 70°C and 1Hz is more preferably 70 kPa or less, but may also be 60 kPa or less or 50 kPa or less. There is no particular limitation on the lower limit of the energy storage modulus of the adhesive layer of the present invention at 70°C and 1Hz. From the viewpoint of processability, such as preventing the adhesive layer from protruding from the end when storing the optical adhesive tape of the present invention, it is preferred to be 1 kPa or more, and it may also be 5 kPa or more.
[0186] There is no particular limitation on the loss tangent of the adhesive layer of the present invention at 70°C and 1Hz, but it is preferably 0.15 or higher. From the viewpoint that the adhesive layer of the present invention fully follows the shrinkage or expansion of the image display device under the usage environment and can suppress bulging or peeling, the configuration of the adhesive layer of the present invention having a loss tangent of 0.15 or higher at 70°C and 1Hz is preferred. Furthermore, from the viewpoint that when there is a height difference in the shape of unevenness caused by wiring or the like on the adhered object such as the image display panel, the adhesive layer fully follows this height difference and can fill it without leaving air bubbles, the configuration of the adhesive layer of the present invention having a loss tangent of 0.15 or higher at 70°C and 1Hz is also preferred. From the viewpoint of suppressing bulging or peeling of the optical adhesive tape of the present invention and being able to follow the height difference, the loss tangent of the adhesive layer of the present invention at 70°C and 1Hz is preferably 0.2 or higher, but may also be 0.25 or higher or 0.3 or higher. There is no particular limitation on the upper limit of the loss tangent of the adhesive layer at 70°C and 1Hz. From the viewpoint of processability, such as preventing the adhesive layer from protruding from the end when storing the optical adhesive tape of the present invention, it is preferred to be 1 or less, and it may also be 0.8 or less.
[0187] The storage modulus at 70°C and 1Hz, and the loss tangent of the adhesive layer of the present invention were measured by dynamic viscoelasticity measurements in the examples described later. The storage modulus at 70°C and 1Hz, and the loss tangent of the adhesive layer of the present invention can be adjusted by the composition of the adhesive composition used to form the adhesive layer of the present invention (e.g., the type or molecular weight of the base polymer, the amount used, the monomer composition, the type and amount of functional groups, the type and amount of crosslinking agent), curing conditions (heating conditions, radiation irradiation conditions), etc.
[0188] For the 1cm of the adhesive layer of the present invention 2 The shear force when the adhesive area is bonded to the resin board and pulled along the shear direction at a pulling speed of 0.06 mm / min at 23°C is not particularly limited, but is preferably 20 N / cm. 2 Below. In this specification, when referring to "shear force," unless otherwise stated, it means "within 1 cm of the adhesive layer." 2 The shear force when the adhesive area is bonded to the resin board and pulled along the shear direction at a pulling speed of 0.06 mm / min at 23°C.
[0189] From the viewpoint that the adhesive layer of the present invention can fully adapt to the shrinkage or expansion of the image display device under the usage environment and can suppress bulging or peeling, the shear force of the adhesive layer of the present invention is 20 N / cm. 2The following configuration is preferred. Furthermore, considering the situation where there are height differences in the surface of the adherend, such as an image display panel, caused by wiring, etc., and the adhesive layer sufficiently follows these height differences to fill them without leaving air bubbles, the shear force of the adhesive layer of the present invention is 20 N / cm. 2 The following configuration is also preferred. From the viewpoint of suppressing bulging or peeling of the optical adhesive tape of the present invention and being able to follow height differences, the shear force of the adhesive layer of the present invention is more preferably 15 N / cm. 2 The following can also be 13 N / cm 2 The following is a description of the lower limit of the shear force of the adhesive layer in this invention. From the viewpoint of minimizing defects such as adhesive layer protrusion from the ends when storing the optical adhesive tape of this invention, a value of 5 N / cm is preferred. 2 The above can also be 7 N / cm. 2 above.
[0190] The shear force of the adhesive layer of the present invention was measured by shear force measurement in the examples described later. The shear force of the adhesive layer of the present invention can be adjusted by the composition of the adhesive composition used to form the adhesive layer of the present invention (e.g., the type or molecular weight of the base polymer, the amount used, the monomer composition, the type and amount of functional groups, the type and amount of crosslinking agent), curing conditions (heating conditions, radiation irradiation conditions), etc.
[0191] There is no particular limitation on the 300% tensile residual stress value of the adhesive layer of the present invention, but it is preferably 10 N / cm. 2 From the viewpoint that the adhesive layer of the present invention can adequately adapt to the shrinkage or expansion of the image display device under the usage environment and can suppress bulging or peeling, the 300% tensile residual stress value of the adhesive layer of the present invention is 10 N / cm. 2 The following configuration is preferred. Furthermore, from the viewpoint that when there are height differences in the shape of uneven surfaces caused by wiring or the like on the adhered object such as an image display panel, the adhesive layer can adequately follow these height differences and fill them without leaving air bubbles, the 300% tensile residual stress value of the adhesive layer of the present invention is 10 N / cm. 2 The following configuration is also preferred. From the viewpoint of suppressing bulging or peeling of the optical adhesive tape of the present invention and being able to follow height differences, the 300% tensile residual stress value of the adhesive layer of the present invention is more preferably 7 N / cm. 2 The following can also be 5 N / cm 2 The following is not a particular limitation on the lower limit of the 300% tensile residual stress value of the adhesive layer of the present invention. However, from the viewpoint of processability, such as preventing the adhesive layer from protruding from the end when storing the optical adhesive tape of the present invention, a value of 1 N / cm is preferred.2 The above can also be 1.5 N / cm. 2 above.
[0192] The 300% tensile residual stress value of the adhesive layer of the present invention was determined by measuring the 300% tensile residual stress value in the examples described later. The 300% tensile residual stress value of the adhesive layer of the present invention can be adjusted by the composition of the adhesive composition used to form the adhesive layer of the present invention (e.g., the type or molecular weight of the base polymer, the amount used, the monomer composition, the type and amount of functional groups, the type and amount of crosslinking agent), curing conditions (heating conditions, radiation irradiation conditions), etc.
[0193] There are no particular limitations on the adhesives constituting the adhesive layer of the present invention, and examples include: acrylic adhesives, rubber adhesives, vinyl alkyl ether adhesives, silicone adhesives, polyester adhesives, polyamide adhesives, urethane adhesives, fluorinated adhesives, epoxy adhesives, etc. Among these, acrylic adhesives are preferred from the viewpoints of transparency, adhesion, weather resistance, cost, and ease of adhesive design. That is, the adhesive layer of the present invention is preferably an acrylic adhesive layer composed of an acrylic adhesive. The above-mentioned adhesives can be used alone or in combination of two or more.
[0194] The aforementioned acrylic adhesive layer contains an acrylic polymer as its base polymer. This acrylic polymer is a polymer that includes acrylic monomers (monomers having a (meth)acryloyl group in the molecule) as monomeric components of the polymer. Preferably, the acrylic polymer includes alkyl (meth)acrylates as monomeric components of the polymer. It should be noted that two or more acrylic polymers can be used alone or in combination.
[0195] The adhesive composition forming the adhesive layer of the present invention can be in any form. For example, the adhesive composition can be an emulsion type, a solvent type (solution type), an active energy radiation curable type, a heat-melt type (hot melt type), etc. Among these, solvent-based and active energy radiation curable adhesive compositions are preferred from the viewpoint of productivity, ease of obtaining an adhesive layer with excellent optical properties and appearance. In particular, active energy radiation curable adhesive compositions are preferred from the viewpoint of easily controlling the various properties of the adhesive layer (especially strain A, strain B, recovery rate, glass transition temperature, etc.) within a specified range.
[0196] That is, the adhesive layer of the present invention is preferably an acrylic adhesive layer containing an acrylic polymer as the base polymer, and is formed by an acrylic adhesive composition that is cured by active energy radiation.
[0197] Examples of such active energy rays include ionizing radiation such as alpha rays, beta rays, gamma rays, neutron rays, and electron rays; and ultraviolet rays, with ultraviolet rays being particularly preferred. That is, the adhesive composition cured by the aforementioned active energy rays is preferably an ultraviolet-cured adhesive composition.
[0198] Examples of adhesive compositions (acrylic adhesive compositions) forming the aforementioned acrylic adhesive layer include, for example, acrylic adhesive compositions that use an acrylic polymer as an essential component; or acrylic adhesive compositions that use a mixture of monomers constituting the acrylic polymer (sometimes referred to as a "monomer mixture") or a portion thereof as essential components. For the former, examples include solvent-based acrylic adhesive compositions. For the latter, examples include active energy radiation-cured acrylic adhesive compositions. The term "monomer mixture" refers to a mixture containing monomer components constituting the polymer. Furthermore, the term "partial polymer," sometimes also called a "prepolymer," refers to a composition in which one or more monomer components in the monomer mixture have partially polymerized.
[0199] The aforementioned acrylic polymers are polymers constructed (formed) by using acrylic monomers as essential monomer components. Preferably, the aforementioned acrylic polymers are polymers constructed (formed) by using alkyl (meth)acrylates as essential monomer components. That is, the aforementioned acrylic polymers preferably contain alkyl (meth)acrylates as structural units. In this specification, "(meth)acrylate" refers to "acrylic acid" and / or "methacrylic acid" (either or both of "acrylic acid" and "methacrylic acid"), and so on. It should be noted that the aforementioned acrylic polymers are composed of one or more monomer components.
[0200] The aforementioned alkyl (meth)acrylates, which are essential monomeric components, are preferably alkyl (meth)acrylates having straight-chain or branched alkyl groups. It should be noted that alkyl (meth)acrylates can be used alone or in combination of two or more.
[0201] There are no particular limitations on alkyl (meth)acrylates having straight or branched alkyl groups, and examples include: methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, and so on. Isononyl acrylate, decyl acrylate, isodecyl acrylate, undecyl acrylate, dodecyl acrylate, tridecyl acrylate, tetradecyl acrylate, pentadecyl acrylate, hexadecyl acrylate, heptadecanyl acrylate, octadecyl acrylate (stearyl acrylate), isostearyl acrylate, nonadecanyl acrylate, eicosyl acrylate, etc., are alkyl methacrylates having a straight-chain or branched alkyl group with 1 to 20 carbon atoms. Preferably, these alkyl methacrylates have a straight-chain or branched alkyl group with 4 to 18 carbon atoms; more preferably, they are 2-ethylhexyl acrylate (2EHA), isostearyl acrylate (ISTA), lauryl acrylate (LA), or butyl acrylate (BA). In addition, the above-mentioned alkyl (meth)acrylates having straight or branched alkyl groups can be used alone or in combination of two or more.
[0202] In all monomer components (100 wt%) constituting the above-mentioned acrylic polymer, the ratio of the above-mentioned alkyl methacrylate is not particularly limited, but is preferably 50 wt% or more (e.g., 50 wt% to 100 wt%), more preferably 53 wt% to 90 wt%, and even more preferably 55 wt% to 85 wt%.
[0203] In addition to the acrylic polymer described above, the acrylic adhesive composition may also contain the alkyl (meth)acrylate described above. When the acrylic adhesive composition contains alkyl (meth)acrylate in addition to the acrylic polymer, the content (compounding amount) of the alkyl (meth)acrylate relative to 100 parts by weight of the acrylic polymer is preferably 10 parts by weight or more (e.g., 10 to 100 parts by weight), more preferably 20 to 90 parts by weight, and even more preferably 30 to 80 parts by weight.
[0204] The aforementioned acrylic polymers may contain copolymerizable monomers as constituent monomers in addition to the aforementioned alkyl (meth)acrylates. That is, the aforementioned acrylic polymers may contain copolymerizable monomers as structural units. It should be noted that two or more copolymerizable monomers may be used alone or in combination.
[0205] As for the aforementioned copolymerizable monomers, there are no particular limitations. From the viewpoint of easily controlling the various properties of the adhesive layer (especially strain A, strain B, recovery rate, glass transition temperature, etc.) within a specified range, suppressing whitening and clouding under high humidity environments, and improving durability, adhesive reliability, compatibility with various additives such as UV absorbers, and transparency, monomers having nitrogen atoms in their molecules and monomers having hydroxyl groups in their molecules are preferred. That is, the aforementioned acrylic polymers preferably contain monomers having nitrogen atoms in their molecules as structural units. Furthermore, the aforementioned acrylic polymers preferably contain monomers having hydroxyl groups in their molecules as structural units.
[0206] The monomers described above that have nitrogen atoms within a molecule are monomers (monomers) that have at least one nitrogen atom within a molecule. In this specification, the term "monomers having nitrogen atoms within a molecule" is sometimes used as "monomers containing nitrogen atoms." There are no particular limitations on the types of monomers containing nitrogen atoms, but preferred examples include cyclic nitrogen-containing monomers and (meth)acrylamides. It should be noted that two or more monomers containing nitrogen atoms can be used alone or in combination.
[0207] There are no particular limitations on the aforementioned cyclic nitrogen-containing monomers, as long as they are monomers with polymerizable functional groups such as (meth)acryloyl or vinyl groups that have unsaturated double bonds and have a cyclic nitrogen structure. Preferably, the aforementioned cyclic nitrogen structure contains nitrogen atoms within the cyclic structure.
[0208] Examples of the aforementioned cyclic nitrogen-containing monomers include: N-vinyl cyclic amides (lactam vinyl monomers), vinyl monomers having nitrogen-containing heterocycles, etc.
[0209] As an example of the above-mentioned N-vinyl cyclic amide, an N-vinyl cyclic amide represented by the following formula (1) can be listed.
[0210]
[0211] (In equation (1), R) 1 (representing a divalent organic group)
[0212] R in equation (1) above 1 It is a divalent organic group, preferably a divalent saturated hydrocarbon group or an unsaturated hydrocarbon group, more preferably a divalent saturated hydrocarbon group (e.g., an alkylene group with 3 to 5 carbon atoms).
[0213] Examples of N-vinylcyclic amides represented by the above formula (1) include: N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-azin-2-one, N-vinyl-3,5-morpholindione, etc.
[0214] Examples of vinyl monomers having nitrogen-containing heterocycles include acrylic monomers having nitrogen-containing heterocycles such as morpholine rings, piperidine rings, pyrrolidine rings, and piperazine rings.
[0215] There are no particular limitations on the vinyl monomers with nitrogen-containing heterocycles mentioned above. Examples include: (meth)acryloylmorpholine, N-vinylpiperazine, N-vinylpyrrole, N-vinylimidazol, N-vinylpyrazine, N-vinylmorpholine, N-vinylpyrazole, vinylpyridine, vinylpyrimidine, vinylazole, vinylisoazole, vinylthiazole, vinylisothiazole, vinylpyridazine, (meth)acryloylpyrrolidone, (meth)acryloylpyrrolidine, (meth)acryloylpiperidine, etc.
[0216] Among the above-mentioned vinyl monomers having nitrogen-containing heterocycles, acrylic monomers having nitrogen-containing heterocycles are preferred, and (meth)acryloylmorpholine, (meth)acryloylpyrrolidine, and (meth)acryloylpiperidine are more preferred.
[0217] Examples of the aforementioned (meth)acrylamides include: (meth)acrylamide, N-alkyl (meth)acrylamide, and N,N-dialkyl (meth)acrylamide. Examples of the aforementioned N-alkyl (meth)acrylamides include: N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-n-butyl (meth)acrylamide, and N-octyl (meth)acrylamide. Furthermore, the aforementioned N-alkyl (meth)acrylamides also include (meth)acrylamides containing an amino group, such as dimethylaminoethyl (meth)acrylamide, diethylaminoethyl (meth)acrylamide, and dimethylaminopropyl (meth)acrylamide. Examples of N,N-dialkyl(methyl)acrylamides include: N,N-dimethyl(methyl)acrylamide, N,N-diethyl(methyl)acrylamide, N,N-dipropyl(methyl)acrylamide, N,N-diisopropyl(methyl)acrylamide, N,N-di-n-butyl(methyl)acrylamide, N,N-di-tert-butyl(methyl)acrylamide, etc.
[0218] Furthermore, the aforementioned (meth)acrylamide class also includes various N-hydroxyalkyl (meth)acrylamides. Examples of such N-hydroxyalkyl (meth)acrylamides include: N-hydroxymethyl (meth)acrylamide, N-(2-hydroxyethyl) (meth)acrylamide, N-(2-hydroxypropyl) (meth)acrylamide, N-(1-hydroxypropyl) (meth)acrylamide, N-(3-hydroxypropyl) (meth)acrylamide, N-(2-hydroxybutyl) (meth)acrylamide, N-(3-hydroxybutyl) (meth)acrylamide, N-(4-hydroxybutyl) (meth)acrylamide, and N-methyl-N-(2-hydroxyethyl) (meth)acrylamide.
[0219] Furthermore, the aforementioned (meth)acrylamide class also includes various N-alkoxyalkyl (meth)acrylamides. Examples of such N-alkoxyalkyl (meth)acrylamides include N-methoxymethyl (meth)acrylamide and N-butoxymethyl (meth)acrylamide.
[0220] In addition, examples of nitrogen-containing monomers other than the aforementioned cyclic nitrogen-containing monomers and (meth)acrylamides include: monomers containing amino groups, monomers containing cyano groups, monomers containing imide groups, and monomers containing isocyanate groups. Examples of amino-containing monomers include: aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate. Examples of cyano-containing monomers include: acrylonitrile and methacrylonitrile. Examples of monomers containing imide groups include: maleimide monomers (e.g., N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, N-phenylmaleimide, etc.), itaconimide monomers (e.g., N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-(2-ethylhexyl)itaconimide, N-laurylitaconimide, N-cyclohexylitaconimide, etc.), and succinimide monomers (e.g., N-(meth)acryloyloxymethylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, N-(meth)acryloyl-8-oxyoctamethylene succinimide, etc.). Examples of monomers containing isocyanate groups include 2-(meth)acryloyloxyethyl isocyanate.
[0221] Among these, cyclic nitrogen-containing monomers are preferred, and N-vinylcyclic amides are more preferred. More specifically, N-vinyl-2-pyrrolidone (NVP) is particularly preferred.
[0222] When the aforementioned acrylic polymer contains the aforementioned nitrogen-containing monomer as a monomeric component of the polymer, there is no particular limitation on the proportion of the nitrogen-containing monomer in the total monomeric component (100% by weight) constituting the aforementioned acrylic polymer. Preferably, it is 1% by weight or more, more preferably 3% by weight or more, and even more preferably 5% by weight or more. When the proportion of the nitrogen-containing monomer is 1% by weight or more, the suppression of white turbidity and durability under high humidity conditions are further improved, resulting in high adhesive reliability, which is preferable. Furthermore, from the viewpoints of obtaining an adhesive layer with moderate flexibility, obtaining an adhesive layer with excellent transparency, and easily controlling the aforementioned properties of the adhesive layer (especially strain A, strain B, recovery rate, glass transition temperature, etc.) within a specified range, the upper limit of the proportion of the nitrogen-containing monomer is preferably 30% by weight or less, more preferably 25% by weight or less, and even more preferably 20% by weight or less.
[0223] The monomers described above that have an intramolecular hydroxyl group are monomers that have at least one hydroxyl (hydroxyl group) within a molecule. Preferably, monomers having polymerizable functional groups with unsaturated double bonds, such as (meth)acryloyl or vinyl groups, and possessing a hydroxyl group are included. However, the monomers containing nitrogen atoms are not included in the list of monomers with an intramolecular hydroxyl group. That is, in this specification, monomers that simultaneously possess both a nitrogen atom and a hydroxyl group within a molecule are included in the category of "monomers containing nitrogen atoms." In this specification, the term "monomers with an intramolecular hydroxyl group" is sometimes used as "hydroxyl-containing monomers." It should be noted that hydroxyl-containing monomers can be used alone or in combination of two or more.
[0224] Examples of hydroxyl-containing monomers include: 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, 6-hydroxyhexyl methacrylate, hydroxyoctyl methacrylate, hydroxydecyl methacrylate, hydroxylauryl methacrylate, and (4-hydroxymethylcyclohexyl) methacrylate; vinyl alcohol; allyl alcohol, etc.
[0225] Among them, hydroxyl-containing monomers are preferred (meth)acrylates, and more preferably 2-hydroxyethyl acrylate (HEA) and 4-hydroxybutyl acrylate (4HBA).
[0226] When the aforementioned acrylic polymer contains the aforementioned hydroxyl-containing monomer as a monomeric component of the polymer, there is no particular limitation on the ratio of the aforementioned hydroxyl-containing monomer in the total monomeric components (100% by weight) constituting the aforementioned acrylic polymer. From the viewpoint of suppressing whitening and turbidity under high humidity environments and improving durability and adhesive reliability, the ratio of the aforementioned hydroxyl-containing monomer is preferably 0.5% by weight or more, more preferably 0.8% by weight or more, and even more preferably 1% by weight or more. In addition, from the viewpoint of easily controlling the aforementioned various properties of the adhesive layer (especially strain A, strain B, recovery rate, glass transition temperature, etc.) within a specified range, the upper limit of the ratio of the aforementioned hydroxyl-containing monomer is preferably 30% by weight or less, more preferably 25% by weight or less, and even more preferably 20% by weight or less.
[0227] Furthermore, to further enhance the aforementioned effects brought about by the hydroxyl-containing monomer, the acrylic adhesive composition may contain a hydroxyl-containing monomer in addition to the aforementioned acrylic polymer. When the acrylic adhesive composition contains a hydroxyl-containing monomer in addition to the acrylic polymer, the content (addition amount) of the hydroxyl-containing monomer relative to 100 parts by weight of the acrylic polymer is preferably 1 part by weight or more, more preferably 3 parts by weight or more, and even more preferably 5 parts by weight or more. When the content of the hydroxyl-containing monomer is 5 parts by weight or more, the suppression of whitening and turbidity under high humidity conditions and the improved durability are further enhanced, resulting in higher adhesive reliability, which is preferable. Furthermore, from the viewpoints of cohesion, ease of obtaining adhesiveness and adhesive reliability, and ease of controlling the aforementioned properties of the adhesive layer (especially strain A, strain B, recovery rate, glass transition temperature, etc.) within a specified range, the upper limit of the content (addition amount) of the hydroxyl-containing monomer is preferably 30 parts by weight or less, more preferably 25 parts by weight or less, even more preferably 20 parts by weight or less, and particularly preferably 17 parts by weight or less.
[0228] There is no particular limitation on the total ratio of the nitrogen-containing monomers and the hydroxyl-containing monomers in all monomer components (100% by weight) constituting the above-mentioned acrylic polymers. From the viewpoint of suppressing white turbidity in high humidity environments, improving durability, and obtaining high adhesive reliability, it is preferably 5% by weight or more, more preferably 10% by weight or more, and even more preferably 15% by weight or more. In addition, from the viewpoint of obtaining an adhesive layer with moderate flexibility, obtaining an adhesive layer with excellent transparency, and easily controlling the above-mentioned various properties of the adhesive layer (especially strain A, strain B, recovery rate, glass transition temperature, etc.) within a specified range, the upper limit of the total ratio is preferably 50% by weight or less, more preferably 40% by weight or less, and even more preferably 35% by weight or less.
[0229] Besides monomers containing nitrogen atoms and monomers containing hydroxyl groups, monomers with alicyclic structures can also be listed as copolymerizable monomers. There are no particular limitations on the aforementioned monomers with alicyclic structures, as long as they have polymerizable functional groups with unsaturated double bonds, such as (meth)acryloyl or vinyl groups. For example, alkyl (meth)acrylates with cycloalkyl groups are included among the aforementioned monomers with alicyclic structures. It should be noted that monomers with alicyclic structures can be used alone or in combination of two or more.
[0230] The alicyclic structure in the above-mentioned monomers containing alicyclic structures is a cyclic hydrocarbon structure, preferably having 5 or more carbon atoms, more preferably having 6 to 24 carbon atoms, even more preferably having 6 to 15 carbon atoms, and particularly preferably having 6 to 10 carbon atoms.
[0231] Examples of monomers containing alicyclic structures include: cyclopropyl methacrylate, cyclobutyl methacrylate, cyclopentyl methacrylate, cyclohexyl methacrylate, cycloheptyl methacrylate, cyclooctyl methacrylate, isobornyl methacrylate, tetrahydrodicyclopentadienyl methacrylate, HPMPA (represented by formula (2), TMA-2 (represented by formula (3), and HCPA (represented by formula (4)). It should be noted that in formula (4), there are no particular restrictions on the bonding sites between the cyclohexyl ring connected by a line and the structural formula within parentheses. Among these, cyclohexyl methacrylate and isobornyl methacrylate are preferred.
[0232]
[0233] When the aforementioned acrylic polymer contains monomers with alicyclic structures as monomeric components constituting the polymer, there is no particular limitation on the proportion of the alicyclic monomers in the total monomeric components (100% by weight) constituting the acrylic polymer. However, from the viewpoint of improving durability and obtaining high adhesive reliability, a proportion of 10% by weight or more is preferred. Furthermore, from the viewpoint of obtaining an adhesive layer with moderate flexibility and easily controlling the various properties of the adhesive layer (especially strain A, strain B, recovery rate, glass transition temperature, etc.) within a specified range, the upper limit of the proportion of the alicyclic monomers is preferably 50% by weight or less, more preferably 40% by weight or less, and even more preferably 30% by weight or less.
[0234] In addition, examples of copolymerizable monomers include, for example, multifunctional monomers. Examples of such multifunctional monomers include: hexanediol di(meth)acrylate, butanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl methacrylate, vinyl methacrylate, divinylbenzene, epoxy acrylates, polyester acrylates, and urethane acrylates. It should be noted that multifunctional monomers can be used alone or in combination of two or more.
[0235] When the aforementioned acrylic polymer contains the aforementioned polyfunctional monomers as monomeric components constituting the polymer, there is no particular limitation on the ratio of the aforementioned polyfunctional monomers in all monomeric components (100% by weight) constituting the aforementioned acrylic polymer. From the viewpoint of easily controlling the aforementioned various properties of the adhesive layer (especially strain A, strain B, recovery rate, glass transition temperature, etc.) within a specified range, it is preferable to be 0.5% by weight or less (e.g., greater than 0% by weight and less than or equal to 0.5% by weight), and more preferably 0.2% by weight or less (e.g., greater than 0% by weight and less than or equal to 0.2% by weight).
[0236] In addition to being incorporated into the aforementioned acrylic polymers, the aforementioned multifunctional monomers can also be incorporated into acrylic adhesive compositions. When the acrylic adhesive composition contains both an acrylic polymer and a multifunctional monomer, from the viewpoint of easily controlling the various properties of the adhesive layer (especially strain A, strain B, recovery rate, glass transition temperature, etc.) within a specified range, the content (incorporation amount) of the multifunctional monomer relative to 100 parts by weight of the acrylic polymer is preferably 0.5 parts by weight or less (e.g., greater than 0 parts by weight and less than or equal to 0.5 parts by weight), more preferably 0.2 parts by weight or less (e.g., greater than 0 parts by weight and less than or equal to 0.2 parts by weight).
[0237] Furthermore, alkoxyalkyl esters of (meth)acrylate can be listed as copolymerizable monomers. There are no particular limitations on the alkoxyalkyl esters of (meth)acrylate, and examples include: 2-methoxyethyl methacrylate, 2-ethoxyethyl methacrylate, methoxytriethylene glycol methacrylate, 3-methoxypropyl methacrylate, 3-ethoxypropyl methacrylate, 4-methoxybutyl methacrylate, and 4-ethoxybutyl methacrylate. Preferably, the alkoxyalkyl esters of (meth)acrylate are alkoxyalkyl acrylates, and more preferably, 2-methoxyethyl acrylate (MEA). It should be noted that two or more of the above-mentioned alkoxyalkyl esters of (meth)acrylate can be used alone or in combination.
[0238] When the above-mentioned acrylic polymer contains the above-mentioned (meth)acrylate alkoxyalkyl ester as a monomer component constituting the polymer, there is no particular limitation on the ratio of the above-mentioned (meth)acrylate alkoxyalkyl ester to the above-mentioned (meth)acrylate alkoxyalkyl ester. In terms of [former:rear] (weight ratio), it is preferably greater than 100:0 and less than or equal to 25:75, more preferably greater than 100:0 and less than or equal to 50:50.
[0239] Furthermore, examples of the aforementioned copolymerizable monomers include: monomers containing carboxyl groups, monomers containing epoxy groups, monomers containing sulfonic acid groups, monomers containing phosphoric acid groups, (meth)acrylates with aromatic hydrocarbon groups, vinyl esters, aromatic vinyl compounds, olefins or dienes, vinyl ethers, vinyl chloride, etc. Examples of the aforementioned carboxyl-containing monomers include: (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, etc. Additionally, among the aforementioned carboxyl-containing monomers are, for example, maleic anhydride, itaconic anhydride, and other monomers containing anhydride groups. Examples of the aforementioned epoxy-containing monomers include: (meth)acrylate glycidyl ester, (meth)acrylate methyl glycidyl ester, etc. Examples of the aforementioned sulfonic acid-containing monomers include: sodium vinyl sulfonate, etc. Examples of the aforementioned phosphoric acid-containing monomers include: 2-hydroxyethylacryloyl phosphate, etc. Examples of (meth)acrylates having aromatic hydrocarbon groups include phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, and benzyl (meth)acrylate. Examples of vinyl esters include vinyl acetate and vinyl propionate. Examples of aromatic vinyl compounds include styrene and vinyltoluene. Examples of olefins or dienes include ethylene, propylene, butadiene, isoprene, and isobutylene. Examples of vinyl ethers include vinyl alkyl ethers.
[0240] From the viewpoint of obtaining an acrylic adhesive layer with excellent corrosion resistance, the aforementioned acrylic polymer preferably contains monomers that do not contain or substantially do not contain acidic groups as monomer components constituting the polymer, and particularly preferably contains monomers that do not contain or substantially do not contain carboxyl groups. Examples of monomers containing acidic groups include, for example, monomers containing carboxyl groups, monomers containing sulfonic acid groups, and monomers containing phosphate groups. Specifically, when the proportion of monomers containing acidic groups in the total monomer components (100% by weight) constituting the aforementioned acrylic polymer is 0.05% by weight or less (preferably 0.01% by weight or less), it can be considered that the monomers substantially do not contain acidic groups.
[0241] There is no particular limitation on the content of the base polymer (especially acrylic polymer) in the adhesive layer of the present invention. It is preferably 50% by weight or more (e.g., 50% to 100% by weight) relative to the total weight of 100% by weight of the adhesive layer of the present invention, more preferably 80% by weight or more (e.g., 80% to 100% by weight), and even more preferably 90% by weight or more (e.g., 90% to 100% by weight).
[0242] The weight-average molecular weight (Mw) of the aforementioned acrylic polymers is 100,000 to 5,000,000, preferably 500,000 to 4,000,000, and more preferably 750,000 to 3,000,000. From the viewpoint of improving adhesion and foaming peel resistance, a composition with a weight-average molecular weight of 100,000 or more of the acrylic polymer is preferred. On the other hand, from the viewpoint of easily improving adhesion and foaming peel resistance, a composition with a weight-average molecular weight of 5,000,000 or less of the acrylic polymer is preferred.
[0243] The weight-average molecular weight (Mw) of the aforementioned acrylic polymers can be determined by GPC and polystyrene conversion. For example, it can be determined using a high-speed GPC apparatus, HPLC-8120GPC, manufactured by Tosoh Corporation, under the following conditions.
[0244] Column: TSKgel Super HZM-H / HZ4000 / HZ3000 / HZ2000
[0245] Solvent: Tetrahydrofuran
[0246] Flow rate: 0.6 ml / min
[0247] There is no particular limitation on the glass transition temperature (Tg) of the aforementioned acrylic polymers, but it is preferably -70°C to -10°C, more preferably -65°C to -15°C, and even more preferably -60°C to -20°C. When the glass transition temperature of the acrylic polymer is -70°C or higher, the cohesive strength is improved, and the foaming peel resistance is easily improved, which is preferred. In addition, from the viewpoint that the stress relaxation of the adhesive layer can be maintained even in low-temperature environments, the adhesive layer can fully follow the shrinkage or expansion of the image display device of the present invention in the usage environment, bulging or peeling can be suppressed, and adhesion to the adhered object can be sufficiently ensured, a configuration with a glass transition temperature of -10°C or lower for the acrylic polymer is preferred.
[0248] The glass transition temperature (Tg) of the above-mentioned acrylic polymers is the theoretical value expressed by the following FOX formula.
[0249] 1 / Tg = W1 / Tg1 + W2 / Tg2 + ... + W n / Tg n
[0250] In the above formula, Tg represents the glass transition temperature (unit: K) of acrylic polymers. i The glass transition temperature (in K) of monomer i when it forms a homopolymer is represented by W. i This represents the weight fraction of monomer i in the total amount of monomer components (i = 1, 2, ..., n).
[0251] The following values can be used for the Tg of the homopolymer of the monomer that constitutes the above-mentioned acrylic polymer.
[0252] 2-Ethylhexyl acrylate -70℃
[0253] hexyl acrylate -65℃
[0254] Octyl acrylate -65℃
[0255] Isononyl acrylate -60℃
[0256] nonyl acrylate -58℃
[0257] n-Butyl acrylate -55℃
[0258] Ethyl acrylate -20℃
[0259] Lauryl acrylate 0℃
[0260] 2-Ethylhexyl methacrylate -10℃
[0261] Methyl acrylate 8℃
[0262] n-Butyl methacrylate 20℃
[0263] Methyl methacrylate 105℃
[0264] Acrylic acid 106℃
[0265] Methacrylic acid 228℃
[0266] Vinyl acetate 32℃
[0267] Styrene 100℃
[0268] Furthermore, the Tg of homopolymers of monomers not described above can be taken from the values recorded in the "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989). Additionally, the Tg of homopolymers of monomers not described in the aforementioned literature can be taken from the values obtained by the aforementioned measurement methods (the peak temperature of tanδ obtained by viscoelasticity testing).
[0269] The adhesive layer of the present invention contains the aforementioned acrylic polymer or other basic polymer, which is obtained by polymerizing monomer components. There are no particular limitations on the polymerization method; examples include solution polymerization, emulsion polymerization, bulk polymerization, and polymerization using active energy rays (active energy ray polymerization). From the viewpoint of transparency and cost of the adhesive layer, solution polymerization and active energy ray polymerization are preferred, and active energy ray polymerization is more preferred.
[0270] Furthermore, various common solvents can be used during the polymerization of the aforementioned monomer components. Examples of such solvents include: esters such as ethyl acetate and n-butyl acetate; aromatic hydrocarbons such as toluene and benzene; aliphatic hydrocarbons such as n-hexane and n-heptane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; and ketones such as methyl ethyl ketone and methyl isobutyl ketone. It should be noted that two or more solvents can be used alone or in combination.
[0271] During the polymerization of the aforementioned monomer components, polymerization initiators such as thermal polymerization initiators and photopolymerization initiators (photoinitiators) can be used depending on the type of polymerization reaction. It should be noted that polymerization initiators can be used alone or in combination of two or more.
[0272] There are no particular limitations on the aforementioned thermal polymerization initiators, and examples include: azo polymerization initiators, peroxide polymerization initiators (e.g., benzoyl peroxide, tert-butyl maleate peroxide, etc.), and redox polymerization initiators. Among these, the azo polymerization initiators disclosed in Japanese Patent Application Publication No. 2002-69411 are preferred. Examples of such azo polymerization initiators include: 2,2'-azobisisobutyronitrile (hereinafter sometimes referred to as "AIBN"), 2,2'-azobis(2-methylbutyronitrile) (hereinafter sometimes referred to as "AMBN"), dimethyl 2,2'-azobis(2-methylpropionic acid), and 4,4'-azobis(4-cyanopentanoic acid). It should be noted that two or more thermal polymerization initiators can be used alone or in combination.
[0273] When the above-mentioned azo polymerization initiator is used in the polymerization of the above-mentioned acrylic polymer, there is no particular limitation on the amount of the azo polymerization initiator used. For example, relative to 100 parts by weight of all the monomer components constituting the above-mentioned acrylic polymer, the amount of the azo polymerization initiator used is preferably 0.05 parts by weight or more, more preferably 0.1 parts by weight or more, and preferably 0.5 parts by weight or less, more preferably 0.3 parts by weight or less.
[0274] There are no particular limitations on the photopolymerization initiators mentioned above. Examples include: benzoin ether photopolymerization initiators, acetophenone photopolymerization initiators, α-keto alcohol photopolymerization initiators, aromatic sulfonyl chloride photopolymerization initiators, photoactive oxime photopolymerization initiators, benzoin photopolymerization initiators, benzoyl photopolymerization initiators, benzophenone photopolymerization initiators, ketal photopolymerization initiators, and thioxanone photopolymerization initiators. Additionally, examples include: acylphosphine oxide photopolymerization initiators and titanocene photopolymerization initiators. Examples of benzoin ether photopolymerization initiators include: benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and anisoimine methyl ether. Examples of acetophenone-based photopolymerization initiators include: 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexylphenyl ketone, 4-phenoxydichloroacetophenone, and 4-tert-butyldichloroacetophenone. Examples of α-keto-alcohol-based photopolymerization initiators include: 2-methyl-2-hydroxyphenylacetone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one. Examples of aromatic sulfonyl chloride-based photopolymerization initiators include: 2-naphthalenesulfonyl chloride. Examples of photoactive oxime-based photopolymerization initiators include: 1-phenyl-1,1-propanedione-2-(O-ethoxycarbonyl)oxime. Examples of benzoin-based photopolymerization initiators include: benzoin. Examples of benzoinyl-based photopolymerization initiators include: benzoinyl. Examples of benzophenone-based photopolymerization initiators include: benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenyl ketone, etc. Examples of ketal-based photopolymerization initiators include: benzoyladium dimethyl ketal, etc. Examples of thioxanthone-based photopolymerization initiators include: thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, dodecylthioxanthone, etc. Examples of phosphine oxide-based photopolymerization initiators include: 2,4,6-trimethylbenzoyl diphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, etc. Examples of titanocene-based photopolymerization initiators include: bis(η- 5 -2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrolo-1-yl)-phenyl)titanium, etc. It should be noted that photopolymerization initiators can be used alone or in combination of two or more.
[0275] When the above-mentioned photopolymerization initiator is used in the polymerization of the above-mentioned acrylic polymer, there is no particular limitation on the amount of the photopolymerization initiator used. For example, relative to 100 parts by weight of all the monomer components constituting the above-mentioned acrylic polymer, the amount of the photopolymerization initiator used is preferably 0.01 parts by weight or more, more preferably 0.1 parts by weight or more, and preferably 3 parts by weight or less, more preferably 1.5 parts by weight or less.
[0276] The aforementioned acrylic adhesive composition preferably contains an acrylic oligomer with a weight-average molecular weight of 1,000 to 30,000 in addition to the aforementioned acrylic polymer. When the acrylic oligomer is included, the adhesiveness of the optical adhesive tape at the interface to the adhered object is improved, thus easily obtaining strong adhesion. Furthermore, excellent resistance to foaming and peeling is readily achieved. It should be noted that in this specification, "acrylic oligomer with a weight-average molecular weight of 1,000 to 30,000" is sometimes simply referred to as "acrylic oligomer".
[0277] As the aforementioned acrylic oligomers, acrylic polymers comprising (meth)acrylates having an intramolecular cyclic structure as a necessary monomer component are preferred examples. More preferably, acrylic polymers comprising (meth)acrylates having an intramolecular cyclic structure and (meth)acrylates having straight-chain or branched alkyl groups as necessary monomer components are preferred examples. That is, as the aforementioned acrylic oligomers, acrylic polymers containing (meth)acrylates having an intramolecular cyclic structure as monomer units are preferred examples. More preferably, acrylic polymers containing (meth)acrylates having an intramolecular cyclic structure and (meth)acrylates having straight-chain or branched alkyl groups as monomer units are preferred examples.
[0278] The cyclic structure (ring) of the aforementioned (meth)acrylates with an intramolecular (intramolecular) cyclic structure (hereinafter sometimes referred to as "cyclic (meth)acrylates") can be any type of aromatic ring or non-aromatic ring, without particular limitation. Examples of the aforementioned aromatic rings include: aromatic carbocyclic rings [e.g., monocyclic carbocyclic rings such as benzene rings, fused carbocyclic rings such as naphthalene rings, etc.], and various aromatic heterocyclic rings, etc. Examples of non-aromatic rings mentioned above include: non-aromatic aliphatic rings (non-aromatic alicyclic rings) [e.g., cyclopentane rings, cyclohexane rings, cycloheptane rings, cyclooctane rings, etc.; cyclohexene rings, etc.], non-aromatic bridging rings [e.g., bicyclic hydrocarbon rings in pinane, pinene, camphene, norbornane, norbornene, etc.; tricyclic or more aliphatic hydrocarbon rings (bridging hydrocarbon rings) in adamantane, etc.], and non-aromatic heterocycles [e.g., epoxy rings, oxacyclopentane rings, oxacyclobutane rings, etc.], etc.
[0279] Examples of aliphatic hydrocarbon rings with three or more rings (bridged hydrocarbon rings with three or more rings) include: tetrahydrodicyclopentadienyl represented by formula (5a), dihydrodicyclopentadienyl represented by formula (5b), adamantyl represented by formula (5c), tetrahydrotricyclopentadienyl represented by formula (5d), and dihydrotricyclopentadienyl represented by formula (5e).
[0280]
[0281] That is, examples of the above-mentioned cyclic (meth)acrylates include: cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, cyclooctyl (meth)acrylate, and other cycloalkyl (meth)acrylates; isobornyl (meth)acrylate and other (meth)acrylates having a bicyclic aliphatic hydrocarbon ring; tetrahydrodicyclopentadienyl (meth)acrylate, tetrahydrodicyclopentadienyloxyethyl (meth)acrylate, tetrahydrotricyclopentadienyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, 2-ethyl-2-adamantyl (meth)acrylate, and other (meth)acrylates having three or more aliphatic hydrocarbon rings; phenyl (meth)acrylate and other aryl (meth)acrylates, phenoxyethyl (meth)acrylate and other aryloxyalkyl (meth)acrylates, benzyl (meth)acrylate and other arylalkyl (meth)acrylates having aromatic rings, etc. Among these, (meth)acrylates containing rings are particularly preferred, especially those containing non-aromatic rings, and more preferably cyclohexyl acrylate (CHA), cyclohexyl methacrylate (CHMA), tetrahydrodicyclopentadienyl acrylate (DCPA), and tetrahydrodicyclopentadienyl methacrylate (DCPMA), and even more preferably tetrahydrodicyclopentadienyl acrylate (DCPA) and tetrahydrodicyclopentadienyl methacrylate (DCPMA). It should be noted that (meth)acrylates containing rings can be used alone or in combination of two or more.
[0282] Among the aforementioned (meth)acrylates containing non-aromatic rings, from the viewpoint of minimizing polymerization inhibition, (meth)acrylates having three or more aliphatic hydrocarbon rings (especially bridging hydrocarbon rings with three or more rings) are particularly preferred. Furthermore, when using (meth)acrylates without unsaturated bonds that contain tetrahydrodicyclopentadienyl (represented by formula (5a), adamantyl (represented by formula (5c), or tetrahydrotricyclopentadienyl (represented by formula (5d)), foaming peel resistance can be further improved, and adhesion to low-polarity substrates such as polyethylene and polypropylene can be significantly improved.
[0283] There is no particular limitation on the content (ratio) of the aforementioned cyclic (meth)acrylate in all monomer units (total monomer components constituting the acrylic oligomer), but it is preferably 10 to 90 parts by weight, more preferably 20 to 80 parts by weight, relative to the total monomer components constituting the acrylic oligomer (100 parts by weight). When the content of the aforementioned cyclic (meth)acrylate is 10 parts by weight or more, it is preferable to easily improve the foaming peel resistance. In addition, when the content of the aforementioned cyclic (meth)acrylate is 90 parts by weight or less, the adhesive layer has moderate flexibility, which is preferable to easily improve adhesion, height difference absorption, etc.
[0284] Furthermore, examples of alkyl (meth)acrylates having straight-chain or branched alkyl groups as monomer units of acrylic oligomers include: methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and so on. Alkyl methacrylates, such as isooctyl acrylate, nonyl methacrylate, isononyl methacrylate, decyl methacrylate, isodecanyl methacrylate, undecyl methacrylate, dodecyl methacrylate, tridecyl methacrylate, tetradecyl methacrylate, pentadecyl methacrylate, hexadecyl methacrylate, heptadecanyl methacrylate, octadecyl methacrylate, nonadecanyl methacrylate, and eicosyl methacrylate, are alkyl methacrylates with 1 to 20 carbon atoms. Among these, methyl methacrylate (MMA) is preferred from the viewpoint of good compatibility with acrylic polymers. It should be noted that the above-mentioned alkyl methacrylates can be used alone or in combination of two or more.
[0285] There is no particular limitation on the content (ratio) of the aforementioned alkyl (meth)acrylates having straight-chain or branched alkyl groups in all monomer units (total monomer components constituting the acrylic oligomer). From the viewpoint of foaming and peel resistance, it is preferably 10 to 90 parts by weight, more preferably 20 to 80 parts by weight, and even more preferably 20 to 60 parts by weight, relative to the total monomer components constituting the acrylic oligomer (100 parts by weight). When the content of the aforementioned alkyl (meth)acrylates having straight-chain or branched alkyl groups is 10 parts by weight or more, it is particularly easy to improve the adhesion to substrates made of acrylic resins and polycarbonate, which is preferred.
[0286] As monomer units of acrylic oligomers, in addition to the aforementioned cyclic (meth)acrylates and alkyl (meth)acrylates having straight or branched alkyl groups, monomers capable of copolymerizing with these monomers (copolymerizable monomers) may also be included. It should be noted that there is no particular limitation on the content (ratio) of the aforementioned copolymerizable monomers in all monomer units of the acrylic oligomer (the total amount of monomer components constituting the acrylic oligomer), but it is preferably 49.9 parts by weight or less (e.g., 0 parts by weight to 49.9 parts by weight), more preferably 30 parts by weight or less, relative to the total amount of monomer components constituting the acrylic oligomer (100 parts by weight). Furthermore, two or more copolymerizable monomers may be used alone or in combination.
[0287] Examples of copolymerizable monomers that serve as monomeric units of acrylic oligomers (the copolymerizable monomers constituting acrylic oligomers) include: alkoxyalkyl esters of (meth)acrylate [e.g., 2-methoxyethyl ester, 2-ethoxyethyl ester, methoxytriethylene glycol ester, 3-methoxypropyl ester, 3-ethoxypropyl ester, 4-methoxybutyl ester, 4-ethoxybutyl ester, etc.]; monomers containing hydroxyl groups [e.g., 2-hydroxyethyl ester, 2-hydroxypropyl ester, 2-hydroxybutyl ester, 3-hydroxypropyl ester, 4-hydroxybutyl ester, 6-hydroxyhexyl ester, etc.; hydroxyalkyl esters of (meth)acrylate; vinyl alcohol.] Monomers containing amide groups [e.g., (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, etc.]; monomers containing amino groups [e.g., aminoethyl(meth)acrylate, dimethylaminoethyl(meth)acrylate, tert-butylaminoethyl(meth)acrylate, etc.]; monomers containing cyano groups [e.g., acrylonitrile, methacrylonitrile, etc.]; monomers containing sulfonic acid groups [e.g., sodium vinyl sulfonate, etc.]; monomers containing phosphate groups [e.g., 2-hydroxyethylacryloyl phosphate, etc.]; monomers containing isocyanate groups [e.g., 2-methacryloyloxyethyl isocyanate, etc.]; monomers containing imide groups [cyclohexylmaleimide, isopropylmaleimide, etc.], etc.
[0288] As described above, acrylic oligomers are preferably acrylic polymers comprising (meth)acrylates having an intramolecular cyclic structure and (meth)acrylates having straight-chain or branched alkyl groups as monomer units. Preferably, they are acrylic polymers comprising (meth)acrylates containing a ring and the aforementioned (meth)acrylates having straight-chain or branched alkyl groups as monomer units. In the aforementioned acrylic polymers comprising (meth)acrylates containing a ring and (meth)acrylates having straight-chain or branched alkyl groups as monomer units, the amount of (meth)acrylates containing a ring relative to the total amount of monomer components constituting the acrylic oligomer (100 parts by weight) is not particularly limited, but is preferably 10 to 90 parts by weight, more preferably 20 to 80 parts by weight. Furthermore, the content of (meth)acrylates having straight-chain or branched alkyl groups is not particularly limited, but is preferably 10 to 90 parts by weight, more preferably 20 to 80 parts by weight, and even more preferably 20 to 60 parts by weight.
[0289] Furthermore, a particularly preferred specific composition for acrylic oligomers can be listed as follows: an acrylic polymer comprising (1) at least one monomer selected from the group consisting of tetrahydrodicyclopentadienyl acrylate, tetrahydrodicyclopentadienyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate, and (2) methyl methacrylate as a monomer unit. In the acrylic oligomers with the above-mentioned particularly preferred specific composition, it is preferable that, relative to the total amount of monomer components constituting the acrylic oligomer (100 parts by weight), the content of (1) tetrahydrodicyclopentadienyl acrylate, tetrahydrodicyclopentadienyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate in all monomer units of the acrylic oligomer (the total amount of these monomers if two or more are included) is 30 to 70 parts by weight, and the content of (2) methyl methacrylate is 30 to 70 parts by weight. However, the above-mentioned acrylic oligomers are not limited to the above-mentioned specific composition.
[0290] Acrylic oligomers can be obtained by polymerizing the aforementioned monomer components using known or conventional polymerization methods. Examples of polymerization methods for these acrylic oligomers include solution polymerization, emulsion polymerization, bulk polymerization, and polymerization using active energy rays (active energy ray polymerization). Bulk polymerization and solution polymerization are preferred, with solution polymerization being more preferred.
[0291] Various common solvents can be used in the polymerization of acrylic oligomers. Examples of such solvents include: esters such as ethyl acetate and n-butyl acetate; aromatic hydrocarbons such as toluene and benzene; aliphatic hydrocarbons such as n-hexane and n-heptane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; and ketones such as methyl ethyl ketone and methyl isobutyl ketone. It should be noted that such solvents can be used alone or in combination of two or more.
[0292] Furthermore, in the polymerization of acrylic oligomers, known or conventional polymerization initiators (e.g., thermal polymerization initiators, photopolymerization initiators, etc.) can be used. It should be noted that polymerization initiators can be used alone or in combination of two or more.
[0293] Examples of thermal polymerization initiators include: 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2-methylbutyronitrile) (AMBN), dimethyl 2,2'-azobis(2-methylpropionic acid), 4,4'-azobis(4-cyanopentanoic acid), 2,2'-azobis(4-methoxy-2,4-dimethylpentanonitrile), 2,2'-azobis(2,4-dimethylpentanonitrile), 1 Azo initiators include 1'-azobis(cyclohexane-1-carboxynitrile) and 2,2'-azobis(2,4,4-trimethylpentane); peroxide initiators include benzoyl peroxide, tert-butyl hydroperoxide, di-tert-butyl peroxide, tert-butyl peroxide, dicumyl peroxide, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, and 1,1-bis(tert-butylperoxy)cyclododecane. It should be noted that oil-soluble polymerization initiators are preferred for solution polymerization. Furthermore, two or more thermal polymerization initiators can be used alone or in combination.
[0294] There is no particular limitation on the amount of the aforementioned thermal polymerization initiator used. For example, the amount of the thermal polymerization initiator used is 0.1 to 15 parts by weight relative to 100 parts by weight of all monomer units of the acrylic oligomer (the total amount of monomer components constituting the acrylic oligomer).
[0295] Furthermore, there are no particular limitations on the photopolymerization initiator used, and for example, the same photopolymerization initiators used in the polymerization of the acrylic polymers listed above can be cited. There are no particular limitations on the amount of the photopolymerization initiator used; it can be selected appropriately.
[0296] In the polymerization of the aforementioned acrylic oligomers, chain transfer agents can be used to adjust the molecular weight (specifically, to adjust the weight-average molecular weight to 1000–30000). Examples of such chain transfer agents include: 2-mercaptoethanol, α-thioglycerol, 2,3-dimercapto-1-propanol, octylthiol, tert-nonylthiol, dodecylthiol (laurylthiol), tert-dodecylthiol, glycidylthiol, mercaptoacetic acid, methyl mercaptoacetate, ethyl mercaptoacetate, propyl mercaptoacetate, butyl mercaptoacetate, tert-butyl mercaptoacetate, 2-ethylhexyl mercaptoacetate, octyl mercaptoacetate, isooctyl mercaptoacetate, decyl mercaptoacetate, dodecyl mercaptoacetate, ethylene glycol mercaptoacetate, neopentyl glycol mercaptoacetate, pentaerythritol mercaptoacetate, and α-methylstyrene dimer. From the viewpoint of suppressing the whitening of the optical adhesive tape of the present invention caused by humidification, α-thioglycerol and methyl mercaptoacetate are preferred, with α-thioglycerol being particularly preferred. It should be noted that chain transfer agents can be used alone or in combination of two or more.
[0297] There is no particular limitation on the content (amount) of the chain transfer agent. Relative to 100 parts by weight of all monomer units of the acrylic oligomer (the total amount of monomer components constituting the acrylic oligomer), the content (amount) of the chain transfer agent is preferably 0.1 parts by weight to 20 parts by weight, more preferably 0.2 parts by weight to 15 parts by weight, and even more preferably 0.3 parts by weight to 10 parts by weight. By setting the content (amount) of the chain transfer agent within the above range, acrylic oligomers with a weight-average molecular weight controlled to be 1000 to 30000 can be easily obtained.
[0298] The weight-average molecular weight (Mw) of the aforementioned acrylic oligomers is 1,000 to 30,000, preferably 1,000 to 20,000, more preferably 1,500 to 10,000, and even more preferably 2,000 to 8,000. Since the weight-average molecular weight of the acrylic oligomers is 1,000 or more, the adhesive strength, retention properties, and foam peel resistance are improved. On the other hand, since the weight-average molecular weight of the acrylic oligomers is 30,000 or less, it is easier to improve the adhesive strength and foam peel resistance.
[0299] The weight-average molecular weight (Mw) of the aforementioned acrylic oligomers can be determined by GPC and polystyrene conversion. For example, it can be determined using a high-speed GPC apparatus, HPLC-8120GPC, manufactured by Tosoh Corporation, under the following conditions.
[0300] Column: TSKgel Super HZM-H / HZ4000 / HZ3000 / HZ2000
[0301] Solvent: Tetrahydrofuran
[0302] Flow rate: 0.6 ml / min
[0303] There is no particular limitation on the glass transition temperature (Tg) of the aforementioned acrylic oligomers, but it is preferably 20°C to 300°C, more preferably 30°C to 300°C, and even more preferably 40°C to 300°C. When the glass transition temperature of the acrylic oligomers is above 20°C, it is easier to improve the foaming peel resistance, which is preferred. Furthermore, when the glass transition temperature of the acrylic oligomers is below 300°C, the adhesive layer has moderate flexibility, making it easy to obtain good adhesion, good height difference absorption, and excellent adhesive reliability, which is also preferred.
[0304] The glass transition temperature (Tg) of the aforementioned acrylic oligomers is the theoretical value expressed by the FOX formula above.
[0305] The Tg of homopolymers of monomers constituting the aforementioned acrylic oligomers can be taken from the values listed in Table 1 below. Furthermore, the Tg of homopolymers of monomers not listed in Table 1 can be taken from the values listed in the "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989). Additionally, the Tg of homopolymers of monomers not listed in the aforementioned literature can be taken from the values obtained by the aforementioned measurement method (the peak temperature of tanδ obtained by viscoelasticity testing).
[0306] [Table 1]
[0307]
[0308] It should be noted that the copolymer “DCPMA / MMA=60 / 40” in Table 1 refers to a copolymer of 60 parts by weight of DCPMA and 40 parts by weight of MMA.
[0309] There is no particular limitation on the content of acrylic oligomers in the acrylic adhesive composition containing both acrylic polymers and acrylic oligomers. The content of acrylic oligomers is preferably 1 to 30 parts by weight, more preferably 2 to 20 parts by weight, and even more preferably 2 to 10 parts by weight, relative to 100 parts by weight of the acrylic polymer. That is, there is no particular limitation on the content of acrylic oligomers in the adhesive composition. The content of acrylic oligomers is preferably 1 to 30 parts by weight, more preferably 2 to 20 parts by weight, and even more preferably 2 to 10 parts by weight, relative to 100 parts by weight of all monomer units of the acrylic polymer. There is no particular limitation on the content of acrylic oligomers in the acrylic adhesive composition. For example, the content of acrylic oligomers is preferably 1 to 30 parts by weight, more preferably 2 to 20 parts by weight, and even more preferably 2 to 10 parts by weight, relative to 100 parts by weight of the monomer mixture. When the content of acrylic oligomers is 1 part by weight or more, excellent adhesiveness and excellent foaming peel resistance are easily obtained, which is preferred. Furthermore, when the content of acrylic oligomers is 30 parts by weight or less, excellent transparency and adhesive reliability are easily obtained, which is also preferred. In addition, from the viewpoint of easily controlling the various properties of the adhesive layer (especially strain A, strain B, recovery rate, glass transition temperature, etc.) within a specified range, the content of acrylic oligomers is preferably 10 parts by weight or less, more preferably 8 parts by weight or less.
[0310] There are no particular limitations on the method for producing the above-described adhesive composition containing acrylic polymers and acrylic oligomers. For example, it can be produced by adding acrylic oligomers, additives, etc. as needed to a mixture of monomer components constituting acrylic polymers or a portion of a mixture of monomer components constituting acrylic polymers (the monomer mixture forming acrylic polymers or a portion of the polymer thereof) and mixing them.
[0311] There are no particular limitations on the adhesive layer of the present invention, but it is preferable to contain an ultraviolet (UVA) absorber. When the adhesive layer of the present invention contains an ultraviolet absorber, it is preferable from the viewpoint of being able to suppress damage to the image display panel caused by ultraviolet rays. It should be noted that ultraviolet absorbers can be used alone or in combination of two or more.
[0312] There are no particular limitations on the types of ultraviolet absorbers mentioned above. Examples include: benzotriazole ultraviolet absorbers, hydroxyphenyltriazine ultraviolet absorbers, benzophenone ultraviolet absorbers, salicylates ultraviolet absorbers, cyanoacrylate ultraviolet absorbers, and hydroxybenzophenone ultraviolet absorbers.
[0313] Examples of benzotriazole UV absorbers (benzotriazole compounds) include: 2-(2-hydroxy-5-tert-butylphenyl)-2H-benzotriazole (trade name "TINUVIN PS", manufactured by BASF); esters of phenylpropionic acid and 3-(2H-benzotriazole-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy (C7-9 side chain and straight-chain alkyl) (trade name "TINUVIN 384-2", manufactured by BASF); and mixtures of octyl 3-[3-tert-butyl-4-hydroxy-5-(5-chloro-2H-benzotriazole-2-yl)phenyl]propionate and 2-ethylhexyl 3-[3-tert-butyl-4-hydroxy-5-(5-chloro-2H-benzotriazole-2-yl)phenyl]propionate (trade name "TINUVIN"). 109, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (trade name "TINUVIN 900", manufactured by BASF), 2-(2H-benzotriazol-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (trade name "TINUVIN 928", manufactured by BASF), the reaction product of methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propionate and polyethylene glycol 300 (trade name "TINUVIN 1130", manufactured by BASF), 2-(2H-benzotriazol-2-yl)-p-cresol (trade name "TINUVIN 109"). P", manufactured by BASF, 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (trade name "TINUVIN 234", manufactured by BASF), 2-[5-chloro-2H-benzotriazol-2-yl]-4-methyl-6-tert-butylphenol (trade name "TINUVIN 326", manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol (trade name "TINUVIN 328", manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol (trade name "TINUVIN 329", manufactured by BASF), 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol[3-Tetramethylbutyl)phenol] (trade name "TINUVIN 360", manufactured by BASF), methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propionate reacting with polyethylene glycol 300 (trade name "TINUVIN 213", manufactured by BASF), 2-(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol (trade name "TINUVIN 571", manufactured by BASF), 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidemethyl)-5-methylphenyl]benzotriazole (trade name "Sumisorb 250", manufactured by Sumitomo Chemical Co., Ltd.), 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-tert-octylphenol] (trade name "ADK STAB") LA-31", manufactured by ADEKA Co., Ltd.), etc.,
[0314] Examples of hydroxyphenyl triazine UV absorbers (hydroxyphenyl triazine compounds) include: the reaction product of 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-hydroxyphenyl with [(C10-C16 (mainly C12-C13)alkoxy)methyl]ethylene oxide (trade name "TINUVIN 400", manufactured by BASF); 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]-5-[3-(dodecyloxy)-2-hydroxypropoxy]phenol; and the reaction product of 2-(2,4-dihydroxyphenyl)-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine with (2-ethylhexyl) glycidyl acid (trade name "TINUVIN"). The following are listed as products: 405 (manufactured by BASF), 2,4-bis(2-hydroxy-4-butoxyphenyl)-6-(2,4-dibutoxyphenyl)-1,3,5-triazine (trade name "TINUVIN 460", manufactured by BASF), 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-hexyloxyphenol (trade name "TINUVIN 1577", manufactured by BASF), 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]phenol (trade name "ADK STAB LA-46", manufactured by ADEKA Corporation), 2-(2-hydroxy-4-[1-octoxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (trade name "TINUVIN 479", manufactured by BASF), etc. In addition, compounds represented by the following formula (6) can be listed (trade name "TINUVIN 477", manufactured by BASF).
[0315]
[0316] Examples of benzophenone-based ultraviolet absorbers (benzophenone compounds) and hydroxybenzophenone-based ultraviolet absorbers (hydroxybenzophenone compounds) include: 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid (anhydrous and trihydrate salts), 2-hydroxy-4-octoxybenzophenone, 4-dodecyloxy-2-hydroxybenzophenone, 4-benzyloxy-2-hydroxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone (trade name "KEMISORB 111", manufactured by Chemipro Chemical Co., Ltd.), 2,2',4,4'-tetrahydroxybenzophenone (trade name "SEESORB 106", manufactured by Shipro Chemical Co., Ltd.), and 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, etc.
[0317] Examples of salicylate-based ultraviolet absorbers (salicylate compounds) include: phenyl 2-acryloyloxybenzoate, phenyl 2-acryloyloxy-3-methylbenzoate, phenyl 2-acryloyloxy-4-methylbenzoate, phenyl 2-acryloyloxy-5-methylbenzoate, phenyl 2-acryloyloxy-3-methoxybenzoate, phenyl 2-hydroxybenzoate, phenyl 2-hydroxy-3-methylbenzoate, phenyl 2-hydroxy-4-methylbenzoate, phenyl 2-hydroxy-5-methylbenzoate, phenyl 2-hydroxy-3-methoxybenzoate, and 2,4-di-tert-butyl-4-hydroxybenzoate (trade name "TINUVIN 120", manufactured by BASF).
[0318] Examples of cyanoacrylate ultraviolet absorbers (cyanoacrylate compounds) include: alkyl cyanoacrylate, cycloalkyl cyanoacrylate, alkoxyalkyl cyanoacrylate, alkenyl cyanoacrylate, alkynyl cyanoacrylate, etc.
[0319] As the aforementioned ultraviolet absorber, from the viewpoints of further improving corrosion resistance (especially UV resistance) while possessing high ultraviolet absorption, easily obtaining an adhesive layer with excellent optical properties and high transparency, and having excellent photostability, at least one ultraviolet absorber selected from the group consisting of benzotriazole ultraviolet absorbers, benzophenone ultraviolet absorbers, and hydroxyphenyltriazine ultraviolet absorbers is preferred, and benzotriazole ultraviolet absorbers and benzophenone ultraviolet absorbers are more preferred. Particularly preferred are benzotriazole ultraviolet absorbers having a group having 6 or more carbon atoms and a phenyl group as a substituent bonded to a nitrogen atom constituting the benzotriazole ring.
[0320] Furthermore, from the viewpoint of obtaining higher ultraviolet absorption and further improving corrosion resistance (especially UV resistance), the above-mentioned ultraviolet absorber preferably has an absorbance A of 0.5 or less as determined below.
[0321] Absorbance A: The absorbance measured by irradiating a 0.08% toluene solution of the above ultraviolet absorber with light of a wavelength of 400 nm.
[0322] When the adhesive layer of the present invention contains a UV absorber, there is no particular limitation on the content of the UV absorber in the adhesive layer (especially the acrylic adhesive layer) of the present invention. From the viewpoint of further improving corrosion resistance (especially UV resistance), the content of the UV absorber is preferably 0.01 parts by weight or more, more preferably 0.05 parts by weight or more, and even more preferably 0.1 parts by weight or more, relative to 100 parts by weight of the base polymer. In addition, from the viewpoint of suppressing the yellowing phenomenon of the adhesive accompanying the addition of the UV absorber and obtaining excellent optical properties, high transparency and excellent appearance properties, the upper limit of the content of the UV absorber relative to 100 parts by weight is preferably 10 parts by weight or less, more preferably 9 parts by weight or less, and even more preferably 8 parts by weight or less.
[0323] The adhesive layer of the present invention may contain a light stabilizer. When the adhesive layer of the present invention contains a light stabilizer, it is particularly preferable to contain a light stabilizer simultaneously with the aforementioned ultraviolet absorber. The light stabilizer can capture free radicals generated due to photo-oxidation, thus improving the light resistance (especially ultraviolet) of the adhesive layer. It should be noted that light stabilizers can be used alone or in combination of two or more.
[0324] There are no particular limitations on the above-mentioned light stabilizers. Examples include: phenolic light stabilizers (phenolic compounds), phosphorus-containing light stabilizers (phosphorus-containing compounds), thioether light stabilizers (thioether compounds), amine light stabilizers (amine compounds) (especially hindered amine light stabilizers (hindered amine compounds)), etc.
[0325] Examples of phenolic light stabilizers (phenolic compounds) include: 2,6-di-tert-butyl-4-methylphenol, 4-hydroxymethyl-2,6-di-tert-butylphenol, 2,6-di-tert-butyl-4-ethylphenol, butylated hydroxyanisole, octadecyl 3-(4-hydroxy-3,5-di-tert-butylphenyl)propionate, distearate (4-hydroxy-3-methyl-5-tert-butyl)benzylmalonate, tocopherol, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), and 4,4'-methylenebis(2,6-di-tert-butylphenol). ), 4,4'-Butidene bis(6-tert-butyl-m-cresol), 4,4'-Thiobis(6-tert-butyl-m-cresol), Styrified phenol, N,N'-Hexamethylene bis(3,5-di-tert-butyl-4-hydroxyhydrocinnamate), bis(3,5-di-tert-butyl-4-hydroxybenzylphosphonate ethyl ester) calcium, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, 1,6-hexanediol bis[3-( [3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,2'-methylenebis(4-methyl-6-cyclohexylphenol), 2,2'-methylenebis[6-(1-methylcyclohexyl)-p-cresol], 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanuric acid, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanuric acid, triethylene glycol bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], 2,2'-oxamidobis[ethyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 6-(4-hydroxy -3,5-di-tert-butylaniline)-2,4-dioctylthio-1,3,5-triazine, di[2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl] ester, 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxellaspiro[5.5]undecane, 3,9-bis{2-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxellaspiro[5.5]undecane, etc.
[0326] Examples of phosphorus-containing light stabilizers (phosphorus compounds) include: tris(nonylphenyl) phosphite, tris(2,4-di-tert-butylphenyl) phosphite, tris[2-tert-butyl-4-(3-tert-butyl-4-hydroxy-5-methylphenylthio)-5-methylphenyl] phosphite, tridecyl phosphite, diphenyl octyl phosphite, monophenyl di(decyl) phosphite, pentaerythritol diphosphite di(tridecyl) ester, pentaerythritol diphosphite distearate ester, pentaerythritol diphosphite di(nonylphenyl) ester, pentaerythritol diphosphite di(2,4-di-tert-butylphenyl) ester, and pentaerythritol diphosphite di(2,6-di-tert-butyl-4-methylphenyl) ester. Pentaerythritol diphosphite di(2,4,6-tri-tert-butylphenyl) ester, isopropylidene diphenol diphosphite tetra(tetrazyl) ester, 4,4'-n-butylidene bis(2-tert-butyl-5-methylphenol) diphosphite tetra(tetrazyl) ester, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane triphosphite hexa(tetrazyl) ester, biphenylene diphosphonate tetra(2,4-di-tert-butylphenyl) ester, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, tris(2-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphacyclohepta-dien-6-yl)oxy]ethyl)amine, etc.
[0327] Examples of thioether light stabilizers (thioether compounds) include: dilauryl thiodipropionate, dimyristyl thiodipropionate, distearate thiodipropionate, and other dialkyl thiodipropionate compounds; β-alkyl mercaptopropionate compounds of polyols such as tetra[methylene(3-dodecylthio)propionate]methane, etc.
[0328] Examples of amine-based light stabilizers (amine compounds) include: a polymer of dimethyl succinate and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidineethanol (trade name "TINUVIN 622", manufactured by BASF); a polymer of dimethyl succinate and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidineethanol; and a 1:1 reaction product of N,N',N”,N”'-tetra(4,6-bis(butyl-(N-methyl-2,2,6,6-tetramethylpiperidine-4-yl)amino)-triazin-2-yl)-4,7-diazadecane-1,10-diamine (trade name "TINUVIN"). 119”, manufactured by BASF), dibutylamine / 1,3,5-triazine / N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidinyl)butylamine condensate (trade name “TINUVIN 2020”, manufactured by BASF), poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{2,2,6,6-tetramethyl-4-piperidinyl}imino]hexamethylene{(2,2,6,6-tetramethyl-4-piperidinyl)imino} (trade name “TINUVIN”) 944, manufactured by BASF), a mixture of di(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and methyl sebacate 1,2,2,6,6-pentamethyl-4-piperidinyl ester (trade name "TINUVIN 765", manufactured by BASF), di(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (trade name "TINUVIN 770", manufactured by BASF), di(2,2,6,6-tetramethyl-1-(octoxy)-4-piperidinyl) sebacate, the reaction product of 1,1-dimethylethyl hydroperoxide and octane (trade name "TINUVIN 123", manufactured by BASF), [[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butylmalonate di(1,2,2,6,6-pentamethyl-4-piperidinyl) ester (trade name "TINUVIN 765"). 144”, manufactured by BASF, a reaction product of cyclohexane and N-butylperoxide-2,2,6,6-tetramethyl-4-piperidinamine-2,4,6-trichloro-1,3,5-triazine with 2-aminoethanol (trade name “TINUVIN 152”, manufactured by BASF), a mixture of di(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and methyl sebacate 1,2,2,6,6-pentamethyl-4-piperidinyl ester (trade name “TINUVIN 292”, manufactured by BASF), 1,2,3,4-butanetetracarboxylic acid with 1,2,2,6,6-pentamethyl-4-piperidinol and 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,Mixed esters of 10-tetraoxaspiro[5.5]undecane (trade name "ADK STAB LA-63P", manufactured by ADEKA Corporation), etc. Hindered amine stabilizers are particularly preferred as amine stabilizers.
[0329] When the adhesive layer of the present invention contains a light stabilizer, there is no particular limitation on the content of the light stabilizer in the adhesive layer (especially the acrylic adhesive layer). From the viewpoint of easily exhibiting lightfastness, the content of the light stabilizer is preferably 0.1 parts by weight or more, more preferably 0.2 parts by weight or more, relative to 100 parts by weight of the base polymer. Furthermore, from the viewpoints of minimizing coloration caused by the light stabilizer itself, easily obtaining high transparency, and optical properties, the upper limit of the above-mentioned light stabilizer content is preferably 5 parts by weight or less, more preferably 3 parts by weight or less, relative to 100 parts by weight of the base polymer.
[0330] There are no particular limitations on the formation of the adhesive layer of the present invention, and crosslinking agents can be used. For example, acrylic polymers in acrylic adhesive layers can be crosslinked to control the gel fraction. It should be noted that crosslinking agents can be used alone or in combination of two or more.
[0331] There are no particular limitations on the crosslinking agents mentioned above, and examples include: isocyanate crosslinking agents, epoxy crosslinking agents, melamine crosslinking agents, peroxide crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, zopyridine crosslinking agents, amine crosslinking agents, etc. Among them, isocyanate crosslinking agents and epoxy crosslinking agents are preferred, and isocyanate crosslinking agents are more preferred.
[0332] Examples of crosslinking agents (polyfunctional isocyanate compounds) for the aforementioned isocyanates include: lower aliphatic polyisocyanates such as 1,2-ethylidene diisocyanate, 1,4-butylidene diisocyanate, and 1,6-hexamethylene diisocyanate; alicyclic polyisocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated xylene diisocyanate; and aromatic polyisocyanates such as 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and phenylenediamine diisocyanate. In addition, as crosslinking agents for the aforementioned isocyanates, examples include: trimethylolpropane / toluene diisocyanate adduct (trade name "Coronate L", manufactured by Nippon Polyurethane Kogyo Co., Ltd.), trimethylolpropane / hexamethylene diisocyanate adduct (trade name "Coronate HL", manufactured by Nippon Polyurethane Kogyo Co., Ltd.), and trimethylolpropane / phenylenediamine diisocyanate adduct (trade name "Takenate D-110N", manufactured by Mitsui Chemicals Co., Ltd.), etc.
[0333] Examples of epoxy crosslinking agents (multifunctional epoxy compounds) include: N,N,N',N'-tetraglycidyl-m-phenylenediamine, diglycidyl-aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitan... These include polyglycidyl ethers, glycerol polyglycidyl ethers, pentaerythritol polyglycidyl ethers, polyglycerol polyglycidyl ethers, sorbitol polyglycidyl ethers, trimethylolpropane polyglycidyl ethers, diglycidyl adipic acid ester, diglycidyl phthalate ester, tri(2-hydroxyethyl)isocyanurate triglycidyl ester, resorcinol diglycidyl ether, bisphenol S diglycidyl ether, and epoxy resins having two or more epoxy groups within the molecule. Additionally, commercially available products such as "Tetrad C" (manufactured by Mitsubishi Gas Chemical Co., Ltd.) can also be cited as examples of the aforementioned epoxy crosslinking agents.
[0334] When a crosslinking agent is used in the formation of the adhesive layer of the present invention, there is no particular limitation on the amount of the crosslinking agent used. From the viewpoint of obtaining sufficient adhesive reliability, the amount of the crosslinking agent used is preferably 0.001 parts by weight or more, more preferably 0.01 parts by weight or more, relative to 100 parts by weight of the base polymer. In addition, from the viewpoint of obtaining appropriate flexibility of the adhesive layer, improving adhesion, and easily controlling the various properties of the adhesive layer (especially strain A, strain B, recovery rate, glass transition temperature, etc.) within a specified range, the upper limit of the amount of the crosslinking agent used is preferably 10 parts by weight or less, more preferably 5 parts by weight or less, relative to 100 parts by weight of the base polymer.
[0335] From the viewpoint of improving adhesive reliability under humidified conditions, and particularly improving adhesive reliability to glass, the adhesive layer (especially the acrylic adhesive layer) of the present invention may contain a silane coupling agent. It should be noted that silane coupling agents can be used alone or in combination of two or more. When the adhesive layer contains a silane coupling agent, adhesive properties under humidified conditions, especially adhesive properties to glass, can be improved.
[0336] There are no particular limitations on the silane coupling agents mentioned above, and examples include γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyltriethoxysilane, γ-aminopropyltrimethoxysilane, and N-phenylaminopropyltrimethoxysilane. Furthermore, commercially available products under the trade name "KBM-403" (manufactured by Shin-Etsu Chemical Co., Ltd.) can also be cited as examples. Among these, γ-glycidoxypropyltrimethoxysilane is preferred as the silane coupling agent mentioned above.
[0337] When the adhesive layer of the present invention contains a silane coupling agent, there is no particular limitation on the content of the silane coupling agent in the adhesive layer (especially the acrylic adhesive layer) of the present invention. The content of the silane coupling agent is preferably 0.01 parts by weight or more, more preferably 0.02 parts by weight or more, relative to 100 parts by weight of the base polymer. Furthermore, the upper limit of the content of the silane coupling agent relative to 100 parts by weight is preferably 1 part by weight or less, more preferably 0.5 parts by weight or less.
[0338] The adhesive layer of this invention may contain an antistatic agent. It should be noted that the antistatic agent can be used alone or in combination of two or more. When the adhesive layer contains an antistatic agent, it can prevent damage to the adhered objects such as image display panels.
[0339] Examples of antistatic agents include: cationic antistatic agents with cationic functional groups such as quaternary ammonium salts, pyridinium salts, primary amine groups, secondary amine groups, and tertiary amine groups; anionic antistatic agents with anionic functional groups such as sulfonates, sulfates, phosphonates, and phosphates; zwitterionic antistatic agents such as alkyl betaines and their derivatives, imidazolines and their derivatives, and alanine and its derivatives; nonionic antistatic agents such as amino alcohols and their derivatives, glycerols and their derivatives, and polyethylene glycols and their derivatives; and ionically conductive polymers obtained by polymerizing or copolymerizing monomers with the above-mentioned cationic, anionic, and zwitterionic ion-conductive groups.
[0340] When the adhesive layer of the present invention contains an antistatic agent, there is no particular limitation on the content of the antistatic agent in the adhesive layer of the present invention. The content of the antistatic agent is preferably 0.01 parts by weight or more, more preferably 0.02 parts by weight or more, relative to 100 parts by weight of the base polymer. Furthermore, the upper limit of the content of the antistatic agent relative to 100 parts by weight is preferably 1 part by weight or less, more preferably 0.5 parts by weight or less.
[0341] The adhesive layer of the present invention may contain a colorant. It should be noted that the colorant can be used alone or in combination of two or more. When the adhesive layer contains a colorant, it is preferable from the viewpoint of preventing reflections caused by metal wiring, ITO wiring, etc., disposed on the substrate of the image display device of the present invention.
[0342] The aforementioned colorant can be either a dye or a pigment, as long as it can be dissolved or dispersed in the adhesive layer of the present invention. Dyes are preferred from the perspective of achieving low haze even with small amounts added, and from being easily and uniformly distributed unlike pigments due to their sedimentation properties. Furthermore, pigments are preferred from the perspective of high color development even with small amounts added. When using pigments as colorants, pigments with low or no conductivity are preferred. Additionally, when using dyes, it is preferable to use them in combination with the aforementioned light stabilizers, etc.
[0343] As the aforementioned colorant, any colorant that absorbs visible light (wavelength 400 nm to 700 nm) and exhibits transmittance to ultraviolet light (wavelength 330 nm to 400 nm) or absorbs ultraviolet light can be used without limitation. A colorant that absorbs visible light and exhibits ultraviolet transmittance is preferred. That is, the aforementioned colorant is preferably one whose maximum transmittance at wavelengths of 330 nm to 400 nm is greater than the maximum transmittance at wavelengths of 400 nm to 700 nm. Furthermore, the aforementioned colorant is preferably one whose average transmittance at wavelengths of 330 nm to 400 nm is greater than the average transmittance at wavelengths of 400 nm to 700 nm. The transmittance of the colorant is measured using a solution or dispersion diluted with a suitable solvent such as tetrahydrofuran (THF) or a dispersion medium (an organic solvent with low absorption in the wavelength range of 330 nm to 700 nm) to achieve a transmittance of approximately 50% to approximately 60% at wavelength 400 nm.
[0344] Carbon black or titanium black, commonly used as black colorants, absorb more ultraviolet light than visible light (ultraviolet transmittance is less than visible light transmittance). Therefore, when colorants such as carbon black are added to active energy ray-curable acrylic adhesive compositions, most of the ultraviolet light irradiated for photocuring is absorbed by the colorant, resulting in less light absorption by the photopolymerization initiator and requiring more time for photocuring (due to increased cumulative irradiation). Furthermore, with thick adhesive layers, less ultraviolet light reaches the side opposite the irradiated surface, leading to a tendency for insufficient photocuring even with prolonged irradiation. In contrast, using colorants with ultraviolet transmittance greater than visible light transmittance can suppress curing obstacles caused by the colorant.
[0345] Examples of black pigments that transmit ultraviolet light include "9050BLACK" and "UVBK-0001" manufactured by Tokushiki Co., Ltd. Examples of black pigments that absorb ultraviolet light include "VALIFAST BLACK 3810" and "NUBIAN Black PA-2802" manufactured by Orient Chemical Industry Co., Ltd. Examples of black pigments that absorb ultraviolet light include carbon black and titanium black.
[0346] Relative to 100 parts by weight of the aforementioned base polymer, the content of colorant in the adhesive layer of the present invention is, for example, about 0.01 parts by weight to about 20 parts by weight, and can be appropriately set according to the type of colorant, the hue of the adhesive layer, and the light transmittance, etc. The colorant can be added to the composition in the form of a solution or dispersion dissolved or dispersed in a suitable solvent.
[0347] The adhesive layer of the present invention may, as needed and without impairing the effects of the present invention, further contain additives such as crosslinking accelerators, tackifying resins (rosin derivatives, polyterpene resins, petroleum resins, oil-soluble phenols, etc.), anti-aging agents, fillers, antioxidants, chain transfer agents, plasticizers, softeners, and surfactants. It should be noted that such additives can be used alone or in combination of two or more.
[0348] There are no particular limitations on the haze of the adhesive layer of the present invention. From the viewpoint of appearance characteristics, transparency, and optical properties, it is preferably 5% or less, more preferably 3% or less, and even more preferably 1% or less. It should be noted that, in this specification, the haze of the adhesive layer can be measured, for example, using a haze meter according to JIS K 7136.
[0349] There are no particular limitations on the total light transmittance of the adhesive layer of the present invention. From the viewpoint of appearance characteristics, transparency, and optical properties, it is preferably 85% or more, more preferably 90% or more, and even more preferably 92% or more. It should be noted that, in this specification, the total light transmittance of the adhesive layer can be measured, for example, using a haze meter according to JIS K 7361-1. It should also be noted that the above-mentioned total light transmittance is the transmittance of light (visible light) with a wavelength of 400 nm to 780 nm.
[0350] There is no particular limitation on the thickness of the adhesive layer of the present invention. However, from the viewpoint of obtaining sufficient adhesive reliability, it is preferably 12 μm or more, more preferably 15 μm or more, further preferably 20 μm or more, and particularly preferably 70 μm or more. When the above-mentioned thickness is 12 μm or more, it is preferred from the viewpoint that the adhesive layer fully conforms to the shrinkage or expansion of the image display device of the present invention under the usage environment and can suppress bulging or peeling. In addition, from the viewpoint of optical properties, the above-mentioned thickness is preferably 500 μm or less, more preferably 300 μm or less, and further preferably 200 μm or less.
[0351] <Manufacturing of Optical Adhesive Tape>
[0352] The optical adhesive tape of the present invention can be prepared by laminating the adhesive layer of the present invention onto the first surface of the substrate of the present invention.
[0353] There are no particular limitations on the method of laminating the adhesive layer of the present invention onto the first surface of the substrate of the present invention. For example, it can be carried out by: applying the above-mentioned adhesive composition onto a spacer and drying and curing the resulting adhesive composition layer; applying the above-mentioned adhesive composition onto a spacer and irradiating the resulting adhesive composition layer with active energy rays to cure it, thereby forming a sheet-like adhesive layer on the spacer, and then attaching the adhesive layer to the first surface of the substrate of the present invention. In addition, further heating and drying can be performed as needed.
[0354] When curing by irradiation with active energy rays, it is preferable to further provide spacers on the surface of the coating film, and irradiate the adhesive composition with active energy rays while sandwiching the adhesive composition between two spacers, thereby preventing polymerization inhibition caused by oxygen.
[0355] Other methods for laminating the adhesive layer of the present invention onto the first surface of the substrate of the present invention may also be carried out, for example, by applying (coating) the above-described adhesive composition onto the first surface of the substrate of the present invention and allowing the resulting adhesive composition layer to dry and cure; or by applying (coating) the above-described adhesive composition onto the first surface of the substrate of the present invention and irradiating the resulting adhesive composition layer with active energy rays to cure it. Additionally, further heating and drying may be performed as needed.
[0356] When curing by irradiation with active energy rays, it is preferable to provide a spacer on the surface of the coating film, and irradiate the adhesive composition with active energy rays while the substrate of the present invention is sandwiched between the spacer, thereby preventing polymerization inhibition caused by oxygen.
[0357] Before irradiating with active energy rays, the sheet-like coating can be heated to remove solvents and other substances. When removing solvents and other substances by heating, it is preferable to perform this action before setting the spacer.
[0358] Examples of such active energy rays include ionizing radiation such as alpha rays, beta rays, gamma rays, neutron rays, and electron rays; ultraviolet radiation is also acceptable, with ultraviolet radiation being particularly preferred. Furthermore, there are no particular restrictions on the irradiation energy, irradiation time, or irradiation method for these active energy rays.
[0359] The above-described adhesive compositions can be prepared by known or conventional methods. For example, solvent-based acrylic adhesive compositions can be prepared by adding additives (e.g., ultraviolet absorbers) as needed to a solution containing the above-described acrylic polymer. For example, active energy ray-curable acrylic adhesive compositions can be prepared by adding additives (e.g., ultraviolet absorbers) as needed to a mixture of the above-described acrylic monomers or a portion thereof.
[0360] It should be noted that the coating (coating) of the above-mentioned adhesive composition can be performed using known coating methods. For example, gravure roller coating machines, reverse roller coating machines, roller licking coating machines, dip roller coating machines, doctor blade coating machines, doctor blade coating machines, spraying machines, comma coating machines, direct coating machines, and other coating machines can be used.
[0361] In particular, when forming an adhesive layer using an active energy ray-curable adhesive composition, the active energy ray-curable adhesive composition preferably includes a photopolymerization initiator. It should be noted that when the active energy ray-curable adhesive composition contains an ultraviolet absorber, the photopolymerization initiator preferably includes at least a photopolymerization initiator that has light absorption properties over a broad wavelength range. For example, it is preferable to include at least a photopolymerization initiator that has light absorption properties not only in the ultraviolet range but also in the visible light range. This is because there is a concern that the ultraviolet absorber might hinder curing caused by active energy rays; when a photopolymerization initiator with light absorption properties over a broad wavelength range is included, the adhesive composition readily achieves high photocurability.
[0362] <Antistatic layer>
[0363] In the optical adhesive tape of the present invention, an antistatic layer may be provided on the surface or in any interlayer space. By providing an antistatic layer, damage to the adhered object, such as an image display panel, can be prevented. Preferably, the antistatic layer is formed between the substrate of the present invention and the adhesive layer of the present invention.
[0364] There are no particular limitations on the aforementioned antistatic layer; for example, it can be an antistatic layer formed by coating a conductive coating liquid containing a conductive polymer onto the spacer. Specifically, for example, it can be an antistatic layer formed by coating a conductive coating liquid containing a conductive polymer onto the first surface of the substrate of the present invention. Specific coating methods include: roller coating, doctor blade coating, gravure coating, etc.
[0365] Examples of the aforementioned conductive polymers include conductive polymers doped with polyanions within a π-conjugated system. Examples of π-conjugated conductive polymers include chain-like conductive polymers such as polythiophene, polypyrrole, polyaniline, and polyacetylene. Examples of polyanions include polystyrene sulfonic acid, polyisoprene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyethyl acrylate sulfonic acid, and polymethacrylic acids.
[0366] The thickness of the aforementioned antistatic layer is preferably 1 nm to 1000 nm, more preferably 5 nm to 900 nm. The aforementioned antistatic layer may be a single layer or two or more layers.
[0367] <Separator>
[0368] In the optical adhesive tape of the present invention, the surface of the adhesive layer of the present invention (the adhesive surface of the adhesive layer of the present invention) can be protected by a spacer until use. The spacer serves as a protective material for the adhesive layer and is peeled off when the optical adhesive tape of the present invention is adhered to the substrate.
[0369] As the aforementioned spacer, conventional release paper or similar materials can be used. Specifically, for example, a substrate having a release treatment layer formed by a release agent on at least one surface can be used, as well as a low-adhesion substrate containing fluoropolymers (e.g., polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, chlorofluoroethylene-vinylidene fluoride copolymer, etc.) or a low-adhesion substrate containing non-polar polymers (e.g., polyethylene, polypropylene and other olefin resins, etc.).
[0370] As the aforementioned spacer, for example, a spacer with a release treatment layer formed on at least one surface of the spacer substrate is suitable for use. Examples of such spacer substrates include: polyester film (polyethylene terephthalate film, etc.), olefin resin film (polyethylene film, polypropylene film, etc.), polyvinyl chloride film, polyimide film, polyamide film (nylon film), rayon film and other plastic substrate films (synthetic resin film), paper (high-grade paper, Japanese paper, kraft paper, cellophane, synthetic paper, surface-coated paper, etc.); and substrates obtained by multiplying them by lamination, co-extrusion and the like (2- to 3-layer composites).
[0371] There are no particular limitations on the release agent used to constitute the above-mentioned release treatment layer. For example, silicone-based release agents, fluorinated release agents, long-chain alkyl-based release agents, etc., can be used. Two or more release agents can be used alone or in combination.
[0372] There are no particular restrictions on the thickness of the aforementioned spacers; they can be appropriately selected from the range of 5μm to 100μm.
[0373] To prevent damage to the adhered objects such as image display panels, the aforementioned spacer may have an antistatic layer formed on at least one side of the spacer substrate. The antistatic layer may be formed on one side of the spacer (the peeled-off side or the untreated side) or on both sides of the spacer (the peeled-off side and the untreated side).
[0374] There are no particular limitations on the aforementioned antistatic layer; for example, it can be an antistatic layer formed by applying a conductive coating liquid containing a conductive polymer onto the spacer. Specifically, for example, it can be an antistatic layer formed by applying a conductive coating liquid containing a conductive polymer onto the spacer (the peel-off surface and / or the untreated surface). Specific coating methods include: roller coating, doctor blade coating, gravure coating, etc.
[0375] As the conductive polymer described above, the same conductive polymer as the conductive polymer constituting the antistatic layer of the optical adhesive tape of the present invention can be used.
[0376] The thickness of the aforementioned antistatic layer is preferably 1 nm to 1000 nm, more preferably 5 nm to 900 nm. The aforementioned antistatic layer may be a single layer or two or more layers.
[0377] <Surface Protective Film>
[0378] In the optical adhesive tape of the present invention, the second side of the substrate of the present invention can be protected by a surface protective film. This surface protective film is used as a protective material for the second side of the substrate of the present invention during the manufacture or transportation of the optical adhesive tape, the image display device, and the video wall display of the present invention.
[0379] Examples of materials that can form the aforementioned surface protective film include: ester resins such as polyethylene terephthalate resins, cyclic olefin resins such as norbornene resins, olefin resins such as polypropylene resins, polyamide resins, polycarbonate resins, and copolymers thereof. Ester resins (especially polyethylene terephthalate resins) are preferred.
[0380] The thickness of the aforementioned surface protective film is typically 20 μm to 250 μm, preferably 30 μm to 150 μm.
[0381] The aforementioned surface protective film is peelably adhered to the second surface of the substrate of the present invention using any suitable adhesive. Preferably, a surface protective film with an adhesive layer is formed and adhered to the second surface of the substrate of the optical adhesive tape of the present invention. Examples of adhesives used in the lamination of the aforementioned surface protective films include adhesive compositions using acrylic resins, styrene resins, silicone resins, etc., as base resins, and incorporating crosslinking agents selected from isocyanate compounds, epoxy compounds, aziridine compounds, etc., and silane coupling agents, etc., in the base resin. The thickness of the adhesive layer is typically 1 μm to 60 μm, preferably 3 μm to 30 μm. When the adhesive layer is too thin, reduced adhesion and easy incorporation of air bubbles may occur; when the adhesive layer is too thick, adhesive protrusion may occur. From the viewpoint of chemical resistance and adhesion, acrylic adhesives are preferred.
[0382] <Image display device>
[0383] The image display device of the present invention has a laminated structure obtained by laminating the optical adhesive tape of the present invention and the image display panel. Figure 3In the image display device 20, an image display panel 4 is laminated on the adhesive layer 1 of the optical adhesive tape 10B.
[0384] The image display device of the present invention, by incorporating the optical adhesive tape of the present invention in its laminated structure, can suppress shrinkage or expansion under operating conditions and maintain its transparency. Furthermore, the adhesive layer of the present invention fully follows the shrinkage or expansion of the image display device, thereby reducing the likelihood of bulging or peeling. Moreover, when there are height differences in the image display panel caused by wiring or the like, the adhesive layer of the present invention fully follows these height differences, enabling filling without leaving air bubbles or the like.
[0385] There are no particular limitations on the image display panels mentioned above. Examples include liquid crystal display panels, self-emissive display panels (e.g., organic EL (electroluminescent) display panels, LED display panels), etc.
[0386] The aforementioned image display panel is formed by arranging RGB elements alternately. To improve contrast, it is preferable to fill the spaces between the RGB elements with a black matrix (BM).
[0387] The image display device of the present invention may have optical components other than the optical adhesive tape of the present invention and the image display panel described above on its surface or in any interlayer. There are no particular limitations on the optical components described above, and examples include: polarizing plates, phase retardation plates, anti-reflection films, viewing angle adjustment films, optical compensation films, etc. It should be noted that the optical components described above also include components that serve a decorative and protective function while maintaining the visual recognizability of the image display device and the input device (such as appearance design films, decorative films, surface protection plates, etc.).
[0388] The image display device of the present invention can be manufactured by bonding the image display panel described above with the adhesive layer of the optical adhesive tape of the present invention.
[0389] Specifically, the bonding of the image display panel and the optical adhesive tape of the present invention can be carried out by laminating them under heat and / or pressure. Curing can be performed by irradiating with active energy rays after lamination under heat and / or pressure. Irradiation with active energy rays can be carried out in the same manner as the formation of the adhesive layer of the present invention.
[0390] <Video Display>
[0391] The splicing display of the present invention is formed by arranging multiple image display devices of the present invention. Figure 4In this design, the splicing display 30 is formed by arranging nine image display devices 20 (layered structure omitted from illustration) in a 3×3 array on a support substrate 31 in a tile-like pattern, with the image display devices 20 contacting each other through gaps 32. The support substrate can be the same glass plate or plastic film as the substrate of this invention.
[0392] Because the image display device of the present invention suppresses shrinkage or expansion under the operating environment, gaps or overlaps are less likely to occur between multiple image display devices in the splicing display of the present invention, and the gaps are less likely to become noticeable, maintaining a good appearance. Furthermore, minimal shrinkage or expansion maintains transparency. Additionally, the adhesive layer of the present invention can adequately follow the shrinkage or expansion of the image display device, thereby preventing defects caused by bulging or peeling.
[0393] Furthermore, in the splicing display of the present invention, when the second surface of the substrate of the present invention is subjected to anti-reflection treatment and / or anti-glare treatment, it is preferable from the viewpoint that reflections caused by metal wiring, ITO wiring, etc., disposed on the substrate of the image display device of the present invention can be prevented. Additionally, it is also preferable from the viewpoint that the gaps between the image display devices of the present invention are not easily visually discernible in the splicing display.
[0394] The splicing display of the present invention may include components other than the image display device of the present invention and the aforementioned support substrate. There are no particular limitations on such components; examples include: backlights, touch sensors, etc.
[0395] The splicing display of the present invention can be manufactured by arranging multiple image display devices of the present invention without gaps on the aforementioned support substrate and fixing them by using glass to seal the outermost surface or the like.
[0396] Example
[0397] The present invention will now be described in more detail based on embodiments, but the present invention is not limited to these embodiments.
[0398] Manufacturing Example 1
[0399] (Preparation of anti-glare film 1)
[0400] [Preparation of coating liquid for forming anti-glare layer 1]
[0401] The resin contained in the anti-glare layer forming material comprises: 40 parts by weight of UV-curable urethane acrylate resin (manufactured by Shin-Nakamura Chemical Co., Ltd., trade name "NK Oligo UA-53H-80BK"), 57.5 parts by weight of a multifunctional acrylate with pentaerythritol triacrylate as the main component (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name "Viscoat#300"), 2.5 parts by weight of a diluent for an optical conditioning layer composition containing zirconium oxide particles and UV-curable resin ("OPSTAR Z7540", manufactured by JSR Corporation), 2.8 parts by weight of silicone particles (manufactured by Momentive Materials Japan Co., Ltd., trade name "Tospearl 130ND"), 2.5 parts by weight of an organoclay as a thixotropic agent, namely synthetic montmorillonite (manufactured by Kunimine Industry Co., Ltd., trade name "Smecton SAN"), and 3 parts by weight of a photopolymerization initiator (manufactured by BASF Corporation, trade name "OMNIRAD"). 6.5 parts by weight of crosslinked acrylic-styrene copolymer resin particles (manufactured by Sekisui Chemicals Co., Ltd., trade name "SSX-103DXE") and 0.1 parts by weight of leveling agent (manufactured by Kyoei Chemicals Co., Ltd., trade name "LE-303") were mixed. It should be noted that the above-mentioned organoclay was diluted with toluene to a solid content of 6% by weight before use. This mixture was diluted with a toluene / cyclopentanone (CPN) mixed solvent (weight ratio 64 / 36) to a solid content concentration of 38% by weight, and an anti-glare layer forming material (coating liquid) was prepared using an ultrasonic disperser.
[0402] [Formation of anti-glare layer 1]
[0403] A transparent plastic film substrate (PET film, manufactured by Toray Industries, Inc., trade name "38U413", thickness: 38μm) was prepared as the substrate. The anti-glare layer forming material (coating liquid) was applied to one side of the transparent plastic film substrate using a winding bar to form a coating film (coating process). Next, the coating film was dried by heating at 95°C for 1 minute (drying process). Then, it was irradiated with a high-pressure mercury lamp with a cumulative light intensity of 300 mJ / cm². 2 The coating was cured by ultraviolet light to form an anti-glare layer with a thickness of 6.5 μm. In this way, a laminate of the light-transmitting substrate and the anti-glare layer 1 was obtained.
[0404] [Preparation of coating solution for forming antireflective layer 1]
[0405] 100 parts by weight of a multifunctional acrylate with pentaerythritol triacrylate as the main component (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name "Viscoat#300"), 100 parts by weight of hollow silica nanoparticles (manufactured by Nichibukai Chemical Industry Co., Ltd., trade name "THRULYA 5320"), 40 parts by weight of solid silica nanoparticles (manufactured by Nissan Chemical Industry Co., Ltd., trade name "MIBK-ST", solid content 30% by weight, weight average particle size 10nm), 12 parts by weight of a fluorine-containing additive (manufactured by Shin-Etsu Chemical Industry Co., Ltd., trade name "KY-1203"), 5 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "OMNIRAD 907") and 5 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "OMNIRAD 2959") were mixed together. A mixed solvent obtained by mixing MIBK (methyl isobutyl ketone) and PMA (propylene glycol monomethyl ether acetate) in a weight ratio of 70:30 was added to the mixture as a diluent to bring the total solid content to 1.5% by weight, and the mixture was stirred to prepare a coating liquid for forming an antireflective layer.
[0406] [Formation of Antireflective Layer 1]
[0407] The anti-reflection layer forming coating liquid is applied to the anti-glare layer of the laminate of the transparent substrate and the anti-glare layer 1 using a winding rod (coating process). The coating liquid is heated at 80°C for 1 minute to dry it, thereby forming a coating film (drying process). The dried coating film is irradiated with a high-pressure mercury lamp, and the cumulative light intensity is 300 mJ / cm. 2 The coating is cured by ultraviolet light (curing process). This cures the coating, thereby forming an anti-reflective layer 1 with a thickness of 0.1 μm (anti-reflective layer formation process). The anti-glare film 1 of this Manufacturing Example 1 was manufactured in the manner described above.
[0408] Manufacturing Example 2
[0409] (Preparation of anti-glare film 2)
[0410] [Formation of anti-glare layer 2]
[0411] In the preparation of the coating liquid for forming the anti-glare layer, the amount of the polyfunctional acrylate with pentaerythritol triacrylate as the main component was changed to 60 parts by weight, the amount of organosilicon particles was changed to 0.9 parts by weight, the organic clay, i.e., synthetic montmorillonite, which is used as a thixotropic agent, was changed to 1.5 parts by weight, and the diluent of the optical conditioning layer composition containing zirconium oxide particles and ultraviolet curable resin and the crosslinked acrylic-styrene copolymer resin particles were not used. Otherwise, the above-mentioned translucent substrate and anti-glare layer 2 laminate was manufactured by the same method as in manufacturing example 1.
[0412] [Formation of Antireflective Layer 2]
[0413] In the preparation of the coating liquid for forming the antireflective layer, the amount of the aforementioned hollow silica nanoparticles was changed to 240 parts by weight. Otherwise, the antireflective layer 2 was formed using the same method as in Manufacturing Example 1. The anti-glare film 2 of Manufacturing Example 2 was manufactured in the manner described above.
[0414] Manufacturing Example 3
[0415] (Preparation of anti-glare film 3)
[0416] In the formation of the anti-glare layer, a transparent plastic film substrate (COP film, manufactured by Zeon Corporation of Japan, trade name "ZF14", thickness: 50μm) was used as the substrate. Otherwise, the anti-glare film 3 of this manufacturing example 3 was manufactured by the same method as in manufacturing example 1.
[0417] Manufacturing Example 4
[0418] (Preparation of anti-glare film 4)
[0419] In the formation of the anti-glare layer, a transparent plastic film substrate (PEN film, manufactured by Toyobo Co., Ltd., trade name "Q51", thickness: 25μm) was used as the substrate. Otherwise, the anti-glare film 4 of this manufacturing example 4 was manufactured by the same method as in manufacturing example 1.
[0420] Manufacturing Example 5
[0421] (Preparation of anti-glare film 5)
[0422] In the formation of the anti-glare layer, a transparent plastic film substrate (PEEK film, manufactured by Kurabo Co., Ltd., trade name "EXPEEK", thickness: 50μm) was used as the substrate. Otherwise, the anti-glare film 5 of this manufacturing example 5 was manufactured by the same method as in manufacturing example 1.
[0423] Manufacturing Example 6
[0424] (Manufacturing of transparent plastic film substrate)
[0425] Relative to 81.98 parts by mass of isosorbide (hereinafter sometimes referred to as "ISB"), 47.19 parts by mass of tricyclodecanediethanol (hereinafter sometimes referred to as "TCDDM"), 175.1 parts by mass of diphenyl carbonate (hereinafter sometimes referred to as "DPC"), and 0.979 parts by mass of a 0.2% by mass aqueous solution of cesium carbonate as a catalyst were added to a reaction vessel. As the first stage of the reaction, under a nitrogen atmosphere, the temperature of the heating tank was raised to 150°C, and the raw materials were dissolved by stirring as needed (approximately 15 minutes). Next, the pressure was adjusted from atmospheric pressure to 13.3 kPa, and the temperature of the heating tank was raised to 190°C over 1 hour, while the generated phenol was extracted from the reaction vessel. The entire reaction vessel was maintained at 190°C for 15 minutes. Then, as the second stage, the pressure inside the reaction vessel was adjusted to 6.67 kPa, and the temperature of the heating tank was raised to 230°C over 15 minutes, while the generated phenol was extracted from the reaction vessel. Due to the increased stirring torque of the mixer, the temperature was raised to 250°C over 8 minutes. Then, to remove the generated phenol, the pressure inside the reaction vessel was brought down to below 0.200 kPa. After reaching the specified stirring torque, the reaction was terminated, and the resulting reaction product was extruded into water, thus obtaining polycarbonate resin granules. The obtained polycarbonate resin was vacuum dried at 80°C for 5 hours, and then a transparent plastic film substrate with a thickness of 40 μm made of polycarbonate resin was produced using a film-forming apparatus equipped with a single-screw extruder (manufactured by Shibaura Machinery Co., Ltd., barrel set temperature: 250°C), a T-die (width 300 mm, set temperature: 250°C), a cooling roller (set temperature: 120°C~130°C), and a winding machine.
[0426] (Preparation of anti-glare film 6)
[0427] In the formation of the anti-glare layer, the transparent plastic film substrate made of polycarbonate resin obtained above was used as the substrate. Otherwise, the anti-glare film 6 of this manufacturing example 6 was manufactured by the same method as manufacturing example 1.
[0428] Manufacturing Example 7
[0429] (Preparation of anti-glare film 7)
[0430] In the formation of the anti-glare layer, a transparent plastic film substrate (CPI film, manufactured by KOLON Corporation, trade name "C_50_D", thickness: 50μm) was used as the substrate. Otherwise, the anti-glare film 7 of this manufacturing example 7 was manufactured by the same method as in manufacturing example 1.
[0431] Manufacturing Example 8
[0432] (Preparation of anti-glare film 8)
[0433] In the formation of the anti-glare layer, a transparent plastic film substrate (TAC film, manufactured by Fujifilm Corporation, trade name "TD80UL", thickness: 80μm) was used as the substrate. Otherwise, the anti-glare film 8 of this manufacturing example 8 was manufactured by the same method as in manufacturing example 1.
[0434] Manufacturing Example 9
[0435] (Preparation of acrylic adhesive composition 1)
[0436] [Preparation of acrylic acid oligomers]
[0437] 60 parts by weight of tetrahydrodicyclopentadienyl methacrylate (DCPMA) and 40 parts by weight of methyl methacrylate (MMA), 3.5 parts by weight of α-thioglycerol as a chain transfer agent, and 100 parts by weight of toluene as a polymerization solvent were mixed and stirred at 70°C for 1 hour under a nitrogen atmosphere. Next, 0.2 parts by weight of 2,2'-azobisisobutyronitrile (AIBN) as a thermal polymerization initiator were added, and the reaction was carried out at 70°C for 2 hours, then the temperature was raised to 80°C and reacted for another 2 hours. The reaction mixture was then heated to 130°C and dried to remove toluene, chain transfer agent, and unreacted monomers, thus obtaining a solid acrylic oligomer (acrylic oligomer A). Acrylic oligomer A has a weight-average molecular weight of 5100 and a glass transition temperature (Tg) of 130°C.
[0438] [Preparation of Prepolymer and Acrylic Adhesive Composition 1]
[0439] The prepolymer composition was obtained by combining 60 parts by weight of lauryl acrylate (LA), 22 parts by weight of 2-ethylhexyl acrylate (2EHA), 8 parts by weight of 4-hydroxybutyl acrylate (4HBA), and 10 parts by weight of N-vinyl-2-pyrrolidone (NVP) as monomer components for prepolymer formation, and 0.1 parts by weight of "Omnirad 184" and 0.1 parts by weight of "Omnirad 651" manufactured by BASF as photopolymerization initiators, and polymerizing them by irradiation with ultraviolet light. In 100 parts by weight of the above prepolymer composition, 37 parts by weight of 2-ethylhexyl acrylate (2EHA), 0.08 parts by weight of 1,6-hexanediol diacrylate (trade name "A-HD-N", manufactured by Shin-Nakamura Chemical Co., Ltd.), 6 parts by weight of the above acrylic oligomer A, and 0.3 parts by weight of silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., "KBM403") were added as post-addition components, and then they were mixed uniformly to prepare acrylic adhesive composition 1.
[0440] Manufacturing Example 10
[0441] (Preparation of prepolymer and acrylic adhesive composition 2)
[0442] A prepolymer composition was obtained by combining 67 parts by weight of butyl acrylate (BA), 14 parts by weight of cyclohexyl acrylate (Viscoat #155 manufactured by Osaka Organic Chemicals Co., Ltd.), and 19 parts by weight of 4-hydroxybutyl acrylate (4HBA) as monomer components for prepolymer formation, and 0.09 parts by weight of Omnirad 184 manufactured by BASF and Omnirad 651 manufactured by BASF as photopolymerization initiators, and polymerizing them by irradiation with ultraviolet light. To 100 parts by weight of the above-mentioned prepolymer composition, 9 parts by weight of hydroxyethyl acrylate (HEA), 8 parts by weight of 4-hydroxybutyl acrylate (4HBA), 0.02 parts by weight of dipentaerythritol hexaacrylate (DPHA), 0.3 parts by weight of photopolymerization initiator ("Omnirad 651" manufactured by BASF) and 0.35 parts by weight of silane coupling agent ("KBM403" manufactured by Shin-Etsu Chemical Co., Ltd.) were added as post-addition components, and then they were mixed uniformly to prepare acrylic adhesive composition 2.
[0443] Manufacturing Example 11
[0444] (Preparation of prepolymer and acrylic adhesive composition 3)
[0445] The prepolymer composition was obtained by combining 78 parts by weight of 2-ethylhexyl acrylate (2EHA), 4 parts by weight of hydroxyethyl acrylate (HEA), and 18 parts by weight of N-vinyl-2-pyrrolidone (NVP) as monomer components for prepolymer formation, and 0.035 parts by weight of "Omnirad 184" and 0.035 parts by weight of "Omnirad 651" manufactured by BASF as photopolymerization initiators, and by irradiating with ultraviolet light. To 100 parts by weight of the above-mentioned prepolymer composition, 17.6 parts by weight of hydroxyethyl acrylate (HEA), 0.294 parts by weight of 1,6-hexanediol diacrylate (trade name "A-HD-N", manufactured by Shin-Nakamura Chemical Co., Ltd.), 11.8 parts by weight of the above-mentioned acrylic oligomer A, and 0.35 parts by weight of silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., "KBM403") were added as post-addition components, and then they were mixed uniformly to prepare acrylic adhesive composition 3.
[0446] Example 1
[0447] (Preparation of substrate-free adhesive layer 1)
[0448] A polyethylene terephthalate (PET) film (manufactured by Mitsubishi Chemical Corporation, "Diafoil MRF75") with a thickness of 75 μm and an organosilicon release layer on its surface was used as a substrate (also serving as a heavy-duty release film). The aforementioned acrylic adhesive composition 1 was coated onto the release layer of the substrate with a thickness of 25 μm, thereby forming a coating layer. A 75 μm thick PET film (manufactured by Mitsubishi Chemical Corporation, "Diafoil MRE75") with a release layer that had undergone organosilicon release treatment on one side was then bonded onto the coating layer as a protective sheet (also serving as a light-duty release film). The irradiation intensity of the irradiation surface directly below the lamp was set to 5 mW / cm². 2 A black light with adjustable position was used to irradiate the laminate with ultraviolet light from the protective sheet side to perform photocuring, thereby obtaining a substrate-free adhesive layer 1 with a thickness of 25 μm.
[0449] (Preparation of Adhesive Tape 1)
[0450] The adhesive surface exposed by peeling a release film from the substrate-free adhesive layer 1 obtained above is attached to the non-anti-glare layer of the anti-glare film 1 shown in Manufacturing Example 1, thereby obtaining an adhesive tape 1 comprising the anti-glare film 1, the adhesive layer 1, and the release film.
[0451] Example 2
[0452] (Preparation of Adhesive Tape 2)
[0453] In addition to using the anti-glare film 2 described above, an adhesive tape 2 comprising the anti-glare film 2 / adhesive layer 1 / release film was obtained in the same manner as in Example 1.
[0454] Example 3
[0455] (Preparation of substrate-free adhesive layer 2)
[0456] In addition to using the acrylic adhesive composition 2 described above, a substrate-free adhesive layer 2 with a thickness of 25 μm was obtained in the same manner as in Example 1.
[0457] (Preparation of adhesive tape 3)
[0458] In addition to using the substrate-free adhesive layer 2 obtained above, an adhesive tape 3 comprising an anti-glare film 1 / adhesive layer 2 / release film was obtained in the same manner as in Example 1.
[0459] Example 4
[0460] (Preparation of adhesive tape 4)
[0461] In addition to using the anti-glare film 3 described above, an adhesive tape 4 comprising the anti-glare film 3, adhesive layer 1, and release film was obtained in the same manner as in Example 1.
[0462] Example 5
[0463] (Preparation of adhesive tape 5)
[0464] In addition to using the anti-glare film 4 described above, an adhesive tape 5 comprising the anti-glare film 4, adhesive layer 1, and release film was obtained in the same manner as in Example 1.
[0465] Example 6
[0466] (Preparation of adhesive tape 6)
[0467] In addition to using the anti-glare film 5 described above, an adhesive tape 6 comprising the anti-glare film 5, adhesive layer 1, and release film was obtained in the same manner as in Example 1.
[0468] Example 7
[0469] (Preparation of adhesive tape 7)
[0470] In addition to using the anti-glare film 6 described above, an adhesive tape 7 comprising the anti-glare film 6, adhesive layer 1, and release film was obtained in the same manner as in Example 1.
[0471] Example 8
[0472] (Preparation of Adhesive Tape 8)
[0473] In addition to using the anti-glare film 7 described above, an adhesive tape 8 comprising the anti-glare film 7, adhesive layer 1, and release film was obtained in the same manner as in Example 1.
[0474] Comparative Example 1
[0475] (Preparation of Adhesive Tape 9)
[0476] In addition to using the anti-glare film 8 described above, an adhesive tape 9 comprising the anti-glare film 8, adhesive layer 1, and release film was obtained in the same manner as in Example 1.
[0477] Comparative Example 2
[0478] (Preparation of substrate-free adhesive layer 3)
[0479] In addition to using the acrylic adhesive composition 3 described above, a substrate-free adhesive layer 3 with a thickness of 25 μm was obtained in the same manner as in Example 1.
[0480] (Preparation of adhesive tape 10)
[0481] In addition to using the anti-glare film 8 and the substrate-free adhesive layer 3 described above, an adhesive tape 10 comprising the anti-glare film 8 / adhesive layer 3 / release film was obtained in the same manner as in Example 1.
[0482] (evaluate)
[0483] The adhesive tapes obtained in the above embodiments and comparative examples were evaluated as follows. The evaluation method is shown below. The results are shown in Table 2.
[0484] (1) Average dimensional change rate
[0485] The adhesive tape prepared in each embodiment and comparative example was cut into a top view approximate square with a diameter of 100mm in the MD direction and a diameter of 100mm in the TD direction. Cross-pattern scratches were made on each of the four corners to create test pieces.
[0486] For the test piece before heating (25°C), the distance (length) between the MD direction and the distance (length) between the scratches (centers of the cross pattern) were measured at room temperature (25°C) using a CNC three-dimensional measuring instrument (manufactured by Mitutoyo Corporation, "LEGEX774"). Thus, the lengths before heating in the MD and TD directions were obtained.
[0487] Next, the test piece was heated at 60°C and 90% relative humidity for 500 hours, and then naturally cooled at room temperature (25°C) for 1 hour. Then, the distances between the scratches in the MD and TD directions were measured using a CNC 3D measuring instrument. This yielded the lengths after heating in both the MD and TD directions. Next, the dimensional change rates A1 and A2 in the MD and TD directions were calculated using the following formula, and their average value was taken as the average dimensional change rate (%). Furthermore, the ratio of the dimensional change rate in the MD direction to the dimensional change rate in the TD direction (A1 / A2) was calculated.
[0488] Dimensional change rate (%) = [Length after heating (mm) - Length before heating (mm)] / Length before heating (mm) × 100
[0489] Average dimensional change rate (%) = [Dimensional change rate in MD direction + Dimensional change rate in TD direction] / 2
[0490] (2) Maximum curl
[0491] The release film of the adhesive tape prepared in each embodiment and each comparative example was peeled off, a PET film (manufactured by Mitsubishi Chemical Corporation, trade name "Diafoil T100E50") was pasted on, and the resulting laminate was cut into a 100mm × 100mm top-view approximately square to produce a test piece.
[0492] Next, the test piece was heated at 60°C and 90% relative humidity for 500 hours, and then naturally cooled at room temperature (25°C) for 1 hour. Then, it was placed on a horizontal surface with the curled and convex side facing down, and the distances from the four corner points to the horizontal surface were measured. The distance from the longest point to the horizontal surface was taken as the maximum curl amount (mm).
[0493] It should be noted that the maximum amount of curl measured when the laminate is placed on a horizontal surface with the PET film side of the laminate as the bottom side is set as +, and the maximum amount of curl measured when the laminate is placed on a horizontal surface with the substrate side (opposite side of the PET film) of the laminate as the bottom side is set as -.
[0494] (3) Reflectivity
[0495] The adhesive surfaces of the adhesive tapes obtained in each embodiment and comparative example were adhered to a black acrylic resin plate to prepare test pieces. The test pieces were then tested in a spectrophotometer U4100 (manufactured by Hitachi High Technology Co., Ltd.) with the adhesive tape side facing the light source side, and the reflectance (%) of the visible light region with 5° positive reflection was measured.
[0496] (4) Haze
[0497] The adhesive tapes obtained in each example and comparative example were measured at room temperature (23°C) using a haze measuring device (manufactured by Murakami Color Research Institute, HR-100). The measurements were repeated three times, and the average value was taken as the measured value.
[0498] (5) Dependent variable A, dependent variable B and recovery rate
[0499] The spacer was peeled off from the adhesive layer obtained in the various embodiments and comparative examples, and multiple adhesive layers were stacked to prepare a test sample with a thickness of approximately 2 mm. This test sample was then punched into a disk shape with a diameter of 7.9 mm and used as the specimen. A shear test was conducted to determine "strain A", "strain B", and "recovery rate". Figure 5 The procedure is as shown. Specifically, an "Advanced Rheometric Expansion System (ARES)" manufactured by Rheometric Scientific, with parallel plates 41 and 42 having a diameter of 7.9 mm, is used, aligning and contacting the upper surface of parallel plate 41 and the bottom surface of parallel plate 42 with the bottom and upper surfaces of the adhesive layer of the sample, respectively. Figure 5 (b) Next, dynamic viscoelasticity measurements were performed under the following conditions, and the readings were taken at 500 Pa and 600 seconds. Figure 5 (c) The dependent variable A was then read, and the time when it remained at 0 Pa for 1800 seconds was recorded. Figure 5 (d) The dependent variable B is calculated using the following formula to determine the recovery rate.
[0500] (Measurement conditions)
[0501] Deformation mode: Torsion
[0502] Measurement procedure: Hold at 500 Pa for 600 seconds, then at 0 Pa for 1800 seconds.
[0503] Measurement temperature: 60℃
[0504] Axial force: 0.2N
[0505] Recovery rate: (Due variable A - Dependent variable B) / Dependent variable A × 100
[0506] (6) Storage modulus, loss tangent and glass transition temperature of adhesive layer
[0507] The spacer was peeled off from the adhesive layer obtained in the various embodiments and comparative examples, and multiple adhesive layers were stacked to prepare a test sample with a thickness of approximately 2 mm. This test sample was punched into a disk shape with a diameter of 7.9 mm, sandwiched between parallel plates, and dynamic viscoelasticity was measured using an "Advanced Rheometric Expansion System (ARES)" manufactured by Rheometric Scientific under the following conditions. The storage modulus G' and loss tangent tanδ at each temperature were read from the measurement results. Furthermore, the temperature at which tanδ reaches its maximum was taken as the glass transition temperature of the adhesive layer.
[0508] (Measurement conditions)
[0509] Deformation mode: Torsion
[0510] Measurement frequency: 1Hz
[0511] Measurement temperature: -70℃~150℃
[0512] (7) Shear force of adhesive layer
[0513] The adhesive tape obtained in each embodiment and comparative example was cut into pieces with a width of 10 mm and a length of 100 mm. The spacer was peeled off, and then the adhesive area of the adhesive layer of the above-mentioned adhesive tape was 1 cm². 2 It is bonded to an acrylic resin board (Acrylite, manufactured by Mitsubishi Chemical Corporation) in a specific manner, and then pulled along the shear direction at a peeling speed of 0.06 mm / min at 23°C to achieve the maximum load (N / cm²). 2 ( ) as shear force.
[0514] (8) 300% tensile residual stress value of adhesive layer
[0515] The adhesive layers obtained in the various embodiments and comparative examples were cut into 40mm × 40mm pieces. A spacer on one side was peeled off, and the layers were folded once with the adhesive sides facing each other. The spacer on one side was peeled off again, and the adhesive sides were faced each other again, thus producing an adhesive layer sample with a size of approximately 10mm × 40mm and a thickness of approximately 400μm. The adhesive layer sample was placed in a tensile testing machine with the clamp spacing set to 20mm, and stretched for 60mm (300%) at a tensile speed of 200mm / min (the clamp spacing after stretching was 80mm). The sample was held at the 60mm stretch position for 300 seconds, and the stress value was measured. The "300% tensile residual stress value" was calculated using the following formula.
[0516] 300% tensile residual stress value (N / cm) 2 = Stress value after holding for 300 seconds (N) / (4 × adhesive sheet thickness (mm) / 10)
[0517] (9) Humidity expansion rate
[0518] The adhesive tapes obtained in each embodiment and comparative example were cut into pieces with a width of 2 mm in the TD direction and a length of 20 mm in the MD direction, and were measured under the following conditions using an HC-TMA4000SA type manufactured by Bruker AXS Co., Ltd.
[0519] (Measurement conditions)
[0520] Deformation mode: Stretch
[0521] Load: 2g
[0522] Duration: 5 hours
[0523] Humidity increase rate: 5%RH / minute
[0524] Measurement atmosphere: Maintain at 60℃ and 30% relative humidity until saturation, and then control the temperature to 60℃ and relative humidity to 60%.
[0525] (10) Coefficient of moisture expansion of substrate
[0526] The coefficient of thermal expansion (CTE) was determined by measuring the elongation of each film at 60°C as the humidity changed from 30% RH to 60% RH using a Bruker AXS HC-TMA4000SA film (unit: / RH%). The CTE (α) was calculated using the following formula.
[0527] α=ΔL / {(T2-T1)×L}
[0528] T1: Calculate the humidity (%RH) on the low humidity side for the humidity expansion coefficient.
[0529] T2: Calculate the humidity (%RH) on the high humidity side, which has the coefficient of humidity expansion.
[0530] ΔL: The difference (μm) between the length of the test piece at time T1 and time T2.
[0531] L: Length (μm) of the test piece at room temperature (60℃)
[0532] (11) Glass transition temperature (Tg) of the substrate
[0533] Take approximately 8 mg of the sample, place it in an aluminum container, and perform DSC analysis.
[0534] Device: Q-2000 manufactured by TA Instruments
[0535] Container: Aluminum container
[0536] Temperature program: -30℃ → 300℃
[0537] Heating rate: 10℃ / minute
[0538] Atmospheric gas: N2 (50 ml / min)
[0539] (12) Confirmation of gaps between adhesive tapes
[0540] The adhesive tapes obtained in the examples and comparative examples were cut into 5cm × 5cm pieces. Four pieces of adhesive tape were then bonded to the glass without gaps and heated at 60°C and 90% relative humidity for 500 hours, followed by natural cooling at room temperature (25°C) for 1 hour. The glass was then placed on a backlight, and the gaps between the adhesive tapes when illuminated by the backlight were visually evaluated according to the following criteria.
[0541] ○……The gap between the adhesive tapes has not been identified.
[0542] ×……Confirmed the gap between the adhesive tapes
[0543] (13) Adhesive peeling confirmation
[0544] The ends of the adhesive tapes used in the gap confirmation between the adhesive tapes were examined using an optical microscope. The samples were heated for 500 hours at 60°C and 90% relative humidity. The samples were evaluated according to the following criteria.
[0545] ○……No adhesive tape peeling detected.
[0546] ×……Confirmed that the adhesive tape has peeled off.
[0547]
[0548] The following are variations of the present invention.
[0549] [Appendix 1] An optical adhesive tape, the optical adhesive tape having a laminated structure obtained by laminating a substrate and an adhesive layer, the substrate having a first side and a second side, the adhesive layer being laminated on the first side of the substrate, characterized in that...
[0550] The average dimensional change rate in both the width and length directions of the optical adhesive tape was within ±0.15% after being heated at 60°C and 90% relative humidity for 500 hours.
[0551] The recovery rate of the adhesive layer determined in the following shear test is less than 95%.
[0552] <Shear Test>
[0553] The strain A (%) was measured when a torsional shear force of 500 Pa was applied to a 2 mm thick, 7.9 mm diameter disc-shaped adhesive layer at 60 °C for 600 seconds, and the strain B (%) was measured when the layer was held at a shear force of 0 Pa for 1800 seconds. The recovery rate (%) was calculated using the following formula.
[0554] Recovery rate (%) = (Sufficiency A - Sufficiency B) / Sufficiency A × 100
[0555] [Note 2] The optical adhesive tape as described in Note 1, wherein the optical adhesive tape satisfies the following formula:
[0556] |C×D|≤3
[0557] In the above formula,
[0558] C represents the average dimensional change rate [%) of the optical adhesive tape in the width and longitudinal directions after heating it at 60°C and 90% relative humidity for 500 hours.
[0559] D is the maximum curl [mm] of the laminate obtained by bonding the adhesive layer of the optical adhesive tape onto a 50μm thick PET film and then cutting it into 10cm squares, and heating the laminate at 60°C and 90% relative humidity for 500 hours.
[0560] • Maximum curl amount: With the convex side of the laminate facing down on a horizontal surface, the highest warp amount among the four corner warp amounts is defined as the maximum curl amount D [mm]. The maximum curl amount measured with the PET film side of the laminate facing down on a horizontal surface is defined as +, and the maximum curl amount measured with the substrate side of the laminate facing down on a horizontal surface is defined as -.
[0561] [Note 3] The optical adhesive tape as described in Note 1 or 2, wherein the strain A of the adhesive layer is 3% or more.
[0562] [Note 4] The optical adhesive tape as described in any one of Notes 1 to 3, wherein the strain B of the adhesive layer is 0.1% or more.
[0563] [Note 5] The optical adhesive tape as described in any one of Notes 1 to 4, wherein the glass transition temperature (Tg) of the substrate is 60°C or higher.
[0564] [Note 6] The optical adhesive tape as described in any one of Notes 1 to 5, wherein the glass transition temperature (Tg) of the adhesive layer is below -10°C.
[0565] [Note 7] The optical adhesive tape as described in any one of Notes 1 to 6, wherein the humidity expansion rate of the optical adhesive tape when humidified from 60°C and 30% relative humidity to 60°C and 60% relative humidity is 0.1% or less.
[0566] [Note 8] The optical adhesive tape as described in any one of Notes 1 to 7, wherein the coefficient of hygroscopic expansion of the substrate is 5 × 10⁻⁶. -5 Below / %RH.
[0567] [Note 9] The optical adhesive tape as described in any one of Notes 1 to 8, wherein the second side of the substrate is treated with anti-reflection and / or anti-glare treatment.
[0568] [Note 10] The optical adhesive tape as described in any one of Notes 1 to 9, wherein the adhesive layer is an acrylic adhesive layer comprising an acrylic polymer.
[0569] [Note 11] An image display device, wherein the image display device is obtained by laminating an image display panel and an optical adhesive tape as described in any one of Notes 1 to 10.
[0570] [Note 12] A video wall display, wherein the video wall display is obtained by arranging a plurality of image display devices as described in Note 11.
[0571] Label Explanation
[0572] 10A and 10B Optical Adhesive Tapes
[0573] 1. Substrate
[0574] 1a First surface of the substrate
[0575] 1b The second side of the substrate
[0576] 2 Adhesive layer
[0577] 3. Anti-reflective treatment and / or anti-glare treatment
[0578] 20 Image display devices
[0579] 4. Image display panel
[0580] 30-unit video wall
[0581] 31 Supporting substrate
[0582] 40 Adhesive layer
[0583] 41, 42 parallel plates
Claims
1. An optical adhesive tape, the optical adhesive tape having a laminated structure obtained by laminating a substrate and an adhesive layer, the substrate having a first side and a second side, the adhesive layer being laminated on the first side of the substrate, characterized in that, The materials constituting the substrate are polyester resins, polysulfones, polyarylates, polyetheretherketones, polyimides, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, or ethylene-propylene copolymers. The haze of the substrate is 5% or higher. The average dimensional change rate in both the width and length directions of the optical adhesive tape was within ±0.15% after heating it at 60°C and 90% relative humidity for 500 hours. The recovery rate of the adhesive layer determined in the following shear test is less than 95%. <Shear Test> The strain A (%) was measured when a torsional shear force of 500 Pa was applied to a 2 mm thick, 7.9 mm diameter disc-shaped adhesive layer at 60 °C for 600 seconds, and the strain B (%) was measured when the layer was held at a shear force of 0 Pa for 1800 seconds. The recovery rate (%) was calculated using the following formula. Recovery rate (%) = (dependent variable A - dependent variable B) / dependent variable A × 100.
2. The optical adhesive tape as claimed in claim 1, wherein, The optical adhesive tape satisfies the following formula: |C×D|≤3 In the above formula, C represents the average dimensional change rate [%] in both the width and length directions of the optical adhesive tape after heating it at 60°C and 90% relative humidity for 500 hours. D is the maximum curl [mm] of the following when the adhesive layer of the optical adhesive tape is bonded to a 50 μm thick PET film, then cut into 10 cm squares to obtain a laminate, and the laminate is heated at 60°C and 90% relative humidity for 500 hours. Maximum curl amount: With the convex side of the laminate facing down on a horizontal surface, the highest warp amount among the four corner warp amounts is defined as the maximum curl amount D [mm]; the maximum curl amount measured with the PET film side of the laminate facing down on a horizontal surface is defined as +, and the maximum curl amount measured with the substrate side of the laminate facing down on a horizontal surface is defined as -.
3. The optical adhesive tape as described in claim 1 or 2, wherein, The strain A of the adhesive layer is 3% or more.
4. The optical adhesive tape as described in claim 1 or 2, wherein, The strain B of the adhesive layer is 0.1% or more.
5. The optical adhesive tape as described in claim 1 or 2, wherein, The glass transition temperature (Tg) of the substrate is above 60°C.
6. The optical adhesive tape as described in claim 1 or 2, wherein, The glass transition temperature (Tg) of the adhesive layer is below -10°C.
7. The optical adhesive tape as described in claim 1 or 2, wherein, The humidity expansion rate of the optical adhesive tape when humidified from 60°C and 30% relative humidity to 60°C and 60% relative humidity is less than 0.1%.
8. The optical adhesive tape as described in claim 1 or 2, wherein, The coefficient of hygroscopic expansion of the substrate is 5 × 10⁻⁶. -5 The following is / %RH.
9. The optical adhesive tape as described in claim 1 or 2, wherein, The second surface of the substrate is treated with anti-reflective and / or anti-glare treatment.
10. The optical adhesive tape as claimed in claim 1 or 2, wherein, The adhesive layer is an acrylic adhesive layer containing an acrylic polymer.
11. An image display device, wherein, The image display device is obtained by laminating an image display panel and an optical adhesive tape according to any one of claims 1 to 10.
12. A video wall display, wherein, The splicing display is obtained by arranging multiple image display devices as described in claim 11.
Citation Information
Patent Citations
Acrylic adhesives and its production method
JP2002069411A
Cured coating film, Anti-reflection hard coating film using it, polarization plate and image display device
JP2008088309A
Antiglare film, polarizing plate, image display apparatus, and method for manufacturing antiglare film
JP2017138620A
Display member device and display device
JP2017161634A
Adhesive sheet for optical use
CN102791815A